Interconnected macroporous foamed hydrogels enable stable and efficient nitrogen removal in low temperature Anammox systems - Wanqi Liu; Ning An; Yuhan Zhu; Peng Gao; Tingting Liu; Xingrong Yao; Kaiyao Hu; Jun Li; Dongyue Li; Zhaoming Zheng; Zehao Zhang (Water Research, 2027)

Optimising baffle layout for more balanced force distribution and progressive energy dissipation in high-velocity granular avalanches - Quanzhong Lu; Ning Hu; Bei Zhang; Zaiyan Wu; Da Huang; Hengxing Lan; Jianbing Peng (European Journal of Environmental and Civil Engineering, 2026)

Comprehensive study of the tumor immune microenvironment and the prognostic significance of reticulocalbin-1: a pan-cancer analysis - JiangLi Zhao; XuChen Liu; QingYuan Sun; ShuJie Peng; ZhiWei Xue; JunZhi Liu; Bin Huang; JiWei Wang; Chao Li; Ning Yang; Xinyu Wang (Functional & Integrative Genomics, 2026)

Mechanism and engineering evaluation of multi-element removal in lead-bismuth fast reactor concentrate using commercial ion exchange resins - Shiyang Peng; Jiayu Li; Shuang Li; Ning Zhang; Kaiyuan Jiang; Hua Xie (Annals of Nuclear Energy, 2026)

A novel inversion method for assessing pipe corrosion condition based on upstream-downstream water quality variation in drinking water distribution systems - Yun-Qiao Zeng; Tian-Yang Zhang; Zhen-Ning Luo; Ling Hu; Bing Geng; Renjie Pan; Zhu Peng; Dai-Xu Zhang; Yi-Ru Chen; Huan He; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Cropping diversification increases microbial network complexity associated with enhanced soil multifunctionality and resistance to global change - Qian Guo; Peng He; Rui Li; Rong Yang; Jianing Wang; Tengfei Ma; Ning Ling; Lina Zheng; Zhaoming Wang (Soil and Tillage Research, 2026)

A critical review on microalgae-driven wastewater treatment: Dual focus on high-value bioproducts recovery and emerging contaminants removal - Shuli Liu; Jiajun Hua; Yuhong Zhang; Yatong Gao; Xiaohong Han; Yali Liu; Glen T. Daigger; Qi Li; Ning Guo; Zhixin Song; Peng Zhang; Xiane Zhang; et al. (Journal of Environmental Sciences, 2026)

Effects of extraction methodologies on structural characterization and gut microbiota fermentation properties of Apocynum venetum polysaccharides - Linlu Xiao; Yilai Wan; Mengyu Jiang; Zhen Liu; Guandi Chen; Sheng Ke; Jiahui Jiang; Song Guo; Peng Yu; Haotian Wu; Anqi Wang; Ming Ning; et al. (Food Research International, 2026)

Xylitol-regulated interfacial polymerization enables high-permeance and antifouling nanofiltration membranes for selective surface water purification - Guangchao Li; Yixuan Li; Guangjian Bao; Xinwei Kang; Jianjun Zhu; Yongshan Ma; Ning Wang; Xinyu Zhang; Hong Peng; Xuewu Zhu (Desalination, 2026)

Multi-omics reveals novel CYP450s and transcription factors regulating triterpenoid biosynthesis in Aralia elata - Yao Cheng; Hanbing Liu; Ning Cao; Qingyi Zhao; Yutong Jiang; Miao Jiang; Peng Gao; Xinmei Jiang (Plant Science, 2026)

Two new acylated iridoid glycosides with insulin resistance-improving activity from Scrophularia ningpoensis - Wen-Ying Zhou; Yu-Xin Peng; Bi-Qing Zhao; Hong-Yu Jiang; Xi-Ning Sun; Guang-Yun Su; Li Li; Xiao-Jiang Zhou (Phytochemistry Letters, 2026)

Genesis of high-grade uranium mineralization in sandstone-hosted uranium deposits in the northern Sichuan Basin - Zongbo Zhang; Zhengqi Xu; Minghui Yin; Qiwei Feng; Banghong Mo; Qiushuang Fan; Peng Ning; Taosheng Sun; Jincheng He (Ore and Energy Resource Geology, 2026)

New insights of nitrate sources and nitrogen dynamics in the ecological control zone of the northern foothills of the Qinling Mountains, China: A case study of Heihe River Basin - Lingbo Wang; Panpan Xu; Hui Qian; Jianbing Peng; Yanjun Shen; Fenghao Duan; Yibing Ning (Journal of Environmental Chemical Engineering, 2026)

Microwave pulsed vacuum drying improves drying efficiency and quality attributes of Cistanche: comparative evaluation of structural, bioactive, volatile, digestive, and metabolomic characteristics - Yixuan Wu; Yu Peng; Xiaoxuan Zhou; Ning Duan; Xueqiang Liu; Jianxiong Hao; Dandan Zhao (Food Chemistry, 2026)

Coordinated regulation of chloroplast development and SWEET-mediated translocation through miR167-ARF8B for improved fruit carbohydrate content - Zhijing Xu; Dan Qiao; Ning Wen; Chunqi Zhai; Yuanping Zhu; Bing Hua; Xiaojian Peng (Food Bioscience, 2026)

Tailored mixed-ligand defective metal-organic frameworks for highly selective and efficient uranyl capture - Xinhang Zhao; Guanbing Zhou; Peng Liu; Taohong Xu; Haiquan Zhang; Yihui Yuan; Hui Wang; Lijuan Feng; Ning Wang (Chemical Engineering Journal, 2026)

Enhancing sensor calibration and source apportionment with size-resolved optical PM measurements in urban environments - Xiaoliang Qin; Peng Wei; Yuanhui Wei; Shiyi Yang; Ya Wang; Nirmal Kumar Gali; Meisam Ahmadi Ghadikolaei; Zhi Ning (Atmospheric Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Reconstruction of satellite remote sensing AOD considering spatial gap filling and downscaling - Xu Chen; Bowen Meng; Yun Peng; Huiyi Xiao; Bin Zou; Shoutao Zhu; Ning Liu; Shenxin Li; Xin Fang (Atmospheric Environment, 2026)

Triply activated localized DNA circuit based on dual enzyme-guaranteed and analyte-stimulated strategy for robust tumor-cell-specific microRNA imaging - Yuanyuan Peng; Xiaoyu Wang; Wanling Cui; Rui Wang; Haiyan Zhao; Ning Zhang; Min Liu; Yushu Wu (Analytica Chimica Acta, 2026)

Methylome and transcriptome profiles reveal the importance of glycometabolism in thermal plasticity of large yellow croaker - Yanfei Yang; Yichen Li; Yidi Wu; Baohua Chen; Ji Zhao; Qiaozhen Ke; Weiqiang Zheng; Yun Li; Tao Zhou; Peng Xu; Ning Li (Aquaculture, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

pH-Dependent flotation mechanisms of beryl with dodecylamine: from conventional froth flotation to non-froth aggregate flotation - Jingchao Li; Yangge Zhu; Dashi Lei; Ning Sun; Xiaoliang Zhang; Xiang Li; Xiangyu Peng; Liming Wang; Zeping Feng; Jubin Zhai; Fenghua Ding; Yubin Wang (Minerals Engineering, 2026)

Data-driven multi-ion synergistic regulation for cleaner copper electrorefining: Enhancing energy and resource efficiency - Jiaqi Liao; Han Cheng; Runhua Wu; Shibing Cai; Jincheng Lu; Zhezhen Yan; Haodian Peng; Fuyuan Xu; Ning Duan (Journal of Cleaner Production, 2026)

Source apportionment of PM2.5-bound elemental carbon via stable carbon isotope analysis: A comparison study with receptor model - Cheng Wang; Yulong Yan; Xiaolin Duan; Dongmei Hu; Jiaqi Dong; Ning Jin; Hao Chen; Lin Peng (Environmental Pollution, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

A synergistic piezo-photocatalytic strategy via BaTiO3 heterophase homojunctions for MRSA-infected diabetic wound therapy - Lei Qian; Han Lin; Min Wu; Zheng Fang; Jiawei Li; Yao Han; Jinxia Zhai; Peng Yu; Cairong Xiao; Chengyun Ning (Chemical Engineering Journal, 2026)

Dual-functional nanotherapeutics: A novel approach to siRNA-mediated TNF-α silencing in inflammatory bowel disease - Li Qiao; Xue-Tian Qian; Yi-Gang Zhang; Xia-Feng Peng; Qi Liu; Shi-Qi Chang; Chang Cui; Feng Zhang; Shu-Kui Wang; Ning-Ping Huang (Chemical Engineering Journal, 2026)

Ambient PM2.5 exposure is associated with clear cell renal cell carcinoma aggressiveness and promotes tumor progression through ROS-mediated AKT/HIF-2α signaling - Xiao-Hui Wu; Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Xue-Peng Jin; Fei Lin; Qing-Shui Zheng; Yong Wei; Shao-Hao Chen; Ning Xu; Xue-Yi Xue (Chemico-Biological Interactions, 2026)

Improved soil quality underpins bacterial resistance against rainfall perturbations to mitigate maize yield loss - Yangbo Huai; Yonghua Li; Lu Yang; Peng Ning (Applied Soil Ecology, 2026)

Genetic selection response and genomic basis of resistance to Cryptocaryon irritans in large yellow croaker (Larimichthys crocea) - Yin Li; Ji Zhao; Jiaying Wang; Qiaozhen Ke; Hongshu Chi; Sijing Chen; Yujia Chen; Huasong Weng; Fei Pu; Ning Li; José M. Yáñez; Tao Zhou; et al. (Marine Life Science & Technology, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Mediation effects of thyroid hormones in the associations between essential metal elements and anxiety or depression symptoms in the elderly - Juanhua Li; Wenqi Wang; Yang Peng; Ning Qin; Jiemei Li; Ying Wei; Biwen Wang; Huaicai Zeng; Han Li; Lu Cheng (BioMetals, 2026)

Double-layered soil profile structure in an agro-pastoral ecotone revealed by geochemical characteristics: implications for wind erosion in northern North China - Jian-Yu Liu; Chun-Lei Zha; Zhi-Qiang Yin; Ling Peng; Kai-Ning Lv; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Chlor(am)ination of algal bound extracellular polymeric substances and cellular responses during raw water pre-chlorination - Qi Fu; Tian-Yang Zhang; Chao Zeng; Zheng-Xiong Zheng; Jun Shi; Zhu Peng; Zhen-Ning Luo; Huan He; Qian Xiao; Xi Wang; Bin Xu (Journal of Hazardous Materials, 2026)

Phase-transition-triggered low-temperature synthesis of core-shell Fe0@Fe2O3@Fe3C/BC composites for highly efficient PMS activation - Xiaoqian Peng; Huixin Luo; Mengjie Fan; Shuhao Guo; Mengyao Zhou; Hongying Liu; Ning Gao; Aiguo Gu; Yingwen Chen (Journal of Environmental Sciences, 2026)

Health risk of PM2.5-bound heavy metals in a megacity in South China: Comparison between before and after the outbreak of COVID-19 - Runhua Wang; Xing Peng; Kejin Tang; Yu Han; Jiangyao Tan; Ning Feng; Shaoxia Wang; Liwu Zeng; Xiaofeng Huang; Lingyan He; Sihua Lu; Min Hu (Journal of Environmental Sciences, 2026)

Internal wave behaviors in the central Andaman Sea observed by a moored buoy - Yuchen Peng; Yanliang Liu; Kuiping Li; Chunlin Ning; Liang Chen; Lina Sun; Chalermrat Sangmanee; Yue Fang (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Impact and rebound dynamics of mineral-heterogeneous rocks: From micromechanical mechanisms to energy-based modeling - Ning Hu; Sen Zhang; Bei Zhang; Quanzhong Lu; Hengxing Lan; Da Huang; Jianbing Peng (Computers and Geotechnics, 2026)

Transcriptomic Analyses Reveal Intestine and Liver Responses of Large Yellow Croaker (Larimichthys crocea) to Plant Protein Diet - Wei Liu; Peihong Huang; Qiaozhen Ke; Jiaxing Liu; Fei Pu; Peng Xu; Ning Li; Tao Zhou (Marine Biotechnology, 2026)

Integrated Analysis of Physiological, Histological, and Transcriptomic Responses to Transport Density in Schizothorax nukiangensis - Jinlin Wang; Yuting Duan; Dapeng Gu; Hejiao Li; Luo Lei; Ning Wang; Wenjia He; Yinhua Zhou; Rongrong Liao; Mei Peng; Xinyu Liu; Zhaofang Han; et al. (Marine Biotechnology, 2026)

Enhanced net carbon dioxide sink in rice-duckweed system: Evidence from the diurnal flux variation - Weixuan Liu; Ning Gao; Yawei Li; Xiaoyin Liu; Xue Zhou; Yihao Peng; Lili Zhu; Jian Meng; Junzeng Xu (Agriculture, Ecosystems & Environment, 2026)

Non-monotonic regulation of collective dynamics by group size and speed in schooling fish - Junjia Zeng; Ke Xie; Yanfei Yang; Sijing Chen; Gowena Ling Yi Goh; Yacheng Deng; Ning Li; Tao Zhou; Fei Pu; Wenjing Lu; Kuoqiu Yan; Peng Xu (Aquaculture, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Uridine diphosphate glucose reduces embryonic and diet-induced hepatic lipid accumulation in chickens - Jinhan Wang; Jiahan Liu; Ning Xiao; Huicheng Lu; Ruiying Han; Baichunzhu Tao; Zhirui Wu; Peng Yan; Xiaoli Wang; Xiaochuan Tang (Research in Veterinary Science, 2026)

Dynamic optimization of external carbon dosing in wastewater treatment using seasonally resolved heterotrophic yield coefficients - Peng Xiao; Shanshan Chen; Ning Chen; Qing Huang; Zakhar Maletskyi; Xuejun Bi; Xiaodong Wang (Process Safety and Environmental Protection, 2026)

Acceleration of Fe2+/Fe3+ cycle in core-shell MIL-88A(Fe)@1T-WS2 heterojunction to promote peroxymonosulfate activation for phenol degradation - Dachao Yan; Hongjin Chen; Ning Fu; Guanguo Zhang; Yuxiang Chen; Peng Wang; Shuai Guo; Xuechang Ren (Process Safety and Environmental Protection, 2026)

Hydrobiogeochemical impacts of water sealing on acid mine drainage in karst regions - Lei Song; Peng Liu; Chao Li; Haili Zhang; Jie Yan; Yuhui Liu; Zengping Ning; Yizhang Liu; Jing Sun; Hefa Cheng; Chengshuai Liu (Journal of Hydrology, 2026)

Symbiotic chlorine-resistant bacteria and fungi in urban building drinking water plumbing pipe biofilms - Zhen-Ning Luo; Tian-Yang Zhang; Huan He; Ren-Jie Pan; Yun-Qiao Zeng; Zhu Peng; Jun Shi; Qi Fu; Minyuan Pan; Chao Zeng; Qian Xiao; Ling Hu; et al. (Journal of Hazardous Materials, 2026)

Revealing the impact of low-temperature fermentation by Weissella cibaria MXJSHZ8-3 on soymilk quality through volatile flavor compounds and metabolite profiles - Yanhong Lin; Guandi Chen; Zhen Liu; Yilai Wan; Jingru Zhang; Hexi Yuan; Shiyang Yu; Yang Jiang; Ming Ning; Peng Yu; Zhongkai Zhou (Food Chemistry, 2026)

Identification of the functional food ingredients as novel CD38 inhibitors via pharmacophore model-based molecular docking - Xiaochun Liu; Hongju Li; Xinru Gao; Ning Hou; Chunying Du; Jiajie Li; Fengjiao Wei; Leke Qiao; Senbiao Fang; Peng Wang; Ximing Xu (Food Bioscience, 2026)

Unraveling the effects of selenium and drying on the structure–function relationship of sweet potato protein: A multiscale study - Hui Zhao; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Tao Yu; Xue-Jun Gu; You-Lin Xue (Food Hydrocolloids, 2026)

Seismic performance of T-shaped steel reinforced concrete beams with cantilever splicing in large-span high-speed railway stations - Xiao-jun Ke; Jia-hao Hong; Wan-nian Xiang; Xiu-ning Peng (Engineering Structures, 2026)

Global divergent responses of soil heterotrophic respiration to nitrogen deposition - Peng Guo; Mengyu Miao; Han Zhao; Tian Zuo; Ning Wang; Luna Yan; Zhaowei Li; Tianming Li (CATENA, 2026)

The pivotal regulatory factor circ_0006956 promotes arsenic-induced lung carcinogenesis by enhancing the Warburg effect - Deqing Li; Xiaodong Zhou; Dunyu Cai; Haotian Xu; Xingcai Chen; Shengyi Yuan; Taoran Ning; Xiangyu Dong; Mengyao Li; Qiumei Liu; Ruirui Zhang; Wenyi Peng; et al. (Chemico-Biological Interactions, 2026)

Design of AMPs Targeting BamA as a Potential Target and Research on Their Antimicrobial Mechanisms - Hongyou Chen; Xu Zou; Peiqi Peng; Mingtao Peng; Haoran Liang; Minghe Luo; Tao Wang; Ning Zhang; Qing Zhang; Yuanqiang Wang (Probiotics and Antimicrobial Proteins, 2026)

Formation process of the Ashigong ancient landslide-dammed lake in Guide Basin: impact on geomorphological evolution - Zuopeng Wang; Yezi Quan; Jianbing Peng; Mingdong Zang; Changming Lu; Ruihao Ning (Natural Hazards, 2026)

Genetic differentiation and machine learning based SNP marker development in the Cryptocaryon irritans resistant large yellow croaker (Larimichthys crocea) strain - Yin Li; Ji Zhao; Ningyuan Ding; Changliang Zhang; Ning Li; Tao Zhou; Peng Xu (Aquaculture, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Managing low C/N municipal wastewater in full-scale IFAS: Interactive effects of acetate dosing and seasonal cooling - Ning Chen; Xiaodong Wang; Shanshan Chen; Peng Xiao; Tao Ma; Xiang Li (Process Safety and Environmental Protection, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

Non-thermal plasma-catalytic methane to methanol: Unlocking synergy through tailored nickel dispersion - Danting Peng; Yufei Ji; Yanshi Zhang; Junfei Liu; Guannan Huo; Ning Ding; Haibao Huang; Daiqi Ye; Junliang Wu (Journal of Environmental Chemical Engineering, 2026)

Deciphering auxiliary-driven PFAS profiles among differential textile dyeing processes along source discharge to wastewater treatment and receiving river - Peng Lei; Meng-cheng Wu; Ning Wang; Lei-lei Lu; Guo-dong Kang; Jing-long Liu; Guan-yong Su; Hai-tian Wang; Yan-hua Liu; Sheng-hu Zhang; Ping Wu (Journal of Environmental Chemical Engineering, 2026)

Soil amendments impact hydroxyl radicals production in paddy soil: Dual roles in methane emissions - Yaling Tang; Ning Chen; Fei Peng; Yu Zeng; Juan Wang; Ziyan Yang; Yujun Wang; Guodong Fang (Journal of Environmental Management, 2026)

Long-term exposure to fine particulate matter and its constituents, genetic susceptibility, and incident bipolar disorder - Xinru Zhao; Yudiyang Ma; Ning Chen; Lei Zheng; Meiqi Xing; Feipeng Cui; Jianing Wang; Linxi Tang; Yaohua Tian; Peng Xiong; Yu Chen (Environmental Pollution, 2026)

Nanocellulose-reinforced deep eutectic solvent-based smart hydrogel sensor for adaptive window regulation and machine learning-assisted low-temperature motion monitoring - Zhenchun Li; Yucong Sun; Jiarui Shen; Rongfeng Ge; Jieli Hua; Zhiyuan Zhao; Ning Li; Yunqi Peng; Jiaqi Hou; Hong Zhang; Lei Wang (Chemical Engineering Journal, 2026)

Projected seawater inundation induced by land subsidence will weaken the coastal carbon sink effect - Zhixiong Tang; Rongrong Ning; Fubin Luo; Shilei Peng; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; De Wang (CATENA, 2026)

Investigation Into the Role of Sulfides on Arsenic Release and Immobilization in Anaerobic Groundwater: Insights from Batch Experiments - Sanxi Peng; Ning Wu; Huimei Shan; Jigang Liu; Yunquan Liu (Water, Air, & Soil Pollution, 2026)

Ecophronesis at age 10: a distinctive socio-ecological virtue with four distinct identities - Qin Du; Yuncai Wang; Zhenwei Peng; Wentao Yan; Qingji Shen; Hongyu Zhao; Xiangzhan Cheng; Ying Chen; Jiake Shen; Wei-Ning Xiang (Socio-Ecological Practice Research, 2026)

Integrating Time and Frequency Domain Features of fMRI Time Series for Alzheimer’s Disease Classification Using Graph Neural Networks - Wei Peng; Chunshan Li; Yanhan Ma; Wei Dai; Dongxiao Fu; Li Liu; Lijun Liu; Ning Yu; Jin Liu (Interdisciplinary Sciences: Computational Life Sciences, 2026)

A scheme of terrestrial system of Pakistan and the utilization and protection of its natural resources - Shaohong Wu; Keying Xin; Fenghuan Su; Lulu Liu; Ning Jiang; Peng Cui (Journal of Geographical Sciences, 2026)

Comparison of the environment, energy, and economic impacts of rice production with different mechanized straw management methods - Qingyue Cheng; Chuanhai Shu; Yuanqing Shi; Zhengbo Peng; Binbin Liu; Qiqi Chen; Ning Liu; Hongkun Xie; Xiana Tie; Song Chen; Zhonglin Wang; Yongjian Sun; et al. (Agricultural Systems, 2026)

Circ-Hipk3 in Adipose Derived Stem Cells Exosome Alleviates Myocardial Infarction Induced Myocardial Damage by Regulation miR-138-5p/Sirt1 Axis Mediated Autophagy - Guoxun Yang; Danpeng Nong; Xiao Tang; Ling Tan; Peng Yang; Haien Ning (Biochemical Genetics, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Antibacterial compounds from an endophytic fungus Cladosporium colombiae GTJ67 - Hua-Juan Yang; Yan Shu; Yan Luo; Ning Zhang; Sheng-Qi Zhang; Jia-Peng Wang; Le Cai (Natural Product Research, 2026)

Pathways to sustainability for growing coal-resource cities: evidence from the Turpan-Hami energy base - Ning Ma; Xiaojie Liu; Lin Chen; Haiyan Zhang; Peng Wang (Environment, Development and Sustainability, 2026)

Rapid evaluation of the comprehensive quality of paeonol/cyclodextrin supramolecular complexes using CASSA based on near-infrared spectroscopy combined with artificial intelligence - Bo-yao Zhang; Xin-li Li; Cheng Qian; Si-min Xue; Zhi-tong Zhang; Si-yi Liu; Guo Zhang; Guo-ping Peng; Ning Ding; Yun-feng Zheng (Molecular Diversity, 2026)

Distinct successional strategies and assembly dynamics of soil microbial community utilizing carbon derived from plant shoot versus root residues - Peng He; Jianing Wang; Xuewei Wang; Tengfei Ma; Ning Ling (Soil Biology and Biochemistry, 2026)

Volatile organic compounds from Meyerozyma guilliermondii JY19 trigger apoptosis-like cell death in Botrytis cinerea and control postharvest gray mold of ginseng berries - Guanzhong Ding; Fan Zhou; Peng Mu; Lidan Zhang; Yue Zhang; Yidong Zheng; Wenwen Jiang; Ning Liu (Postharvest Biology and Technology, 2026)

Astragaloside IV attenuates cisplatin-induced ototoxicity by preserving mitochondrial function and activating the Nrf2 signaling pathway - Tan Wang; Daquan Wu; Peng Wang; Li Gao; Zhemeng Chen; Xianhui Ning; Xinsheng Huang; Kanglun Jiang (NeuroToxicology, 2026)

Gut-muscle axis improves meat quality by regulating energy metabolism - Haoyu Liu; Lihang He; Ning Ma; Peng Tan; Qi Tang; Kun Cai; Zhaoyue Men; Yutong Lu; Dingyue Hu; Jinshan Zhao; Cunxi Nie; Shuyang Yu; et al. (Meat Science, 2026)

A comprehensive flavor evaluation method for drinking water based on flavor rating assessment (FRA) and the flavor wheel, incorporating benchmark referencing and objective weighting - You Lyu; Huan He; Zhen-Ning Luo; Tian-Yang Zhang; Xin-Li Huang; Zhu Peng; Qi Fu; Xin-Bai Jin; Bin Xu (Journal of Water Process Engineering, 2026)

Sustainable titanium-tannic acid metal-phenolic network for aqueous Vanadium(V) removal: performance, mechanism, and practical potential - Yang Hu; Qian-xin Zhang; Jin-ping Tang; Peng Liu; Yao-ning Guo (Journal of Cleaner Production, 2026)

Cost–benefit comparison of steel slag co-utilization and carbon capture, utilization and storage pathways for cement industry decarbonization: Evidence from China - Peng-Tao Wang; Fei-Yu Song; Jia-Ning Kang; Fei-Ying Wang; Song Peng; Xiaoxi Tian; Lancui Liu; Yi-Ming Wei (Journal of Cleaner Production, 2026)

Sulfur-modified Fe/Mo catalysts: Accelerated dual cycling of Mo(VI)/Mo(IV) and Fe(II)/Fe(III) and efficient H2O2 activation - Xiaoqian Peng; Zhixuan Chen; Yilin Shang; Mengfan Liu; Mengjie Fan; Ning Gao; Bei Guan; Yingwen Chen (Journal of Environmental Management, 2026)

Integrating InSAR surface deformation with sparse borehole data for three-dimensional inversion of deep-seated slip surfaces: Application to the Jungong landslide, Upper Yellow River - Ning Xi; Mingdong Zang; Zuopeng Wang; Jianbing Peng; Yiguo Xue; Junyan Zhao; Jing Wu (Engineering Geology, 2026)

Corrigendum to “Reshaping the metastatic niche with engineered uPA-hunter and VEGF-trap bifunctional nanodecoys for cancer metastasis therapy” [Chem. Eng. J. 535 (2026) 175446 (CEJ_175446)] - Peng Yang; Wenhui Chu; Yuyang Zhao; Yuanhui Xu; Fuyu Du; Meixi Jiang; Dashan Guan; Xinruo Wang; Pengbo Ning; Zhihui Chen (Chemical Engineering Journal, 2026)

Janus POM/BN-phase-change composite fabric with dynamic radiative-thermal-moisture coupling for all-day cooling-heating balance - Tuoqi Liu; Yidong Peng; Haoran Liu; Jiancheng Dong; Jiayan Long; Ning Zhang; Yanqing Gu; Shili Xiao; Tianxi Liu; Yunpeng Huang (Chemical Engineering Journal, 2026)

Reshaping the metastatic niche with engineered uPA-hunter and VEGF-trap bifunctional nanodecoys for cancer metastasis therapy - Peng Yang; Wenhui Chu; Yuyang Zhao; Yuanhui Xu; Fuyu Du; Meixi Jiang; Dashan Guan; Xinruo Wang; Pengbo Ning; Zhihui Chen (Chemical Engineering Journal, 2026)

Wine processing induced structural modification of Polygonati Rhizoma polysaccharide and their enhancement of Tc1 cell immunomodulatory activity via microbiota-mediated butyrate metabolism - Fenghe Yang; Chun Wang; Zhiqian Song; Shitao Peng; Ziqi Tian; Wenjie Lu; Tao Lin; Qiao He; Aiping Lyu; Zhangchi Ning (Carbohydrate Polymers, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

A conservation trade-off: overgrazing by reintroduced Père David’s deer threatens canopy-nesting birds in coastal engineered forests in China - Dawei Wu; Bin Liu; Guoqin Liu; Junjie Peng; Pan Chen; Ning Li; Fang Zhang (Biodiversity and Conservation, 2026)

Coordinated Vessel Arrival Time Prediction and Berth Allocation Optimization for Efficient Port Operations - Peng Fei; Wu Ning; Kecheng Li; Xiyao Xu; Xiumin Chu; Chenguang Liu (Journal of Marine Science and Engineering, 2026)
Uncertainty in vessel arrival times can substantially reduce the efficiency of berth planning in port operations. To address this issue, this study proposes a unified, data-driven, predict-then-optimize framework that explicitly links vessel arrival time (VAT) prediction with downstream continuous berth allocation optimization. In the prediction stage, heterogeneous maritime data, including port call records, AIS trajectories, and vessel physical characteristics, are integrated to construct VAT prediction models. In the optimization stage, the predicted VAT is embedded into a continuous berth allocation problem (BAP) model to support berth scheduling decisions. To better reflect real operations, a two-stage evaluation framework is further developed, in which berth plans generated from estimated arrival times (ETAs) or predicted VATs are re-evaluated under realized actual arrival times while preserving the original temporal and spatial service order. Experimental results show that the proposed framework improves VAT prediction accuracy substantially, reducing the MAE and RMSE from 4.795 h and 7.255 h for the vessel-reported ETAs to 2.844 h and 4.934 h, respectively. More importantly, the predicted-VAT-based BAP consistently outperforms the ETA-based benchmark, yielding an overall 35.96% reduction in objective value across tested scenarios. These findings demonstrate that improved VAT prediction can be effectively translated into meaningful operational gains in berth allocation.

Conjugated organic polymer enables external-sacrificial-agent-free photocatalytic uranium extraction with efficiency boosted by oxygen pre-activation - Xuefeng Tian; Jipeng Li; Xuewen Cao; Jiacheng Zhang; Rui Huang; Peng Lin; Ning Wang; Yihui Yuan (Science Bulletin, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

Phase separation of the redox sensor RCD1 mediates differential ROS signals to regulate plant growth and stress responses - Jingjing Xing; Kaiwen Li; Wenwen Duan; Zhikun Duan; Yu Zhang; Aiyu Guo; Suting Wang; Ning Ding; Yaling Zou; Xiaobin Wei; Xiaoliang Zhao; Junli Zhang; et al. (Molecular Plant, 2026)

Contrasting the roles of plastisphere and soil in shaping antibiotic resistome under flooding and co-pollution stress - Ya-Ning Wang; Xue-Peng Chen; Tian-Gui Cai; Yi-Fei Wang; Di Wu; Dong Zhu (Journal of Hazardous Materials, 2026)

Liquid fuel intrusion causes carbon canister deterioration and excess evaporative VOC emissions from in-use vehicles - Pengfei Song; Yan Liu; Qiang Chen; Jingyu Liu; Xueying Zeng; Tianlong Xing; Rui Zhang; Chongzhi Zhong; Taiyu Zhang; Ning Yang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Cl- induced reactive oxygen species synergy for deep oxidative desulfurization in deep eutectic solvents: Mechanism and process intensification via solid oxidant slow release - Ning Gao; Yike Yao; Yunbo Wang; Mengjie Fan; Xiaoqian Peng; Yingwen Chen (Journal of Environmental Chemical Engineering, 2026)

Scattering of SV waves by the canyon topography: Numerical analysis and shaking table test verification - Yu Zhang; Ning Zhang; Fei Zhang; Shuaijie Sun; Peng Zhou; Guojun Cai; Yufeng Gao (Computers and Geotechnics, 2026)

Contact-induced nearly stable electricity generation in the micro-phase separated ionogels for tactile sensing - Jiahao Fang; Xiaobo Pu; Peng Wang; Yao Chen; Hai Liu; Kedong Shang; Linjin Ye; Ning Zhang; Junjie Hao; Xiangyin Meng; Tingting Yang (Chemical Engineering Journal, 2026)

Collaboration of the symbiotic microbiome and host genome during the high altitude adaptation of chickens - Jiaming Jin; Chaoliang Wen; Junying Li; Chunning Mai; Jingwei Yuan; Ping Wang; Da Peng; Yiqiang Zhao; Congjiao Sun; Xueying Ma; Jing Feng; Ning Yang (Science China Life Sciences, 2026)

Multi-scale structure deterioration mechanisms of the cenozoic red-bed mudstone under freeze-thaw cycles in the guide Basin, Northeastern Tibetan plateau - Ruihao Ning; Zuopeng Wang; Jianbing Peng; Yiguo Xue; Mingdong Zang; Yezi Quan; Changming Lu (Bulletin of Engineering Geology and the Environment, 2026)

Increasing phosphorus availability and dynamics enhance soil organic carbon and its sub-pools sequestration as consequence of phosphorus inputs - Yao Liu; Junru Li; Ning Su; Xiangmin Rong; Yuping Zhang; Xianjun Zeng; Jianwei Peng; Gongwen Luo (Soil Ecology Letters, 2026)

Earthworms enhance nitrogen-metabolizing microbiota in drilosphere and rhizosphere co-occurrence networks - Yang Liu; Ning Wang; Wei Dai; Junwei Peng; Dandan Yao; Jinpeng Shao; Hui Wang (Applied Soil Ecology, 2026)

Bioremediation of enrofloxacin and modulation of nitrogen cycling in a simulated aquaculture system by the fungus Cladosporium cladosporioides 11 - Ning Ma; Hongyu Zhang; Lilai Yuan; Peng Lian; Wenbo Yang; Ying Huang (World Journal of Microbiology and Biotechnology, 2026)

Grain-Scale Origins of Variability in the Normal Coefficient of Restitution of Polycrystal Rocks: Numerical Insights into Velocity-Dependent Microstructural Effects - Ning Hu; Bei Zhang; Quanzhong Lu; Hengxing Lan; Jianbing Peng (Rock Mechanics and Rock Engineering, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Experimental study of soil liquefaction and wave damping during nonlinear waves and silty seabed interaction - Ning Chen; Linlong Tong; Jisheng Zhang; Hao Chen; Ji Peng; Yakun Guo (Ocean Engineering, 2026)

Valorization of phosphogypsum and silica fume in sustainable cementitious materials: Multi-objective optimization and mechanistic insights - Zilong Zhou; Haoyang Fan; Hang Li; Yanlei Chen; Sheng Zhang; Caiyue Jin; Zhongxi Jiang; Ning Liu; Liwei Peng (Journal of Environmental Management, 2026)

A molecular understanding of the potent health of wholemeal sourdough bread derived from different lactic acid bacterial fermentation - Cheng Chen; Anqi Wang; Haotian Wu; Ming Ning; Peng Yu; Ning Li; Chris Blanchard; Zhongkai Zhou; Weining Huang (Journal of Cereal Science, 2026)

SHRIMP U-Pb zircon ages and geochemistry of Jian forsterite jade from Jilin province, North-eastern China - Bijie Peng; Mingyue He; Mei Yang; Ning Wang (Journal of Asian Earth Sciences, 2026)

Conservation mulching with plastic film in maize field of arid irrigation region: Agronomic performance, economic, and environmental effects - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Xiao-Yu Lu; Ying Zhu; Meng Hao; Ning Wang; Meng-Ying Li; Xiao-Feng Zhang; Hong-Yan Tao; You-Cai Xiong (Field Crops Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Harnessing Intraspecific Dynamics in Strip-Planted Wheat: The Dual Role of Competition in Tiller Mortality and Post-Anthesis Growth - Yu Liu; Yonghua Li; Shuhui Song; Xiaojie Feng; Zhanhong Hao; Songlin Ye; Xinsheng Niu; Guohua Mi; Peng Ning (International Journal of Plant Production, 2026)

Analysis of drag force, deformation and stress distribution of biofouled flexible nets - Songchen Yu; Ning Wang; Hongde Qin; Peng Li (Aquacultural Engineering, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research on Combustion Strategies for Marine Low-Speed Two-Stroke Direct Injection Ammonia/Diesel Dual Fuel Engines - Ye-Peng Li; En-Zhe Song; Ke-Shuai Sun; Yi-Lin Ning (Journal of Marine Science and Engineering, 2026)
This study investigates the combustion and emission characteristics of a marine low-speed two-stroke engine using diesel-ignited ammonia dual direct injection. Using a validated 3D CFD model, the impact of ammonia blending ratios (Ra) was systematically explored. Results indicate that the strategy of shifting energy from early diesel injection to late ammonia injection physically repositions the combustion phasing. Rather than ammonia delaying the heat release, this late injection strategy avoids the overly early combustion observed at low ammonia concentrations, thereby lowering peak in-cylinder temperatures while maintaining robust work extraction. Consequently, indicated power at the N90 condition increases by 3.5% (to 1689 kW) over the diesel baseline, with a minimum EISFC of 165.5 g/kWh. High-ratio ammonia blending achieves deep decarbonization: at N90, peak CO and soot emissions are reduced by over 90% and 95%, respectively. Additionally, NOx emissions decrease by approximately 70% at N90 compared to the N20 peak, attributed to the thermal DeNOx mechanism. However, the low-temperature environment introduces trade-offs, leading to increased ammonia slip (4 ppm at N90) and elevated N2O emissions (peaking at N70). These findings clarify the mechanisms governing ammonia combustion and provide theoretical support for optimizing zero-carbon marine propulsion systems.

Genomic safety assessment and metabolic modulation by Enterococcus faecium 140,623, a probiotic strain from lactasin tablets: implications for obesity management - Yongqi Gan; Cheng Liu; Xiaorui Zheng; Jun Nong; Lanyan Fan; Peng Xie; Yang Li; Bin Zhu; Ling Ning; Zan Zhang (World Journal of Microbiology and Biotechnology, 2026)

Integrating geometric morphometrics and GWAS to reveal the genetic basis of body shape variation in large yellow croaker (Larimichthys crocea) - Wei Liu; Yuhang Wang; Miaosheng Feng; Jiaying Wang; Junjia Zeng; Yacheng Deng; Fei Pu; Ning Li; Peng Xu (Aquaculture, 2026)

Research on a vision navigation system for rice transplanters based on machine vision fused with GNSS - Zhaopeng Liu; Xulong Wu; Weiwei Gao; Fengpeng Ning; Wenyu Zhang; Jie He; Muhua Liu; Xiongfei Chen; Peng Fang (Biosystems Engineering, 2026)

Physics-informed deep learning for groundwater contamination sources identification under sparse monitoring - Liming Zhang; Jiawen Liu; Danbing Mei; Xiongbiao Qiao; Zhaoqian Xie; Ning Sun; Zhenyu Ding; Zongwen Zhang; Xiaohong Peng (Journal of Hydrology, 2026)

Human–water adaptation in drylands: Reconciling water use and ecological security in arid inland river basins of China - Cheng-peng Lu; Qi Feng; Xiang-long Gao; Wen Liu; Ting-ting Ning (Journal of Cleaner Production, 2026)

Molecular weight-dependent binding heterogeneity of heavy metals with dissolved organic matter in plateau waters: Insights from EEM-PARAFAC and moving-window - Keli Yang; Mengli Huang; Huacheng Xu; Xin Liu; Tianyuan Chen; Ning Li; Laodong Guo; Jiaoyu Peng; Yaoling Zhang (Journal of Environmental Chemical Engineering, 2026)

A simple controlled assembly strategy for multi-coordinated Ti derived in non-calcinated amorphous Ti-Si mixed gel: strengthened deep catalytic oxidative desulfurization - Ning Gao; Baolong Liu; Mengjie Fan; Yike Yao; Yunbo Wang; Xiaoqian Peng; Xupeng Zong; Fuyuan Xu; Yingwen Chen (Fuel, 2026)

RNA-mediated alternative splicing and polyadenylation shape immune responses underlying disease resistance to Pseudomonas plecoglossicida in Larimichthys crocea - Yin Li; Yujia Chen; Yulin Bai; Longyu Chen; Sijing Chen; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Crosslinked polymer aerogel with multiple binding sites for efficient uranium separation from uranium-containing wastewater - Yaping Jian; Jiacheng Zhang; Xuewen Cao; Jipeng Li; Qin Peng; Xuefeng Tian; Jianfei Du; Yihui Yuan; Ning Wang (Environmental Research, 2026)

From vegetation classification to vegetation zonation: a multi-source modelling framework for evergreen broad-leaved forests in complex terrain - Shiqi Zhang; Peihao Peng; Ning Li; Juan Wang; Xuefeng Peng; Zhaozhi Luo (Environmental Modelling & Software, 2026)

From mineral dissolution to slope failure: wet-dry cycling driven multiscale degradation of Cenozoic red-bed mudstone, NE Tibetan Plateau - Yezi Quan; Zuopeng Wang; Jianbing Peng; Yiguo Xue; Mingdong Zang; Yan Lv; Ruihao Ning; Changming Lu; Chao Xue (Engineering Geology, 2026)

Topology optimization and vibration isolation analysis of periodic pile barriers for full-mode waves - Peng Zhou; Ning Zhang; Yu Zhang; Ming Feng; Shui Wan; Guojun Cai (Computers and Geotechnics, 2026)

Dual functions of pyrite modified polyethylene carrier in Anammox biofilm: Promoting biofilm growth and enhancing nitrogen removal - Tingting Liu; Dongyue Li; Peng Gao; Yuhan Zhu; Linzhu Du; Xingrong Yao; Wanqi Liu; Kailun Yang; Xingxing Xiong; Ning An; Jiarui Li; Qian Zhao; et al. (Chemical Engineering Journal, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

An all-in-one programmable Janus membrane with gemini AIE surfactant for integrated bioaerosol management - Saisai Yan; Xiyao Wang; Zishu Wen; Yufeng Guan; Bixiao Cao; Xuanzhe Wang; Ning Du; Yingjie Zhong; Ningning He; Shangyong Li; Peng Sun (Chemical Engineering Journal, 2026)

Innovative utilization of waste printed circuit boards and coal gangue/ash for multifunctional glass-ceramics: structure-property insights via data-driven analysis - Yingwen Zhang; Lei Gao; Li Chao; Bang Yao; Dekai Fan; Chen Chen; Rong Xiao; Yingrui Ning; Peng Zhu; Urooj gul sandilo; Abeanezer Lukas Bassa; Nasarul Wahab; et al. (Chemical Engineering Journal, 2026)

An anisotropic multi-amine-mediated dynamic network for strong, tough, and self-strengthening conductive hydrogel - Qingye Liu; Xiaohui Wang; Wenbo Xu; Xuan Ning; Yu Yang; Peng Li; Yanling Hu; Xiaojun Li; Qingqing Li (Chemical Engineering Journal, 2026)

Nanocarrier-mediated RNAi targeting glutamate decarboxylase synergizes with neonicotinoids for aphid control - Chenxi Liu; Xinyuan Ning; Peng Zhao; Zihan Wei; Yuqing Xie; Lin Zhu; Zhen Li; Xiaoxia Liu (Chemical Engineering Journal, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

Unraveling shallow landslides in the Qinling Mountains: Novel insights into vegetation-hydrology driven mechanisms - Xing Chen; Yanjun Shen; Yibing Ning; Bailei Shi; Jinyu Zhu; Sirui Li; Zijian Li; You Lyu; Jianbing Peng (Journal of Mountain Science, 2026)

Estimation and simulation on carbon sinks potential of marine aquaculture in China - Peng Li; Xinhao Wu; Dezhi Ning; Yichuan Zhang; Mengru Jiang; Siyi Li; Nan Ma; Jianke Guo (Journal of Geographical Sciences, 2026)

Multi-parameter GNSS monitoring for expansive soil hazards: a case study from coastal Texas - Xiongchuan Chen; Shuangcheng Zhang; Yong Fang; Qingtao Zhang; Lidu Zhao; Peng An; Ning Liu; Qi Liu; Ningkang An; Jun Li; Zhilei Ye (Advances in Space Research, 2026)

A novel peptide oyster-derived antimicrobial peptide against clinical carbapenem-resistant Acinetobacter baumannii - Rui Hou; Yihua Cai; Shida Xu; Dandan Ma; Ning Su; Shanshan Wang; Hongmei Mo; Mian Peng (Frontiers in Marine Science, 2026)
Background The escalating prevalence of multidrug-resistant pathogens, specifically carbapenem-resistant Acinetobacter baumannii (CR-AB), underscores the urgent need for novel antimicrobial strategies. Antimicrobial peptides (AMPs) offer a viable alternative to conventional antibiotics. Methods We discovered a novel AMP, designated OAMP, from oyster hemolymph and evaluated its antimicrobial efficacy against a spectrum of pathogens, including five clinical CR-AB strains. The synergistic potential of OAMP with meropenem, tigecycline, and colistin was assessed via checkerboard assays. Safety profiles were determined through cytotoxicity and hemolysis assays. Results OAMP exhibited potent broad-spectrum activity, effectively inhibiting CR-AB strains with MIC values of 4–8 µM. In combination therapies, OAMP demonstrated additive to synergistic effects with conventional antibiotics, facilitating a reduction in antibiotic dosage. However, safety assessments revealed cytotoxicity and hemolytic activity at MIC levels, indicating a narrow therapeutic window. Conclusions OAMP shows significant promise as a potent antibacterial agent and an effective adjuvant for combinatorial therapy against CR-AB. Future studies should focus on structural optimization to mitigate toxicity and enhance stability for clinical application.

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Nitrogen fertilization simultaneously strengthens soil carbon and nitrogen pools, with implications for productivity gain of double-cropping rice system - Junru Li; Yao Liu; Hao Huang; Ning Su; Qiulong Hu; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Biology and Fertility of Soils, 2026)

Co-reduction of nitrogen and phosphorus fertilizer inputs reduced nutrient losses and maintained crop yield in a rice-oilseed rape rotation system - Haodong Zhang; Ning Su; Gongwen Luo; Zhi Peng; Xizhe Luo; Sihai Qin; Mengjiao Huang; Chang Tian; Xiangmin Rong; Guixian Xie; Jun Xie (Soil and Tillage Research, 2026)

Microbial mechanisms underlying differences of methane emissions between urban and rural wetlands - Yuwen Lin; Xinyu Yi; Chen Ning; Yong Li; Yinghe Peng; Shuguang Liu; Changhui Peng; Xiaoyong Chen; Shuailong Feng; Pengpeng Duan; Yan Liu; Juyang Liao (Soil Biology and Biochemistry, 2026)

Analysis of nitrogen removal performance of gel-immobilized cold-acclimated Anammox granules under low temperature and high nitrogen loading rate (NLR) conditions - Linhua Zhang; Jing Zhang; Jun Li; Peng Gao; Jianwei Chen; Dongyue Li; Xingxing Xiong; Sairui Guan; Ning An; Kailun Yang; Tingting Liu; Xingrong Yao; et al. (Process Safety and Environmental Protection, 2026)

Mechanisms of cavitation erosion risk enhancement by vortex generators at lower Reynolds numbers - Ning Qiu; Haitao Rao; Doubin Xun; Han Zhu; Baowei Shan; Bangxiang Che; Peng Wu (Ocean Engineering, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Programmable oil/water separation performance of wood-based membranes via structural anisotropy and delignification - Kaiwen Chen; Cheng Hao; Luyao Chen; Fengze Sun; Yujing Tan; Wenjuan Zhao; Hui Peng; Tianyi Zhan; Jianxiong Lyu; Ning Yan (Journal of Cleaner Production, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Laboratory-scale characteristics of micro-slip during fault quiescence and implications for injection-induced reactivation stability - Ning Yang; Peng-Zhi Pan; Shuting Miao; Wenbo Hou (International Journal of Rock Mechanics and Mining Sciences, 2026)

Two-stage oxidation phenomenon of n-propylbenzene at elevated pressure - Xiang Gao; Du Wang; Xu-Peng Yu; Qian-Peng Wang; Ya-Ning Zhang; Zhen-Yu Tian (Fuel, 2026)

Comprehensive investigation of the IKKα gene and TBK1 gene's identification, molecular evolution, and expression profiling in lampreys - Boting Lan; Xinyu Du; Ning Yang; Si Gao; Tiesong Li; Peng Su (Fish & Shellfish Immunology, 2026)

Selective control in the oxygen activation involved ROS generation over carbon nitride for long-term aerosol disinfection: Carbonyl location matters - Hanyu Zhang; Long Tan; Guochun Lv; Yaofang Fan; Munir Ahmad; Xiaojing Wang; Kai Wei; Hong Xiao; Hong Peng; Xiaohui Lu; Shihuai Deng; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Hydrodynamic performance of nested dual-chamber OWC breakwaters for enhanced power stability and wave attenuation - Chen Peng; Dezhi Ning; Feng Zhou (Coastal Engineering, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Comparative Machine Learning Algorithms for Dynamic Vegetation Cover Retrieval in Desert Oasis from UAV Time-Series Data - Ning Wang; Fuxin Jin; Chaoyong Peng; Peng Wang; Yuchuan Guo; Ce Yu (Journal of the Indian Society of Remote Sensing, 2026)

Characteristics and mechanism of high-vegetation-coverage recurrent debris flow disaster chain: Insights from a case in the Qinling Mountains, China on July 19, 2024 - Jinyu Zhu; Yanjun Shen; Yibing Ning; Jianbing Peng; Xing Chen; Bailei Shi; Shengwei Zhang (Bulletin of Engineering Geology and the Environment, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Monitoring and determinants analysis of canopy layer urban heat island in China based on both air temperature and apparent temperature - Yuanzheng Li; Chaoqun Ma; Tengbo Yang; Zhifeng Wu; Rui Yao; Guosong Zhao; Xiaojv Ning; Peng Kang (Urban Climate, 2025)

Innovative Co-doped MXene and aerogel catalysts for rapid and efficient degradation of carbamazepine via PMS activation - Yuwei Wu; Guohe Huang; Kai Zhao; Jianan Yin; Peng Zhang; Ning Chen; Renfei Feng (Journal of Environmental Chemical Engineering, 2025)

Tunable selectivity of gas sensors based on ZIFs@graphene oxide at room temperature - Keng Xu; Yong Yang; Yaohui Qu; Cailei Yuan; Zhipeng Wang; Ning Peng (Journal of Environmental Chemical Engineering, 2025)

Bioinspired Nacre-layer composite loose nanofiltration membranes: Preparation and performance evaluation - Junpeng Mao; Peng Liu; Ning Tang; Hui Li; Yaxin Gu; Yunwu Yu; Yunxue Liu; Lihua Wang; Ji Cao (Journal of Environmental Chemical Engineering, 2025)

Spatio-temporal heterogeneity of quality attributes and flavors in grass carp (Ctenopharyngodon idella) cubes during deep frying: Key metabolic evidence - Hao Wang; Ning Cui; Bin Peng; Chengwei Yu; Bizhen Zhong; Mingming Hu; Jinlin Li; Zongcai Tu (Food Chemistry, 2025)

Biofilm with a mechanically strengthened character via enhanced cross-links of soybean proteins with short-chain fatty acid-modified starch - Sheng Ke; Gaoheng Li; Anqi Wang; Haotian Wu; Peng Yu; Ming Ning; Padraig Strappe; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2025)

Cellulose-based triboelectric nanogenerator with efficient filtering performance for medical protection filtration equipment - Peng Du; Yongjian Xu; Meng Zhu; Jian Wang; Lulu Ning; Yuheng Zhang (Chemical Engineering Journal, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Theranostic nanoplatform for triple-negative breast cancer therapy: Autophagy suppression-coordinated siRNA delivery triggers apoptosis, ferroptosis, and pyroptosis via photothermal activation - Guobao Ning; Lishen Yang; Bilian Li; Jianghua Lin; Shufen Li; Fengqi Zhou; Han Chen; Xingye Zheng; Weijie Sun; Hui Zhao; Can-Peng Li (Chemical Engineering Journal, 2025)

Long-term carbon release of peatland soil after permafrost thaw in northmost China - Yunjiang Zuo; Yanyu Song; Lei Jiang; Yue Li; Yongsi Wang; Ning Chen; Peng Jiang; Sijia Zheng; Changchun Song; Xiaofeng Xu; Fenghui Yuan; Li Sun (CATENA, 2025)

Research progress on chemical composition, pharmacological activity and clinical application of Panax japonicus - Ye Huang; Wen-yue Ning; Cai-e Wang; Peng-cheng Lin; Min Wang; Xian-hua Meng (Natural Product Research, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

LETM2 regulates mitochondrial function and autophagy in diabetic foot ulcers: implications for oxidative stress and therapeutic targeting - Nan Su; Jiwei Wang; Zhiwei Xue; Shujie Peng; Wenchen Xing; Haoyong Jin; Jiangli Zhao; Yanya He; Jiaqi Shi; Wenbo Li; Qijian Wei; Bin Huang; et al. (Functional & Integrative Genomics, 2025)

A CSDG photoelectronic transistor based on simulation model mimicking dopamine-facilitated synaptic plasticity for high energy-efficient neuromorphic system - Qing-an Ding; Yuhua Gao; Chunyan Liu; Chaoran Gu; Xiaoyuan Li; Fangfang Ning; Binghui Hou; Yandong Peng; Bing Chen (Cognitive Neurodynamics, 2025)

Molecular evolution of the transcription factor PRDM genes and expression profiles in response to stimulations and spinal cord injury repair in lamprey (Lethenteron reissneri) - Jinyang Guo; Xinyu Du; Jiaqi Wu; Boting Lan; Ning Yang; Peng Su (Immunogenetics, 2025)

Drought in May inhibited conifer growth more seriously with climate warming in the southeastern Tibetan Plateau - Kun Xu; Jingxuan Wei; Yuandong Zhang; Ning Miao; Zhongtong Peng; Shirong Liu (Agricultural and Forest Meteorology, 2025)

Control of post-harvest soft rot (Rhizopus stolonifer) on sweet cherry using volatile organic compounds produced by Bacillus velezensis Q-84 - Jian-Yu Wang; Min-Xin Mao; Chun-Yan Xu; Man Zou; Wen-Ting Bao; Yi-Ning Zhou; Shun-Qing Hu; Ke-Xin Jiao; Qing-Kun Lu; Peng Zhao; Kun-Peng Zhang; Yi-Lun Chen; et al. (BioControl, 2025)

Probiotic characteristics and protective effects of chicken-derived Enterococcus faecium against infection with Avian Pathogenic Escherichia coli and Salmonella in laying hens - Yanan Cui; Kangping Liu; Peng Chen; Pengxin Jiang; Xutao Wang; Ning Chen; Jiamei Cui; Zijuan Hou; Puyu Liu; Jianguo Li; Shishan Dong; Qian Li; et al. (Veterinary Microbiology, 2025)

A novel mycotoxin-degrading enzyme complex can biodegrade AFB1, DON, and ZEN co-contamination in both in vitro and in vivo experiments - Yan-Qi Ning; Zhe Peng; Yu Zhang; Alainaa Refaie; Jing-Hui Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun (Toxicon, 2025)

An incoherent feed-forward loop coordinates nitrate uptake and tillering in wheat - Weiya Xu; Yongming Chen; Yanxiao Niu; Bin Liu; Dejie Du; Xining Ning; Tong Huan; Yilan Zhou; Wensheng Ke; Lingfeng Miao; Weilong Guo; Mingming Xin; et al. (Molecular Plant, 2025)

A MAP (Monitoring–Assessment–Priority) framework for amine degradation products in carbon capture - Peng Chen; Xiao Li; Ningtong Yi; Xining (Ning) Wang; Shengtao Ma; Yali Yang; Xian Zhou; Yongqiang Ren; Shisen Xu; Xinghua Li (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Isolation, genomic characterization and biocontrol potential of the lytic Pectobacterium phage Pcc_P10 against soft rot of pepper fruits - Mengtian Jiang; Jinghan Zhang; Cengceng Huang; Zhuangzhuang Gao; Siyue Chen; Ping Zeng; Ning Dong; Xiaoxiao Sun; Wentao Chen; Xiaoxiao Liang; Peng Lu; Lanhua Yi; et al. (International Journal of Food Microbiology, 2025)

Implementation of three-dimensional numerical manifold method for initiation and propagation simulation of brittle materials - Ge Kang; Liu chen Shu; Qiu meng Ouyang; Zheng Yang; You-jun Ning; Peng-wan Chen (International Journal of Rock Mechanics and Mining Sciences, 2025)

Facile fabrication of highly efficient Cu/CNT catalysts by ALD technique for methanol oxidative carbonylation - Lulu Peng; Shipin Wu; Ning Zhang; Jun Ren (Fuel, 2025)

Spatio-temporal prevalence and distribution of Salmonella spp. serovars in animal-origin foods in China: A comprehensive outlook derived from nine years of national surveillance, 2014—2022 - Ying Li; Lisha Liu; Li Bai; Zhaoping Liu; Ning Li; Weijun Kang; Dajin Yang; Zixin Peng; Lingmei Niu (Food Research International, 2025)

Investigation of the matrix effects on structural stability and application performance of aptamers: Insights from tetrodotoxin detection in typical seafood - Yu Li; Shuo Qi; Peifang Chen; Mingwei Qin; Ning Ding; Chifang Peng; Zhouping Wang (Food Chemistry, 2025)

In situ growth of N-doped carbon nanotubes encapsulated nZVI as nanoconfinement catalyst for mitigating the hurdles of ferric cations leaching and low oxidant utilization in Fenton-like catalysis - Youxue Deng; Xiangyu Wang; Ping Ning; Iseult Lynch; Zhiling Guo; Peng Zhang; Lisi Wu (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Cyclic Wetting–Drying Driven Geological Gene Changes and Multi-scale Degradation Mechanisms of the Neogene Red-Bed Sandstone in the Guide Basin, NE Tibetan Plateau - Yezi Quan; Zuopeng Wang; Jianbing Peng; Yiguo Xue; Mingdong Zang; Changming Lu; Ruihao Ning (Rock Mechanics and Rock Engineering, 2025)

The Impact of Petrographic Characteristics on Granite Strength: Insights from an Interpretable Machine Learning Model - Kaiwei Tian; Zeqi Zhu; Qian Sheng; Ning Tian; Peng Wu; Ningxi Zhou (Rock Mechanics and Rock Engineering, 2025)

Grassland shrub encroachment generates divergent contributions of plant- and microbial-derived carbon to soil organic carbon - Xuewei Wang; Pengfei Zhang; Yuntao Zhang; Jianing Wang; Peng He; Lina Zheng; Ning Ling; Zhaoming Wang (Plant and Soil, 2025)

Formation mechanism and evolution characteristics of the loess–mudstone interface landslide in Yan’an, China - Penghui Ma; Qixian Jiao; Yalin Nan; Chuanzhi Zhang; Zekun Li; Luqing Zhao; Lisen Chen; Ning Han; Jianbing Peng (Bulletin of Engineering Geology and the Environment, 2025)

Minimum Hydrogen Consumption Energy Management for Hybrid Fuel Cell Ships Using Improved Weighted Antlion Optimization - Peng Zhou; Wenfei Ning; Peiwu Ming; Zhaoting Liu; Xi Wang; Zhengwei Zhao; Zhaoying Yan; Wenjiao Yang; Baozhu Jia; Yuanyuan Xu (Journal of Marine Science and Engineering, 2025)
Energy management in hybrid fuel cell ship systems faces the dual challenges of optimizing hydrogen consumption and ensuring power quality. This study proposes an Improved Weighted Antlion Optimization (IW-ALO) algorithm for multi-objective problems. The method incorporates a dynamic weight adjustment mechanism and an elite-guided strategy, which significantly enhance global search capability and convergence performance. By integrating IW-ALO with the Equivalent Consumption Minimization Strategy (ECMS), an improved weighted ECMS (IW-ECMS) is developed, enabling real-time optimization of the equivalence factor and ensuring efficient energy sharing between the fuel cell and the lithium-ion battery. To validate the proposed strategy, a system simulation model is established in Matlab/Simulink 2017b. Compared with the rule-based state machine control and optimization-based ECMS methods over a representative 300 s ferry operating cycle, the IW-ECMS achieves a hydrogen consumption reduction of 43.4% and 42.6%, respectively, corresponding to a minimum total usage of 166.6 g under the specified load profile, while maintaining real-time system responsiveness. These reductions reflect the scenario tested, characterized by frequent load variations. Nonetheless, the results highlight the potential of IW-ECMS to enhance the economic performance of ship power systems and offer a novel approach for multi-objective cooperative optimization in complex energy systems.

Resveratrol improves boar semen quality in summer months through modulation of the AGEs-RAGE signaling pathway in Leydig cells - Zhiyun Peng; Zereng Chen; Xiaofang Lu; Li Zhang; Ning Gao; Bo Weng; Tuo Xu; Heng Bao; Maoliang Ran (Journal of Thermal Biology, 2025)

Genotype-dependent fortification of rice nodes dictates cadmium fate in grains: A synergistic barrier forged from cell wall and amino acid chelation - Weijian Wu; Qiao Ma; Linhan Chen; Jing Peng; Ning Xie; Feiyu Zheng; Xiaoyu Tan; Yang Yang; Si Luo; Qingru Zeng; Xiao Deng (Journal of Hazardous Materials, 2025)

Electrochemical membrane bioreactors for wastewater treatment: Mechanisms of membrane fouling control and applications to refractory pollutants - Shuli Liu; Yatong Gao; Xiaohong Han; Jiajun Hua; Yuhong Zhang; Glen T. Daigger; Qi Li; Ning Guo; Xiao Mi; Jia Kang; Peng Zhang (Journal of Environmental Chemical Engineering, 2025)

The splash process in aeolian transport: Phenomena, mechanisms, regulations, advances and prospects - Peng Wang; Jialin Zhu; Jie Zhang; Ning Huang (Geomorphology, 2025)

Evolution of loess gullies and geohazard chains in the Dongzhi tableland, China - Penghui Ma; Ning Han; Qiangbing Huang; Yanbo Cao; Zekun Li; Lisen Chen; Qixian Jiao; Jianbing Peng (Geomorphology, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Unveiling the intrinsic electrochemical properties and stability of phase-pure A5B19 La–Mg–Ni-based superlattice allotropes - Kuiyue Wang; Anyi Zhang; Ning Zhang; Wenfeng Wang; Shumin Han; Qiuming Peng; Yuan Li; Lu Zhang (Chemical Engineering Journal, 2025)

Interfacial fluid manipulated strategies: Flexible polyaniline film with artificial microstructure for multifunctional sensing of physical and chemical stimuli - Shuhuan Deng; Yukang Peng; Jingjie Zhou; Jiajie Huang; Zhongtao Qin; Yangguang Ran; Ningjing Wang; Enchong Ning; Lilin Shen; Yulin Hu; Wenbo Chen; Qinping Qiang; et al. (Chemical Engineering Journal, 2025)

Polymer bidirectional induction for ultrathin ZIF-8 membrane with chemisorption site towards in-situ enhanced H2/CO2 separation - Peng Li; Chao Ma; Ning Li; Chi Tang; Zhaolin Lv; Zhenjie Gu; Zhihua Qiao; Chongli Zhong (Chemical Engineering Journal, 2025)

Numerical and experimental investigation on ‘C-pile’ breakwaters for wave attenuation - Chen Peng; Dezhi Ning; Lifen Chen; Jin Xu; Hao Cao (Coastal Engineering, 2025)

Phosphate-mediated pseudo-selectivity in calcification control: Substrate-derived alkalinity outweighs kinetic modulation in anaerobic granular sludge - Hua Lian; Jie-De Luo; Qing-Liu Luo; Ji-Qi Pan; Ling Peng; Guang-Ning Liu; Long-Hui Zhan; Shuang-Fei Wang; Jian Zhang (Bioresource Technology, 2025)

Poly-γ-glutamic acid could enhance the salt resistance of maize by collectively increasing the osmotic, ion, and oxidative stresses resistance and enriching the salt-tolerant PGPBs in rhizosphere soil - Haizhen Ma; Ning Xiao; Yifan Liu; Jiang Liu; Peng Li; Xinru Deng; Jia Wei; Panpan Li; Tao Xia (Plant and Soil, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

YOLO-feed: An advanced lightweight network enabling real-time, high-precision detection of feed pellets on CPU devices and its applications in quantifying individual fish feed intake - Miaosheng Feng; Pengxin Jiang; Yuhang Wang; Shuimu Hu; Sijing Chen; Rui Li; Haibin Huang; Ning Li; Boyu Zhang; Qiaozhen Ke; Yu Zhang; Peng Xu (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Heave motion estimation based on the Cubature Kalman Filter combined with Fast Fourier Transform of acceleration autocorrelation - Daoxi Li; Shuqing Wang; Donghong Ning; Jiajing Peng (Ocean Engineering, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

The effect of inclined plate motion on the classification efficiency of quartz sand in the Reflux Classifier - Zhiyuan Zhang; Dongjiao Gui; Peng Chen; Yifei Li; Ning Han; Yanfeng Li (Minerals Engineering, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

A literature review of direct air capture technology from a socioeconomic perspective - Yi-Ming Wei; Song Peng; Jia-Ning Kang; Lan-Cui Liu; Yunlong Zhang; Helei Liu; Tong Wu (International Journal of Greenhouse Gas Control, 2025)

Selenium-enriched lactic acid bacteria inoculation enhances the quality of Paocai by imparting the microbiome and metabolome - Mingye Peng; Qin Li; Binbin Long; Bo Li; Zhicong Shen; Ning Xu; Yong Hu; Chao Wang; Yang Chen; Mengzhou Zhou (Food Chemistry, 2025)

Molecular mechanism by which luteolin inhibits toll-like receptor 4 activation: Multi-spectroscopic analysis and molecular simulation - Siting Wei; Youdan Ning; Deming Gong; Peng Zhang; Guowen Zhang; Xing Hu (Food Bioscience, 2025)

A C1q domain-containing protein from Scapharca subcrenata may participate in the immune defense against pathogen infection - Jing Yang; Qiang Peng; Min Shen; Guilong Liu; Xin Xu; Chunde Wang; Junhao Ning (Fish & Shellfish Immunology, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Reactive species-mediated biodegradability improvement of biogas slurry in a Fenton-like system - Xianglin Chang; Haoxi Dai; Lan Liang; Wenchao Peng; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Ning Li (Chemical Engineering Journal, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

MTGGF: A Metabolism Type-Aware Graph Generative Model for Molecular Metabolite Prediction - Peng-Cheng Zhao; Xue-Xin Wei; Qiong Wang; Hao-Yang Wang; Bing-Xue Du; Jia-Ning Li; Bei Zhu; Hui Yu; Jian-Yu Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Genomic Approaches to Enhance Disease Resistance in Large Yellow Croaker: Recent Progress and Future Perspectives - Zhou Jiang; Yulin Bai; Ning Li; Lin Chen; Ji Zhao; Yin Li; Tao Zhou; Peng Xu (Reviews in Aquaculture, 2025)
Large yellow croaker is an important marine aquaculture species in China, but frequent disease outbreaks have led to significant losses in the aquaculture industry. Although traditional genetic selection methods have long been applied in fish breeding, an increasing number of studies are introducing genomic selection methods into large yellow croaker breeding to target complex traits such as disease resistance. Recent advancements in genomic resources, including an updated reference genome and SNP array, have opened up new opportunities for genetic and evolutionary research on this species. This review provides an overview of the current status of the large yellow croaker aquaculture industry and the existing approaches to addressing disease challenges. It also summarizes genomic selection techniques, the genetic mechanisms underlying disease resistance traits, and potential improvements in genomic selection methods. Furthermore, we summarize future directions for large yellow croaker breeding, incorporating the application of genetic research, multi‐dimensional data integration, standardized testing protocols, and artificial intelligence for phenotypic measurement. These strategies have opened new pathways to enhance disease resistance in large yellow croaker and to promote the sustainable development of its aquaculture industry.

Expression of leptin and its long-form receptor in the porcine corpus luteum during pregnancy and the protective role of leptin in corpus luteum function in vitro - Wenlong Zhang; Jiang Peng; Ning Wang; Zulian Shi; Jiaman Wu; Dewen Tong (Theriogenology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

Long-range electron transfer pathways at FeCu bimetallic interfaces: Bridging catalytic mechanisms and scalable applications for persistent pollutant degradation - Xiaoyin You; Chaohai Wang; Chuqiao Wang; Xing Xu; Yuying Hu; Ning Li; Fengping Hu; Wen Liu; Xiaoming Peng (Journal of Hazardous Materials, 2025)

Construction of biomass-derived magnetic-recyclable FeNi-LDO@CS to activate persulfate for simultaneous degradation of cationic and anionic dyes: Discrepancy, mechanism and toxicity analysis - Fengjie Liang; Jiali Cui; Chaoneng Ning; Peng Xiangli; Feng Zhang; Yi Liang; Jingyi Gao (Journal of Environmental Sciences, 2025)

Effects of the southwest vortex on the vertical structure of ozone in the Sichuan Basin in China - Huiqiong Ning; Hong Wang; Ping Kang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Wei Liu; Ping Wang; Huizheng Che (Atmospheric Pollution Research, 2025)

Single-cell sequencing and spatial transcriptomics reveal FAS+ T cell and autophagy-related signatures predicting chemoimmunotherapy response in diffuse large B-cell lymphoma patients - Ning Lou; Liyuan Dai; Ruyun Gao; Jianliang Yang; Lin Gui; Sheng Yang; Peng Liu; Yuankai Shi; Xiaohong Han (Science China Life Sciences, 2025)

Detecting Deleterious Recessive Variants in Large Yellow Croaker Using Data from 7337 Individuals - Zhou Jiang; Ji Zhao; Ning Li; Jiaying Wang; Fei Pu; Hongshu Chi; Peng Xu; Tao Zhou (Marine Biotechnology, 2025)

Neonicotinoid pesticides: residue detection and dietary risk assessment in commercially available plant-based agricultural products in North China - Peng Sun; Danqi Ren; Guotao Ding; Ning Hao; Ge Shi; Weihao Li (Environmental Monitoring and Assessment, 2025)

Two new megastigmane glycosides from the leaves of Nicotiana tabacum and their anti-inflammatory activities - Peng-fei Yang; Wei Wu; Hang-hang Han; Qing-fu Wang; Lei Li; Ze-ning Wang; Duo-bin Mao; Zhi-fei Chen (Natural Product Research, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Understanding cross-market strategic behaviors of prosumers: An equilibrium-driven evolutionary game approach - Kai Kang; Yifan Su; Peng Yang; Zhaojian Wang; Yunfan Zhang; Ning Qi; Feng Liu (Journal of Cleaner Production, 2025)

Emerging MXene-based catalysts for advanced oxidation processes - Yanlei Zhu; Ning Li; Rui Wang; Longfei Zhang; Yong Liu; Wenchao Peng; Jiapeng Liu (Fuel, 2025)

Tiller growth and mortality in winter wheat as affected by carbon and nitrogen partitioning via stem internode structure - Xiaojie Feng; Lu Yang; Suoqian Kang; Yangbo Huai; Yuanwei Gan; Shuhui Song; Yonghua Li; Peng Ning (Field Crops Research, 2025)

Cascade-responsive nanoplatform for synergistic cancer therapy via ROS amplification and hypoxia targeting - Chunyun Xu; Yanfang Ding; Jingjing Qi; Peng Chu; Hongjie Huo; Zhuang Wang; Qingxuan Han; Yuan Liang; Ning Yang; Youwei Xu; Ligeng Xu; Lixue Chen; et al. (Chemical Engineering Journal, 2025)

Mxene quantum dot insertion-induced electron transfer in CoFe LDH for high-performance zinc-air batteries - Qing Sun; Kailin Li; Tie Shu; Ziyang Guo; Yongfei Li; Yuxin Zhang; Liang Li; Jiaoyi Ning; Peng Zhao; Ke Xin Yao (Chemical Engineering Journal, 2025)

The failure modes and evolution process of loess landslide dams via flume tests - Zekun Li; Penghui Ma; Ning Han; Qixian Jiao; Lisen Chen; Lin Ran; Zhijie Jia; Luqing Zhao; Jingjing Nan; Jianbing Peng (Landslides, 2025)

Interpretable machine learning approach for predicting lunar soil shear strength parameters based on data imputation techniques - Peng Wu; Jian Chen; Juehao Huang; Kaiwei Tian; Ning Tian; Ningxi Zhou (Advances in Space Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Pathways of south-derived iodine-129 intrusion into Tibet as revealed by its spatial distribution - Yukun Fan; Peng Cheng; Jie Zhou; Yanyun Wang; Weijian Zhou; Qi Liu; Luyuan Zhang; Huan Jiang; Ge Xu; Ning Chen; Xiaolin Hou (Journal of Hazardous Materials, 2025)

Fluoro-functionalized porous poly(ionic liquid)s for efficient CO2 conversion under mild conditions - Xiaoxia Yang; Ning Zhou; Xiaowen Xie; Tingyan Peng; Cheng Zhang; Xianglei Meng; Zhifeng Dai; Yubing Xiong (Fuel, 2025)

Localized chemical disorder induced superior energy storage performance of PbZrO3-based antiferroelectric ceramics - Mingqi Shi; Xingke Pan; Dingheng Lin; Ning Liu; Wei Zhang; Sen Chen; Peng Li; Jinjun Liu; Hongzhen Xie; Zhongbin Pan (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

National Inventory of Plastic Mulch Residues in Chinese Croplands From 1993 to 2050 - Jizhao Dai; Can Hu; Markus Flury; Yao Huang; Matthias C. Rillig; Dechang Ji; Jianwei Peng; Jiangchi Fei; Qing Huang; Youcai Xiong; Ning Yang; Davey L. Jones; et al. (Global Change Biology, 2025)
Agricultural plastic mulch films are a major source of plastic pollution of croplands. In China, which uses about 68% of the plastic mulch film produced globally (ca. 1.4 million tonnes y −1 ), soils have been heavily contaminated with mulch fragments. Here, we collected a national dataset of macroplastic residues (> 5 mm) in soil, including 3145 sampling sites, and provincial plastic film usage from 1992 to 2019 in China, and we established a linear model between the residue amount and historical cumulative usage within each province. Using the model, we quantified the amount of macroplastic residues in Chinese croplands on a national scale during the past 30 years and predict plastic pollution until 2050. Our results reveal the total national amount of plastic mulch residue in 2020 to be 2.07 million tonnes with a 95% CI of [1.67, 2.58]. This accumulated amount of plastic in Chinese soils roughly equals the annual amount of plastic films used globally (2.08 million tonnes in 2018) and is about 8% of national historically used plastic mulch film (27.3 million tonnes) remaining in soil as legacy plastic. Plastic concentrations in Chinese croplands in 2020 range from 7.7 kg ha −1 in Anhui to 399 kg ha −1 in Xinjiang, with an average value of 119 kg ha −1 (equivalent to 0.03 g kg −1 soil). We predict that the total amount and average concentration of plastic residues in Chinese croplands will reach 6.24 million tonnes and 357 kg ha −1 (equivalent to 0.1 g kg −1 soil) in 2050 under current plastic usage. There is an urgent need for regulatory actions to control plastic pollution in Chinese agriculture.

Upper limit of ice content at the lunar south pole as revealed by the Earth-based SYISR–FAST bistatic radar system - Mingyuan Li; Jinghai Sun; Xin’an Yue; Honglei Lin; Zhiqing Chen; Feng Ding; Baiqi Ning; Yong Wei; Chi Wang; Peng Jiang (Science Bulletin, 2025)

Characterization, mechanism, and application of aldolase: A Patulin-degrading enzyme from Kluyveromyces Marxianus YG-4 - Mengge Ning; Qi Guo; Peng Guo; Yuanyuan Cui; Kai Wang; Gengan Du; Zhouli Wang; Yuan Wang; Yahong Yuan; Tianli Yue (Food Bioscience, 2025)

Organic molecule-based nanoparticles for multimodal colorectal cancer therapy: Oxidative stress-induced apoptosis and ferroptosis - Dezhou Peng; Zhibo Zhang; Qiyu Zhang; Yichao Liu; Ning Wang (Chemical Engineering Journal, 2025)

Study on the contribution of the major desert groups on SDS weather in East Asia combining the model simulation and multiple observations - Huiqiong Ning; Hong Wang; Zhaodong Liu; Yue Peng; Wenjie Zhang; Chen Han; Yang Zhao; Ping Wang; Hailin Gui; Jikang Wang; Huizheng Che; Xiaoye Zhang (Atmospheric Research, 2025)

Study on the Flow Velocity Preference of the Four Major Chinese Carps Using Convolutional Neural Networks - Ning Qiu; Wenjing Li; Yi Yu; Jianna Jia; Guoqiang Ma; Shitao Peng (Fishes, 2025)
Flow velocity is a critical factor in determining the suitability of fish habitats. Understanding the preference patterns of the four major Chinese carps (FMCCs) for different flow velocities is crucial for their habitat conservation and restoration. In this study, the preference of individual fish species, approximately 15 cm in length, for flow velocity was investigated at flow velocity gradients of 0.0, 0.4, 0.8, 1.2, 1.6, and 2.0 times their body length. Additionally, a deep learning algorithm based on convolutional neural networks (CNNs) was employed for fish target detection. The results showed that, at this length, black carp (Mylopharyngodon piceus) preferred fast currents when the inlet flow velocity was between 0.4 and 1.6 times their body length, while grass carp (Ctenopharyngodon idella), silver carp (Hypophthalmichthys molitrix), and bighead carp (Hypophthalmichthys nobilis) preferred fast currents when the inlet flow velocity of the test flume was between 0.4 and 2.0 times their body length. However, this preference for fast currents decreased as the overall flow velocity increased to a specific threshold, eventually leading to their avoidance. The highest preference for fast currents among the four species was observed at inlet flow velocities of 1.2, 0.4, 0.8, and 0.8 times their body length, respectively. The findings of this study provide important insights into habitat conservation and restoration for the FMCCs in projects focused on the construction of navigation channels and water conservancy.

Construction of glycine modified NZVI@gelatin aerogel for high efficient activation of dissolved oxygen towards catalytic degradation of tetracycline - Xiangyu Wang; Kunhong Wu; Ping Ning; Zhiling Guo; Peng Zhang; Lisi Wu; Iseult Lynch (Journal of Water Process Engineering, 2025)

Insights into algae cell inactivation by mixed chlor(am)ines in source water: Unraveling removal mechanisms, derived risks and control methods - Zhu Peng; Tian-Yang Zhang; Qi Fu; Xiang-Chi Xie; Zhen-Ning Luo; Yu-Lin Tang; Huan He; Chao Zeng; Jian Lu; Yun-Qiao Zeng; Chen-Yan Hu; Bin Xu (Journal of Environmental Chemical Engineering, 2025)

Characterization and release of casein‑sodium alginate embedding phage edible film and the application in controlling of Salmonella contamination in food - Peng Guo; Lei Zhang; Mengge Ning; Ting Cai; Fangyu Long; Yahong Yuan; Tianli Yue (International Journal of Food Microbiology, 2025)

Theoretical analysis on absorption heat transformers boosted multi-effect distillation system for ocean thermal energy conversion - Suyun Yi; Zhixiang Zhang; Han Yuan; Yu Bai; Yongchao Sun; Wenyi Peng; Ning Mei; Yonggong Yuan; Tao Jiang (Desalination, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Ruthenium-doped carbon dots with “three-in-one” chemodynamic, photodynamic, and photothermal activity induce panoptosis for tumor therapy - Xiaokang Lu; Weijie Sun; Xingye Zheng; Lishen Yang; Tan Feng; Xiaoqin Deng; Fengqi Zhou; Hongmin Zhu; Ding Ma; Bilian Li; Guobao Ning; Hang Chen; et al. (Chemical Engineering Journal, 2025)

Knowledge of microalgal Rubiscos helps to improve photosynthetic efficiency of crops - Tongtong Zhu; Peng Ning; Yiguo Liu; Min Liu; Jianming Yang; Zhaobao Wang; Meijie Li (Planta, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Study of the initiating and resisting mechanisms of toppling deformations in anti-inclined rock slopes - Yibing Ning; Huiming Tang; Jianbing Peng; Yanjun Shen; John V. Smith; Tao Ding (Bulletin of Engineering Geology and the Environment, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Dynamic changes in gut microbiota and production phenotypes driven by host genetic background in large yellow croaker - Wei Liu; Junjia Zeng; Ning Suo; Qiaozhen Ke; Ji Zhao; Jiaying Wang; Yulin Bai; Yacheng Deng; Xiaoying Zhou; Yuhang Wang; Zhou Jiang; Tingsen Jiang; et al. (Aquaculture, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Complete genome sequence of Vreelandella sp. SM1641, a marine exopolysaccharide-producing bacterium isolated from deep-sea hydrothermal sediment of the Southwest Indian Ocean - Hai-Xia Zhu; Zhi-Gang Tang; Shi-Ning Cai; Jun-Hui Cheng; Peng Wang; Mei-Ling Sun (Marine Genomics, 2025)

Spatio-temporal characteristics and influencing factors of water quality in Xiangxi Bay under the operation of the three gorges reservoir - Aiping Jiang; Dongsheng Wang; Zhen Ning; Peng Li; Tao Xu; Boran Zhu; Qidong Peng; Tiantian Jin; Junqiang Lin; Di Zhang (Journal of Contaminant Hydrology, 2025)

Preparation of selenium in Kluyveromyces marxianus YG-4 and its protective effects in mice with patulin-induced jejunal injury - Mengge Ning; Peng Guo; Yuanyuan Cui; Gengan Du; Kai Wang; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Bioscience, 2025)

Immune regulation differences in Large yellow croaker with varied resistance to Cryptocaryon irritans infection - Zhou Jiang; Ji Zhao; Rui Li; Qiaozhen Ke; Jiaying Wang; Yin Li; Shuimu Hu; Junjia Zeng; Fei Pu; Ning Li; Peng Xu; Tao Zhou (Fish & Shellfish Immunology, 2025)

Characterization of a heat shock factor 1 (HSF1) gene and the association of its single nucleotide polymorphisms with susceptibility/resistance of Magallana gigas to Halomonas sp. 7T - Tianbao Liu; Qingyu Peng; Bo Wang; Lei Fang; Chuanyan Yang; Ning Kong; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2025)

Associations of green and blue space and the natural environment with suicidal ideation: The role of psychiatric disorders - Tong-Jie Feng; Wei Hu; Zhen-Zhen Shen; Jia-Ning Wang; Bao-Peng Liu; Cun-Xian Jia (Environmental Research, 2025)

Investigating the factors contributing to the maintenance of high levels of warm season nocturnal ozone in a basin city - Ying Xia; Xuan Chen; Youjiang He; Zhigang Xue; Yi Ning; Peng Wei; Qin Yan; Minghui Wei; Wenjie Zhang (Environmental Pollution, 2025)

A supramolecular biofilm disruptor based on cationic macrocyclic amphiphiles to eradicate bacterial biofilm-associated infections - Shiyu Peng; Linzhu Su; Er-Wei Zhang; Xiaoxue Hou; Qingxiang Guo; Ning Zhu; Tian-Xing Zhang; Dong-Sheng Guo; Jianfeng Liu; Fan Huang (Chemical Engineering Journal, 2025)

Noncovalently functionalized carbon microspheres for separating no-carrier added 177Lu from real neutron-irradiated 176Yb target - Guoquan Ma; Haiyue Peng; Xisheng Fan; Yuqi Guo; Yang Li; Jing Gao; Yingjiang Hu; Bo Li; Yuanyou Yang; Jingsong Zhang; Lijian Ma; Ning Liu; et al. (Chemical Engineering Journal, 2025)

A bioengineered antibody conjugate reshape dendritic cell viability for immune-tolerance modulation - Xiaoqing Chen; Yalin Wang; Tao Xu; Han Liu; Xinya Ye; Peng Wang; Xiaojing Qin; Shiting Yang; Wenjing Ning; Hongye Zeng; Lin Xu; Mujin Fang; et al. (Chemical Engineering Journal, 2025)

GHCYP706A7 governs anthocyanin biosynthesis to mitigate ROS under alkali stress in cotton - Yuping Sun; Ning Wang; Xiugui Chen; Fanjia peng; Junling Zhang; Heling Song; Yuan Meng; Mengyue Liu; Hui Huang; Yapeng Fan; Lidong Wang; Zhining Yang; et al. (Plant Cell Reports, 2025)

Refined simulation for predicting the seismic collapse of high and steep dangerous rock masses via the 3D discrete element method - Tao Gong; Ji Zhang; Chuan He; Jiang-peng Qian; Ming-zhi Xiang; Si-yuan Luo; Ning-an Wu; Kai-yun Yan; Jin Gao (Natural Hazards, 2025)

Susceptibility of Soil Elements to Biotic and Abiotic Factors in a Forest-Steppe Ecotone - Qiuhua Li; Jiayun Zhang; Chunbo Li; Hong Ji; Xiaomeng Ma; Peng He; Lixin Yu; Mengfan Zhou; Ning Dang; Jishuai Su; Ruzhen Wang; Heyong Liu; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Associations between shift work and biological age acceleration: A population-based study - Jia-Ning Wang; Wei Hu; Bao-Peng Liu; Cun-Xian Jia (GeroScience, 2025)

Spatiotemporal evolution of PM2.5 and its components and drivers in China, 2000–2023: effects of air pollution prevention and control actions in China - Yindi Peng; Yamin Zhao; Ning Gao; Dan Sheng; Shaoyan Tang; Shan Zheng; Minzhen Wang (Environmental Geochemistry and Health, 2025)

Molecular evidence for goose astrovirus 2 and goose astrovirus 3 coinfection in goslings with gout - Chen Guo; Jingjing Huang; Xiaoyang Hu; Qiong Li; Yinuo Song; Duo Peng; Kang Ning; Xiaoyan Wang; Dabing Zhang (Archives of Virology, 2025)

Effectiveness of Conditioning Strategies in Improving Fish Fitness‐Related Traits - Zonghang Zhang; Guihui Ning; Fei Tong; Wuhan Lin; Yangke Shang; Daomin Peng; Wenhua Liu (Fish and Fisheries, 2025)
Although conditioning strategies are widely used to increase fish post‐release adaptability in stock enhancement projects, their effectiveness has not been systematically evaluated. Using a global‐scale meta‐analysis, we demonstrate that three major conditioning strategies, including environmental enrichment, life skills training and release tactic, can significantly improve fish fitness‐related traits, with the fitness indicator and developmental stage being the most important moderators for interpreting the high heterogeneity among cases. The effect size of approximate fitness indicators was marginally lower than that of post‐release behavioural traits. Our findings indicate the necessity of conditioning procedures and highlight the need to enact context‐dependent strategies in practical conservation projects.

Design and Testing of an autonomous laser weeding robot for strawberry fields based on DIN-LW-YOLO - Peng Zhao; Junlin Chen; Jiahao Li; Jifeng Ning; Yongming Chang; Shuqin Yang (Computers and Electronics in Agriculture, 2025)

Toll-like receptors landscape in Takifugu fasciatus: Dynamic responses to Aeromonas hydrophila, poly I:C, and Ichthyophthirius multifiliis challenge - Ge Lin; Peng Chu; Xiang Gong; Yuxi Liu; Kai Zhang; Xianhui Ning; Tao Wang; Shaowu Yin; Jie Ji (Aquaculture, 2025)

A novel zearalenone lactonase can effectively mitigate zearalenone-induced reproductive toxicity in gilts - Jun-Chao Song; Zhe Peng; Yan-Qi Ning; Alainaa Refaie; Cheng-Fei Wang; Meng Liu; Lv-Hui Sun (Toxicon, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cu/TiO2 adsorbents modified by air plasma for adsorption–oxidation of H2S - Yongqi Yan; Xinyu Yang; Ping Ning; Chi Wang; Xin Sun; Fei Wang; Peng Gao; Kai Li (Journal of Environmental Sciences, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Knowledge-based phosphorus input levels control the link between soil microbial diversity and ecosystem functions in paddy fields - Qiaorong Li; Yao Liu; Ning Su; Chang Tian; Yuping Zhang; Lin Tan; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Agriculture, Ecosystems & Environment, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Biotic and abiotic removal of acetaminophen during sidestream partial nitritation processes: Underlying mechanisms and transformation pathways - Ning Wang; Yifeng Xu; Lai Peng; Chuanzhou Liang; Shaoxian Song; Mildred Quintana (Science of The Total Environment, 2025)

200 years of Portland cement: Technological advancements and sustainability challenges - Hao Chen; Ning Li; Cise Unluer; Peng Chen; Zuhua Zhang (Journal of Cleaner Production, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Probe on the pivotal role of green rust in improving the enzymatic activity and facilitating the formation of 1O2 in Fenton-like process for degradation of 4-chlorophenol - Jie Peng; Meng Li; Qian Zhang; Zefeng Li; Ziqi Zhao; Yuwei Ding; Ning Du (Journal of Environmental Management, 2025)

Biocontrol activity of Kluyveromyces marxianus YG-4 against Penicillium expansum LPH9 on apples - Mengge Ning; Qi Guo; Peng Guo; Yuanyuan Cui; Kai Wang; Gengan Du; Zhouli Wang; Yahong Yuan; Tianli Yue (International Journal of Food Microbiology, 2025)

Mercury isotope evidence for Middle Ordovician photic-zone euxinia: Implications for termination of the Great Ordovician biodiversification event - Mu Liu; Wei Yuan; Chaogang Fang; Xun Wang; Ning Tan; Mingyu Zhao; Xiangli Wang; Thomas J. Algeo; Peng Sun; Xinbin Feng; Daizhao Chen (Gondwana Research, 2025)

Investigating the interaction mechanisms between arachin and resveratrol: Utilizing multi-spectroscopy and computational chemistry - Yu-qi Yang; Qi Gao; Shi-qi Yue; Xue Peng; Ning Wang; Jing-li Xin; Miao Yu; Jia-jia Rao; You-lin Xue (Food Chemistry, 2025)

Multi-period optimal scheduling of building loads based on accurate virtual battery model - Xiuli Zhu; Peng Wang; Ning Li; Weiwu Yan (Energy and Buildings, 2025)

Innovative Janus wood membranes: Harnessing wood anisotropy for superior liquid separation and transport - Kaiwen Chen; Xianfu Xiao; Cheng Hao; Fengze Sun; Haonan Zhang; Yujing Tan; Jianyi Zhu; Hui Peng; Tianyi Zhan; Jianxiong Lyu; Ning Yan (Chemical Engineering Journal, 2025)

Enhancing fire suppression in restricted spaces with fine water mist microcapsules - Yijun Ren; Peng Zhang; Hairui Bian; Dang Ding; Chen Li; Ning Sang; Jiachao Zhang; Fangsheng Huang; Zhiqiang Zhu (Chemical Engineering Journal, 2025)

Four-step continuous-flow biosynthesis of a chiral precursor for angiotensin-converting enzyme inhibitors - Heyong Wang; Meiluan Wang; Guixiang Huang; Mingye Zhao; Yongzhen Peng; Ning Zhu; Zheng Fang; Yujing Hu; Kai Guo (Chemical Engineering Journal, 2025)

Activation potential decreasing of iron oxide/graphite felt cathode by introducing Mn in electrochemical Fenton-like reactions - Yalong Xu; Weijian Li; Jun Wang; Di Wu; Ning Li; Yang Li; Xiaobin Fan; Wenchao Peng (Chemosphere, 2024)

Leaching behavior and release mechanism of pollutants from different depths in a phosphogypsum stockpile - Han Ke; Shu Ning Zheng; Peng Ze Zhang; Bo Xiao; Ji Wu Lan; Shuai Zhang; Jie Hu (Waste Management, 2024)

Roadside measurement of N2O and CH4 emissions from vehicles in Hong Kong - Mengyuan Chu; Peter Brimblecombe; Nirmal Kumar Gali; Meisam Ahmadi Ghadikolaei; Peng Wei; Xin Li; Shiyi Yang; Yuanhui Wei; Zhi Ning (Science of The Total Environment, 2024)

IMST-based identification of time-varying cable forces in cable-supported bridges: Numerical, experimental, and field test validation - Ning Yang; Xun Liu; Peng Huang; Yongbing Huang; Mingqiang Xu; Kaiqi Lin (Ocean Engineering, 2024)

Chiral FeNC single-atom nanozymes with multi-enzyme activity for dye degradation - Guobao Ning; Huan Liang; Linjiang Guo; Xiaokang Lu; Lin Xiao; Tianle Qi; Hui Zhao; Can-Peng Li (Journal of Environmental Chemical Engineering, 2024)

The protective effect of specific yolk antibody against nervous necrosis virus infection in Mandarin fish(Siniperca chuatsi) - Zengjian Liang; Yunshang Ning; Jinqiao Cao; Shijia Liu; Xia Liang; Xiaomei Peng; Youhua Huang; Jingguang Wei; Sumei Xiao; Qiwei Qin; Sheng Zhou (Fish & Shellfish Immunology, 2024)

Constructing micro-region networks in expanded graphite for bi-directional high thermal conductivity of thermoplastic polymer composite - Junqi Ning; Zhe Wang; Yue Zhang; Xinyue Xu; Ting Ma; Jiaxian Du; Haodi Wang; Jianwen Peng; Di Bao; Yanji Zhu; Huaiyuan Wang (Chemical Engineering Journal, 2024)

Cation exchange strategy of ellagic acid-based microporous metal-organic framework for efficient CO2/N2 and CO2/CH4 separation - Chen-Ning Li; Zhi-Peng Tao; Lin Liu; Daqiang Yuan; Zheng-Bo Han (Chemical Engineering Journal, 2024)

Artificial islands in modern development: Construction, applications, and environmental challenges - Yan-Ning Wang; Jing-Rui Peng; Chandra Bogireddy; Bharat Rattan; Meng-Xi Tan (Marine Georesources & Geotechnology, 2024)

Enhanced Adsorption of Cadmium onto Microplastics Derived from Polyethylene Mulching Film by Weathering - Lu Wang; Ruichang Zhang; Shufa Zhu; Jing Li; Xinquan Zhou; Ning Zhang; Shuge Peng; Xuefeng Wei (Water, Air, & Soil Pollution, 2024)

Exploring the global impact of obesity and diet on dementia burden: the role of national policies and sex differences - Xueshan Cao; Huiyuan Peng; Ziyi Hu; Chang Xu; Monan Ning; Mengge Zhou; Yuanqi Mi; Peixin Yu; Vince Fazekas-Pongor; David Major; Zoltan Ungvari; Monika Fekete; et al. (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Synchrotron-aided exploration of REE recovery from coal fly ashes within a Canadian context - Yuwei Wu; Guohe Huang; Peng Zhang; Yao Yao; Kai Zhao; Jian Shen; Renfei Feng; Ning Chen (Chemosphere, 2024)

Green synthesis of diatom–allophane bio-nanocomposites for highly efficient oxytetracycline adsorption - Mengyuan Li; Shun Wang; Dong Liu; Dusan Losic; Ning Zhao; Qian Tian; Yuguo Shen; Rongda Yu; Hao Liu; Qiyi Ma; Peng Yuan (Science of The Total Environment, 2024)

Reproductive resilience of growth and nitrogen uptake underpins yield improvement in winter wheat with forced delay of sowing - Xiaojie Feng; Yangbo Huai; Suoqian Kang; Lu Yang; Yonghua Li; Jiaru Feng; Zhe Zhang; Michael J.W. Maw; Zhenling Cui; Peng Ning (Science of The Total Environment, 2024)

Physicochemical properties, structural characteristics and protein digestibility of pea protein-wheat gluten composited meat analogues prepared via high-moisture extrusion - Yu-Ru Zhao; Ning Peng; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Cai-Yue Wang; Zi-Yue Wang; Chenying Wang; Xidong Ren (Food Hydrocolloids, 2024)

Mg-Substituted dual-walled Prussian blue analogous achieving enhanced active sites and stability for aqueous Al-ion batteries - Weijin Chang; Jian Peng; Wenshan Mao; Qisen Wang; Yuanmin Zhu; Ning Peng (Chemical Engineering Journal, 2024)

Three birds with one stone: A nano zeolitic imidazolate framework-luciferase-antimicrobial peptide biocomposite-based biosensing platform for improving enzyme stability, detection sensitivity, and sterilization effect - Renjie Zhou; Tingting He; Linhao Peng; Dengfeng Li; Zhenzhong Yu; Xin Yang; Ning Gan (Chemical Engineering Journal, 2024)

Selective regulation of nanosheets inside or outside carbon nanoboxes for advanced supercapacitors - Tao Peng; Yili Wang; Ya Yang; Ning Zhang; Weiwei Sun; Mengzhen Ma; Yang Lu; Yongsong Luo (Chemical Engineering Journal, 2024)

The influence of concentration and size on the error of particulate matter detection using charge induction method - Kai Zhang; Yaqi Peng; Hong Yu; Pei Ning; Xueyong Hou; Ling Zhu; Shengyong Lu (Atmospheric Pollution Research, 2024)

A fire risk pre-warning framework for high-rise buildings based on unascertained method - Li-Ning Zhang; Xiang-Ming Wang; Jing An; Hong Xian Li; Jiao-Qian Guo; Guo-bo Han; Peng-Fei Gou (Environmental Science and Pollution Research, 2024)
The growing global interest in preventing and controlling fires in high-rise buildings reflects the increasing significance of this issue today. This research aims to establish an early warning framework for fire risk in high-rise buildings. Firstly, considering the importance of a scientific indicator system for the application of the model, this study combines the event analysis method with the building design fire code to identify 11 key risk factors that have a far-reaching impact on the prevention of fires in high-rise buildings. Based on identifying the risk factors, a high-rise building fire risk warning tree is also established, which scientifically solves the problem of the indicator system of the warning object. Subsequently, in response to the various complex issues arising from the uncertainty of fire occurrence in high-rise buildings, this study adopts the unascertained method to model the fire risk of high-rise buildings for early warning. In addition, the developed methodology was empirically validated through case studies and analyses of empirical data on fire risks in nine representative high-rise buildings. The results of the unascertained method were also compared with the results of the K-means method, from which it was concluded that the unascertained method can predict building fires more accurately. The research results provide a reliable decision support system for fire disaster prevention and control in high-rise buildings.

Environmental explanation of prostate cancer progression based on the comprehensive analysis of polychlorinated biphenyls - Wen-Cai Zheng; Fei Lin; Qian-Ren-Shun Qiu; Yu-Peng Wu; Zhi-Bin Ke; Shao-Hao Chen; Dong-Ning Chen; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Science of The Total Environment, 2024)

Evidence for archaeal metabolism of D-amino acids in the deep marine sediments - Yang Yu; Ning-Hua Liu; Zhao-Jie Teng; Yin Chen; Peng Wang; Yu-Zhong Zhang; Hui-Hui Fu; Xiu-Lan Chen; Yu-Qiang Zhang (Science of The Total Environment, 2024)

Relevance of genetic causes and environmental adaptation of Cronobacter spp. isolated from infant and follow-up formula production factories and retailed products in China: A 7-year period of continuous surveillance based on genome-wide analysis - Wei Tong; Dajin Yang; Shaofu Qiu; Sai Tian; Zehong Ye; Shuran Yang; Lin Yan; Weiwei Li; Ning Li; Xiaoyan Pei; Zhongqing Sun; Chengwei Liu; et al. (Science of The Total Environment, 2024)

Molecular weight-dependent differences in spectral properties and metal-binding behaviors of dissolved organic matter from different lakes - Keli Yang; Yaoling Zhang; Jiaoyu Peng; Huacheng Xu; Xin Liu; Haining Liu; Ning Li; Laodong Guo; Wu Li (Science of The Total Environment, 2024)

Tracing the vertical migration of exogenous cadmium in soil by seasonal freeze-thaw event using rare earth elements - Quan-Ying Wang; Mei-Xuan Wu; Nai-Wen Hu; Bo-Ling Deng; Tian-Ye Wang; Xiu-Tao Yang; Guo-Peng Zhu; Ning-Ning Song; Ying Zeng; Bo Hu; Hong-Wen Yu (Science of The Total Environment, 2024)

High sulfur-to-iron ratios enhance thallium(I) sequestration by sulfidated zero-valent iron - Nana Wang; Fengli Liu; Huosheng Li; Ping Zhang; Juanxi Huang; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Dan Peng; Yuqi Wang; Huanbin Huang; Zengping Ning (Process Safety and Environmental Protection, 2024)

High efficiency separation of bastnaesite (REFCO3) and monazite (REPO4) in mixed rare earth concentrate by heating under N2 and leaching with HCl/AlCl3 - Jiahao He; Peng Gao; Shuai Yuan; Shaokai Cheng; Jilai Ning; Zhenya Zhou; Yongsheng Sun; Wenbo Li (Hydrometallurgy, 2024)

A reliable fluorescence “turn-on” aptasensor based on dual-emitting europium metal-organic frameworks for ultrasensitive and selective detection of sulfamethazine - Qingxiang Liu; Xuelian Hu; Xiaoxiao Dong; Peng Liu; Ning Zhang; Zhe Gao; Wenxiu Wang; Huiling Li; Shuo Wang; Xiuying Liu; Yiwei Tang (Food Chemistry, 2024)

Synergetic effect of green synthesized NZVI@Chitin-modified ZSM-5 for efficient oxidative degradation of tetracycline - Xiangyu Wang; Yimin Zheng; Ping Ning; Iseult Lynch; Zhiling Guo; Peng Zhang; Lisi Wu (Environmental Research, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

Rechargeable Self-Powered pressure sensor based on Zn-ion battery with high sensitivity and Broad-Range response - Yong-Peng Hu; Kai-Yang Liu; Ruo-Ning Bai; Da-Zhuang Liu; Wei Yu; Chui-Zhou Meng; Guo-Xian Li; Shi-Jie Guo (Chemical Engineering Journal, 2024)

Removal characteristics of PCDD/Fs by an adsorbent injection coupled with a baghouse filter system - Kai Zhang; Hong Yu; Shengyong Lu; Juan Qiu; Pei Ning; Xueyong Hou; Ling Zhu; Yaqi Peng (Atmospheric Pollution Research, 2024)

Short-length SSVEP data extension by a novel generative adversarial networks based framework - Yudong Pan; Ning Li; Yangsong Zhang; Peng Xu; Dezhong Yao (Cognitive Neurodynamics, 2024)

Calcium isotopic composition of the bulk silicate Earth: A komatiite perspective - Ze-Ning Wang; Yang Wang; Paolo Sossi; Yongsheng He; Yue Peng; Wen-Ning Lu; Hongjie Wu (Lithos, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

Sustainable forest development in the face of global warming: Optimizing Robinia pseudoacacia L. stands to alleviate soil moisture depletion - Ning Wang; Huaxing Bi; Ruidong Peng; Danyang Zhao; Zehui Liu (Journal of Cleaner Production, 2024)

U(VI) sorption on illite in the Co-existence of carbonates and humic substances - Xiaoyu Yin; Yufan Zhao; Peng Guo; Peng Wu; Chao Chen; Aiming Zhang; Jiali Liao; Yuanyou Yang; Ning Liu; Tu Lan (Journal of Environmental Radioactivity, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

Characterisation of aroma compounds, sensory characteristics, and bioactive components of a new type of huangjiu fermented with Chinese wild rice (Zizania latifolia) - Yuzong Zhao; Mingyue Gu; Peng Jiang; Song Fang; Ning Yan; Fanyu Kong; Donglin Ma; Dongliang Ren; Xueli Pang; Jun Qiu (Food Chemistry, 2024)

Dissecting PM sensor capabilities: A combined experimental and theoretical study on particle sizing and physicochemical properties - Xiaoliang Qin; Peng Wei; Zhi Ning; Nirmal Kumar Gali; Meisam Ahmadi Ghadikolaei; Ya Wang (Environmental Pollution, 2024)

TpPa-1/{010}-BiVO4 S-scheme heterojunction fabricated on specific crystal facets for highly efficient H2O2 artificial photosynthesis - Zhibo Tong; De-Kun Ma; Jianan Wu; Xia Hu; Ning Jiang; Xiaogang Yang; Tai Peng (Chemical Engineering Journal, 2024)

Patterns and drivers of organic carbon in hydromorphic soils across inland aquatic-terrestrial ecotones at the global scale - Yiguo Ran; Peng Wang; Fei Ye; Junfeng Qu; Yang Ning; Yanshuo Zhang; Zhaofei Wen; Shengjun Wu; Ping Huang (CATENA, 2024)

SS-31 mitigates oxidative stress and restores mitochondrial function in cigarette smoke-damaged oral epithelial cells via PINK1-mediated mitophagy - Pei Ye; Hong Liu; Yao Qin; Zhiyuan Li; Zhuwei Huang; Xiangwen Bu; Qiao Peng; Ning Duan; Wenmei Wang; Xiang Wang (Chemico-Biological Interactions, 2024)

Accelerated screening of active sites on biochar for catalysis and adsorption via multidimensional fingerprint factor descriptors - Wenjie Gao; Ning Li; Zhanjun Cheng; Beibei Yan; Wenchao Peng; Shaobin Wang; Guanyi Chen (Bioresource Technology, 2024)

The Carbon and Nitrogen Balance in Developing Grains Affects Grain Protein Concentrations in Two Wheat Varieties with Similar Yields - Xiaojie Feng; Yonghua Li; Suoqian Kang; Yangbo Huai; Fengmei Zhang; Peng Ning (International Journal of Plant Production, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Organic radicals driving polycyclic aromatic hydrocarbon polymerization with peracetic acid activation in soil - Ziyue Li; Xiaolei Wang; Fei Peng; Ning Chen; Guodong Fang (Journal of Hazardous Materials, 2024)

Loss of microbial functional diversity following Spartina alterniflora invasion reduces the potential of carbon sequestration and nitrogen removal in mangrove sediments—from a gene perspective - Zetao Dai; Ning Zhang; Feifei Wang; Yujie Li; Jiarui Peng; Tao Xiang; Xiaoyu Zhao; Shengchang Yang; Wenzhi Cao (Journal of Environmental Management, 2024)

Soil improvement using biostimulated MICP: Mechanical and biochemical experiments, reactive transport modelling, and parametric analysis - Yi-jie Wang; Wen-bo Chen; Peng-lin Li; Zhen-yu Yin; Jian-hua Yin; Ning-jun Jiang (Computers and Geotechnics, 2024)

Fe-Co PBA/rGO interface strategy enabling fast Al3+ intercalation for stable aqueous Al-ion batteries - Anning Zhao; Jian Peng; Wenshan Mao; Qisen Wang; Yuanmin Zhu; Ning Peng (Chemical Engineering Journal, 2024)

Modulating proportion of Ni0 species stabilized by Ni2+ on Ni-MgO catalyst with superior stability for dry reforming of methane - Xieyi Liu; Junjie Wen; Yu xie; Zongling Li; Manshu Zhong; Rongbing Nie; Shiyuan Peng; Jinyan Cao; Jianjun Chen; Ping Ning; Qiulin Zhang (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

Synergistic enhancement of regeneration capacity and ecological functions of Robinia pseudoacacia L. plantations in the Loess Plateau - Ning Wang; Huaxing Bi; Ruidong Peng; Danyang Zhao; Zehui Liu (CATENA, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Application of airborne gamma-ray spectrometry in geological lithology mapping—a case study of a region in the Qinling Mountains, China - Yongzai Xi; Guixiang Liao; Yongbo Li; Junjie Liu; Shan Wu; Ning Lu; Peng He (Acta Geophysica, 2024)

An Algorithm for Ship Detection in Complex Observation Scenarios Based on Mooring Buoys - Wenbo Li; Chunlin Ning; Yue Fang; Guozheng Yuan; Peng Zhou; Chao Li (Journal of Marine Science and Engineering, 2024)
Marine anchor buoys, as fixed-point profile observation platforms, are highly susceptible to the threat of ship collisions. Installing cameras on buoys can effectively monitor and collect evidence from ships. However, when using a camera to capture images, it is often affected by the continuous shaking of buoys and rainy and foggy weather, resulting in problems such as blurred images and rain and fog occlusion. To address these problems, this paper proposes an improved YOLOv8 algorithm. Firstly, the polarized self-attention (PSA) mechanism is introduced to preserve the high-resolution features of the original deep convolutional neural network and solve the problem of image spatial resolution degradation caused by shaking. Secondly, by introducing the multi-head self-attention (MHSA) mechanism in the neck network, the interference of rain and fog background is weakened, and the feature fusion ability of the network is improved. Finally, in the head network, this model combines additional small object detection heads to improve the accuracy of small object detection. Additionally, to enhance the algorithm’s adaptability to camera detection scenarios, this paper simulates scenarios, including shaking blur, rain, and foggy conditions. In the end, numerous comparative experiments on a self-made dataset show that the algorithm proposed in this study achieved 94.2% mAP50 and 73.2% mAP50:95 in various complex environments, which is superior to other advanced object detection algorithms.

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Enhancing crop productivity and resilience by promoting soil organic carbon and moisture in wheat and maize rotation - Yonghua Li; Xiaojie Feng; Yangbo Huai; Mahmood UI Hassan; Zhenling Cui; Peng Ning (Agriculture, Ecosystems & Environment, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Highly-efficient persulfate activation by nitrogen-doped biochar derived from dewatered sewage sludge for 2,4-dichlorophenol removal: Process and mechanism - Jiali Cui; Liuyi Wei; Chaoneng Ning; Feng Zhang; Jianguo Cui; Peng Xiangli (Journal of Environmental Chemical Engineering, 2024)

Antimicrobial susceptibility and genomic characterization of Vibrio parahaemolyticus isolated from aquatic foods in 15 provinces, China, 2020 - Yao Bai; Qiuping Yang; Yanan Sun; Fengqin Li; Jiali Sun; Shuran Yang; Dajin Yang; Zixin Peng; Baowei Yang; Jin Xu; Yinping Dong; Shaofei Yan; et al. (International Journal of Food Microbiology, 2024)

Seismic displacement of bedding slopes stabilized with anchor cables and piles considering dynamic yield acceleration - Hui Qi; Changcheng Du; Ming Peng; Ning Bao (Bulletin of Engineering Geology and the Environment, 2024)

Quorum sensing mediates gut bacterial communication and host-microbiota interaction - Yucheng Zhang; Ning Ma; Peng Tan; Xi Ma (Critical Reviews in Food Science and Nutrition, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Reconstructing atmospheric 129I deposition over 170 years with the varved sediment in the Sihailongwan Maar Lake, northeast China - Luyuan Zhang; Ning Chen; Xiaolin Hou; Yongming Han; Tong Zhang; Dewen Lei; Weijian Zhou; Zhisheng An; Peng Cheng; Jianghu Lan; Liangcheng Tan; Qi Liu; et al. (Science of The Total Environment, 2024)

Associations of ambient ozone exposure and CD4+ T cell levels with mortality among people living with HIV: An eight-year longitudinal study - Hao Chen; Kai Zhang; Dongying Wei; Jiawen Zhu; Weiyi Tian; Jinli Mo; Hongbin Peng; Xia Luo; Yinxia Liang; Yanna Pan; Li Jiang; Yunan Xu; et al. (Science of The Total Environment, 2024)

Antimony and arsenic migration in a heterogeneous subsurface at an abandoned antimony smelter under rainfall - Chao Li; Yiyuan Ran; Pan Wu; Peng Liu; Boyi Yang; Xueyuan Gu; Ping Zhao; Shirong Liu; Lei Song; Yuhui Liu; Yizhang Liu; Zengping Ning; et al. (Journal of Hazardous Materials, 2024)

Fe-N co-doped biochar derived from biomass waste triggers peracetic acid activation for efficient water decontamination - Ruyan Ning; Yudan Dong; Shu-Run Yang; Shuai Yang; Peng Zhou; Zhaokun Xiong; Zhi-Cheng Pan; Chuan-Shu He; Bo Lai (Journal of Hazardous Materials, 2024)

Can the concentration of environmentally persistent free radicals describe its toxicity to Caenorhabditis elegans? Evidence provided by neurotoxicity and oxidative stress - Huijie Li; Hao Li; Ning Zuo; Di Lang; Wei Du; Peng Zhang; Bo Pan (Journal of Hazardous Materials, 2024)

Experimental study of the effect of nanosecond pulse discharge parameters on the methane-air mixture combustion - Jie Tian; Yong Xiong; Lu Wang; Yongqi Wang; Peng Liu; Xinguo Shi; Ning Wang; Wei Yin; Yong Cheng; Qingwu Zhao (Fuel, 2024)

Polydopamine@ZIFs with enhanced electrochemiluminescence quenching performance for mycotoxin detection - Qing Yang; Jianhua Xiong; Luying Duan; Sida Chen; Zhongji Peng; Xiaoning Liao; Zhenqiang Ning; Dan Wang (Food Chemistry, 2024)

Nanofiltration membrane with modified nano-gradient structure and positive charge for Li separation from high Mg/Li ratio brine - Peng Zhao; Fei Guo; Lingfeng Wang; Huange Zhen; Ning Zhang; Shaohua Yin; Guoli Zhou; Xuehua Ruan; Gaohong He; Xiaobin Jiang (Desalination, 2024)

Increased precipitation rather than warming increases ecosystem multifunctionality in an alpine meadow - Lina Shi; Zhenrong Lin; Zeying Yao; Cuoji Peng; Meng-ai Hu; Ning Yin; Xinmin Lu; Huakun Zhou; Kesi Liu; Xinqing Shao (Plant and Soil, 2024)

Synthesis and Application of Specific N2H4 Fluorescent Probes with AIE Effect Based on Pyrazole Structure - Yun-Shang Yang; Zhen Zhang; Ying-Peng Zhang; Yu-Ning Liang; Xing-Xing Li; Zhi-Dong Teng (Journal of Fluorescence, 2024)

Rapid immobilization of arsenic in contaminated soils by microwave irradiation combined with magnetic biochar: Microwave-induced electron transfer for oxidation and immobilization of arsenic (III) - Dengcai Zhang; Junhao Lin; Juan Luo; Shichang Sun; Xi Zhang; Rui Ma; Juan Peng; Fei Ji; Shuaifei Zheng; Zhen Tian; Ning Ma (Science of The Total Environment, 2024)

ALKBH5 SUMOylation-mediated FBXW7 m6A modification regulates alveolar cells senescence during 1-nitropyrene-induced pulmonary fibrosis - Se-Ruo Li; Ning-Ning Kang; Rong-Rong Wang; Meng-Die Li; Li-Hong Chen; Peng Zhou; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Electric-field-controlled energy barrier and reaction pathway ensure high sulfur product selectivity in Cu/γ-Al2O3 catalyst-assisted DBD plasma conversion of carbonyl sulfide - Yixing Ma; Peng Chen; Defu Li; Fei Wang; Langlang Wang; Kai Li; Ping Ning; Xueqian Wang; Kostya (Ken) Ostrikov (Journal of Environmental Chemical Engineering, 2024)

The removal mechanisms of HF and HCl gases using Mg-Al adsorbent prepared by sol-gel synthesis method - Peng Gao; Jiayu Feng; Yuxuan Xie; Xinyu Yang; Ping Ning; Xin Sun; Fei Wang; Lei Shi; Jie Zhao; Kai Li (Journal of Environmental Chemical Engineering, 2024)

Application of g-C3N4-based photocatalysts for N2 photofixation - Longjian Li; Ping Zhang; Ning Li; Tuerhong Reyila; Yongchong Yu; Xiaoping Su; Cheng Peng; Lijuan Han (Journal of Environmental Chemical Engineering, 2024)

Ultrafine FeCuAgCeGd–based high–entropy nanozyme: Preparation, catalytic mechanism, and point–of–care detection of dopamine in human serum - Rui Sheng; Yue Liu; Taimei Cai; Rong Wang; Gan Yang; Tao Wen; Fangjian Ning; Hailong Peng (Chemical Engineering Journal, 2024)

A chemo/chemodynamic nanoparticle based on hyaluronic acid induces ferroptosis and apoptosis for triple-negative breast cancer therapy - Ning Wang; Qiyu Zhang; Zhuoya Wang; Yichao Liu; Sen Yang; Xuerong Zhao; Jinyong Peng (Carbohydrate Polymers, 2024)

Microbial phosphorus‐cycling genes in soil under global change - Xuewei Wang; Hui Guo; Jianing Wang; Peng He; Yakov Kuzyakov; Miaojun Ma; Ning Ling (Global Change Biology, 2024)
The ongoing climate change on the Tibetan Plateau, leading to warming and precipitation anomalies, modifies phosphorus (P) cycling in alpine meadow soils. However, the interactions and cascading effects of warming and precipitation changes on the key “extracellular” and “intracellular” P cycling genes (PCGs) of bacteria are largely unknown for these P‐limited ecosystems. We used metagenomics to analyze the individual and combined effects of warming and altered precipitation on soil PCGs and P transformation in a manipulation experiment. Warming and increased precipitation raised Olsen‐P (bioavailable P, AP) by 13% and 20%, respectively, mainly caused by augmented hydrolysis of organic P compounds (NaOH‐Po). The decreased precipitation reduced soil AP by 5.3%. The richness and abundance of the PCGs' community in soils on the cold Tibetan plateau were more sensitive to warming than altered precipitation. The abundance of PCGs and P cycling processes decreased under the influence of individual climate change factors (i.e., warming and altered precipitation alone), except for the warming combined with increased precipitation. Pyruvate metabolism, phosphotransferase system, oxidative phosphorylation, and purine metabolism (all “intracellular” PCG) were closely correlated with P pools under climate change conditions. Specifically, warming recruited bacteria with the phoD and phoX genes, which encode enzymes responsible for phosphoester hydrolysis (extracellular P cycling), strongly accelerated organic P mineralization and so, directly impacted P bioavailability in alpine soil. The interactions between warming and altered precipitation profoundly influenced the PCGs' community and facilitated microbial adaptation to these environmental changes. Warming combined with increased precipitation compensated for the detrimental impacts of the individual climate change factors on PCGs. In conclusion, warming combined with rising precipitation has boosting effect on most P‐related functions, leading to the acceleration of P cycling within microbial cells and extracellularly, including mineralization and more available P release for microorganisms and plants in alpine soils.

Nitrogen-doped substrate material ion imprinting–capacitive deionization selective recovery of lithium ions from acidic solutions - Yifei Li; Ning Han; Qiongqiong He; Haisen Peng; Xiaoqi Wu; Zhen Meng; Zhenyong Miao (Environmental Science and Pollution Research, 2024)

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

Structural/surface characterization of transition metal element–doped H-ZSM-5 adsorbent for CH3SH removal: identification of active adsorption sites and deactivation mechanism - Yuxuan Xie; Xiao Peng; Xin Song; Ping Ning; Xin Sun; Yixing Ma; Chi Wang; Kai Li (Environmental Science and Pollution Research, 2024)

Abrupt diatom assemblage shifts in Lake Baiyangdian driven by distinct hydrological changes and yet more so by gradual eutrophication - Xin Mao; Linjing Liu; Hongmei Zhao; Yawen Ge; Gaolei Jiang; Lei Song; Kai Ning; Hua Zhao; Peng Zhang (Limnologica, 2024)

Performance assessment of solar photovoltaic-based constructed wetland for sustainable rural wastewater treatment - Ye Yang; Chao-Kun Li; Liu Han; Zhi-Peng Yang; Ning-Ning Xiao; Nan Zhang; Ying-Ying Dong; Zhi-Wen Chen; Hui Xi; Wen-Dong Wang (Journal of Water Process Engineering, 2024)

Influence of SiO2 size effect on multi-scale micro-nanostructure superhydrophobic Al2O3 ceramic membrane: Preparation, mechanism, application - Jiangmin Xiong; Ning Duan; Chenglong Lu; Yinfeng Zhang; Chongrui Li; Shaoxin Peng; Yongxiang Lai; Kaiwen Hu (Journal of Water Process Engineering, 2024)

Distinct toxic effects, gene expression profiles, and phytohormone responses of Polygonatum cyrtonema exposed to two different antibiotics - Guoqun Yang; Dong Jiang; Li-Jun Huang; Chuantong Cui; Runke Yang; Xin Pi; Xia Peng; Xiaofeng Peng; Jianhui Pi; Ning Li (Journal of Hazardous Materials, 2024)

Adsorption and aggregation of Cu2+ on carboxymethylated sugarcane bagasse: Adsorption behavior and mechanism - Shiping Zhang; Jinyan Cao; Peng Yang; Yu Xie; Huiming Wang; Yufeng Mao; Kegong Ning; Qiulin Zhang (Journal of Hazardous Materials, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Preparation and characterization of pea protein isolate-egg white protein composite gels - Yu-Ru Zhao; Ning Peng; Chenying Wang; Ying-Qiu Li; Yan Liang; Zhi-Wei Guo; Ao-Yue Sun; Xidong Ren (Food Hydrocolloids, 2024)

Assessment of nonylphenol exposure based on global urinary concentration data and its risk analysis - Jiemei Li; Hongling Zhang; Juanhua Li; Ning Qin; Qiufen Wei; Yuanyuan Li; Yang Peng; Han Li (Environmental Research, 2024)

The application study of the revised IMPROVE atmospheric extinction algorithm in atmospheric chemistry model focusing on improving low visibility prediction in eastern China - Chen Han; Hong Wang; Yue Peng; Zhaodong Liu; Wenjie Zhang; Yang Zhao; Huiqiong Ning; Ping Wang; Huizheng Che (Atmospheric Research, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Increasing variance of rich-club nodes distribution in early onset depression according to dynamic network - Naikeng Mai; Yujie Wu; Xiaomei Zhong; Ben Chen; Min Zhang; Qi Peng; Yuping Ning (Brain Imaging and Behavior, 2024)

Simultaneous production of high-valued carbon nanotubes and hydrogen from catalytic pyrolysis of waste plastics: The role of cellulose impurity - Qingyu Liu; Bo Peng; Ning Cai; Yinhai Su; Siyu Wang; Peng Wu; Qi Cao; Huiyan Zhang (Waste Management, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Effectiveness of a 10-year continuous reduction of controlled-release nitrogen fertilizer on production, nitrogen loss and utilization of double-cropping rice - Ning Su; Xiangmin Ronga; Guixian Xie; Tian Chang; Yuping Zhang; Jianwei Peng; Gongwen Luo (Science of The Total Environment, 2024)

Dual roles derived from lattice incorporation of Cl- in ultrathin LiCoO2-xClx for water elelctrolysis - Ning Yu; Hai-Jun Liu; Jing-Ke Ren; Zhi-Jie Zhang; Yu Ma; Xue-Jun Zhai; Da-Peng Liu; Yong-Ming Chai; Bin Dong (Fuel, 2024)

Effect of long-term straw return on organic matter transformation by hydroxyl radical during paddy soil oxygenation - Yanqi Xiao; Wei Peng; Junhong Fu; Yaqi Ning; Hao-jie Cui; Dong Cheng; Na Zhang; Weijun Zhou; Wenjuan Liao (Chemical Engineering Journal, 2024)

Poly(amidoxime)/polyzwitterionic semi-interpenetrating network hydrogel with robust salt-shrinkage resistance for enhanced uranium extraction from seawater - Meng Cao; Guangsheng Luo; Qin Peng; Lushuang Wang; Yue Wang; Shilei Zhao; Hui Wang; Jiacheng Zhang; Yihui Yuan; Ning Wang (Chemical Engineering Journal, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

A new eudesmane-type sesquiterpene and other constituents from Chloranthus henryi hemsl. var. hupehensis (Pamp.) K.F.Wu and their chemotaxonomic significance - Yun-He Zou; Ning Wang; Hui Yang; Yu-Hang Ban; Huan Liu; Hang Liu; Xiao-Xia Wang; Peng-Yu Zhuang (Biochemical Systematics and Ecology, 2024)

Impact of meteorological conditions and reductions in anthropogenic emissions on PM2.5 concentrations in China from 2016 to 2020 - Zhuoying Xu; Zhen Peng; Ning Zhang; Hongnian Liu; Lili Lei; Xingxia Kou (Atmospheric Environment, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

A dual-functional fluorescence probe CDs@ZIF-90 for highly specific detection of Al3+ and Hg2+ in environmental water samples - Liping Peng; Hao Guo; Ning Wu; Mingyue Wang; Yanrui Hao; Borong Ren; Yingfei Hui; Henglong Ren; Wu Yang (Analytica Chimica Acta, 2024)

Relative role of soil nutrients vs. carbon availability on soil carbon mineralization in grassland receiving long-term N addition - Liangchao Jiang; Huanhuan Cheng; Yang Peng; Tianran Sun; Yingzhi Gao; Ruzhen Wang; Yanxia Ma; Junjie Yang; Qiang Yu; Haiyang Zhang; Xingguo Han; Qiushi Ning (Soil and Tillage Research, 2024)

Nitrogen rather than phosphorous addition alters the asymmetric responses of primary productivity to precipitation variability across a precipitation gradient on the northern Tibetan Plateau - Jialuo Yu; Ge Hou; Peili Shi; Ning Zong; Jinlong Peng (Science of The Total Environment, 2024)

Direct measurement of brake and tire wear particles based on real-world driving conditions - Qijun Zhang; Tiange Fang; Zhengyu Men; Ning Wei; Jianfei Peng; Tianqiang Du; Xinfeng Zhang; Yao Ma; Lin Wu; Hongjun Mao (Science of The Total Environment, 2024)

Cobalt oxide/polypyrrole derived Co/NC to activate peroxymonosulfate for benzothiazole degradation: Enhanced conversion efficiency of PMS to free radicals - Juan Miao; Peipei Wang; Xinquan Zhou; Ning Zhang; Ruichang Zhang; Xuefeng Wei; Shuge Peng (Journal of Water Process Engineering, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Size and concentration effects of polythene plastic residues on soil physiochemical traits and maize productivity: A three-year appraisal - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Momena Irum; Fei Mo; Jing Cao; Ning Wang; Hong-Yan Tao; Meng Hao; Song Wang; Kai-Wen Xiao; Fang-Kun Yang; et al. (Journal of Cleaner Production, 2024)

Deterministic assembly processes shaping habitat‐specific glycoside hydrolase composition - Dan‐dan Li; Zheng Zhang; Peng Zhang; Jia‐ning Wang; Ya Liu; Yue‐zhong Li (Global Ecology and Biogeography, 2024)
Aim Glycoside hydrolases (GHs) encoded by prokaryotes play a crucial role in the degradation of carbohydrates, which is a key step in the carbon cycle. However, their global distribution remains poorly understood. Here, we conducted a comprehensive investigation of the global biogeographic patterns of prokaryotic‐encoded GHs. Location Global. Time period Present. Major taxa studied Prokaryotes. Methods We conducted a global survey of GH distribution based on 10,000 samples from the Earth Microbiome Project (EMP) and 17,923 completely sequenced prokaryotic genomes. The samples were retrieved from seven continents, covering all 17 EMP Ontology environments. We evaluated the assembly process and influencing factors of GH functional genes within prokaryotic communities, and analysed the rank abundance distributions (RADs), occupancy frequency distributions (OFDs), and taxonomic sources of GH families across various environments. Results The median number of GH genes per thousand genes encoded by global prokaryotic communities was 9.11 (7.16–11.58), with a higher GH abundance in host‐associated communities than in free‐living communities. The median number of GH families in prokaryotic communities was 105 (86–121), with fewer families but tighter functional connections between families in host‐associated communities compared to free‐living communities. In any environment, the RAD of GH families followed a lognormal model, and their OFD was bimodal, with a strong positive correlation between the two. In addition, most GH families had complex and diverse taxonomic sources across different environments. Main conclusions This study provides a panoramic view of the functional potentials for carbohydrate degradation across prokaryotic communities under diverse environmental conditions. The composition of GHs encoded by prokaryotic communities exhibits clear habitat specificity, which is driven by a combination of biotic and abiotic factors and generated through highly deterministic assembly processes.

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Construction of an allophane-based molecularly imprinted polymer for the efficient removal of antibiotic from aqueous solution - Qiyi Ma; Yanfu Wei; Ning Zhao; Shun Wang; Baifa Zhang; Dong Liu; Peng Yuan (Science of The Total Environment, 2023)

Temperature and pH-dependent nanogel for smart pesticide delivery with enhanced foliar dispersion and washout resistance can effectively control multiple plant diseases - Ning Ma; Hanchen Lin; Like Ning; Xinyue Ji; Fei Wang; Cuie Shi; Peng Xu; Chaoqun You (Journal of Cleaner Production, 2023)

A reinforcement-probability Bayesian approach for strategic bidding and market clearing for renewable energy sources with uncertainty - Liying Yu; Peng Wang; Yang Zhang; Ning Li; Rachid Cherkaoui (Journal of Cleaner Production, 2023)

Sorption behavior and mechanism of U(VI) on Tamusu clay in the presence of U(VI)-CO3 complexes - Xiaoyu Yin; Peng Wu; Shilong Shi; Yufan Zhao; Honghui Li; Feize Li; Jiali Liao; Ning Liu; Yuanyou Yang; Tu Lan (Journal of Environmental Radioactivity, 2023)

Non-targeted analysis and risk assessment of intentionally and non-intentionally added substances migrating from the emerging biodegradable food contact material poly(butylene adipate-co-terephthalate)/modified starch blend film - Jun Lin; Wei-Liang Wu; Ai-Hua Zhong; Yan-Ping Xian; Huai-Ning Zhong; Ben Dong; Ming Liang; Jun-Peng Hu; Yong-Ning Wu; Xing-Fen Yang; Hai-Xia Sui; Quan Zhou (Food Packaging and Shelf Life, 2023)

Performance of 18F-DCFPyL PET/CT in Primary Prostate Cancer Diagnosis, Gleason Grading and D'Amico Classification: A Radiomics-Based Study - Yuekai Li; Fengcai Li; Shaoli Han; Jing Ning; Peng Su; Jianfeng Liu; Lili Qu; Shuai Huang; Shiwei Wang; Xin Li; Xiang Li (Phenomics, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Nano-composite system of traditional Chinese medicine for ocular applications: molecular docking and three-dimensional modeling insight for intelligent drug evaluation - Xinyi Jiao; Xingru Peng; Xin Jin; Ning Liu; Yang Yu; Rui Liu; Zheng Li (Drug Delivery and Translational Research, 2023)

Adsorption-desorption behaviors of ciprofloxacin onto aged polystyrene fragments in aquatic environments - Xiao-Yang Liu; Ning Wang; Long-Yi Lv; Peng-Fei Wang; Wen-Fang Gao; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemosphere, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Long-term satellite observations show continuous increase of vegetation growth enhancement in urban environment - Xi Peng; Shucheng Jiang; Shuguang Liu; Rubén Valbuena; Andy Smith; Yang Zhan; Yi Shi; Ying Ning; Shuailong Feng; Haiqiang Gao; Zhao Wang (Science of The Total Environment, 2023)

Effects of prolonged fluoride exposure on innate immunity, intestinal mechanical, and immune barriers in mice - Yan Wang; Jing Xu; Hang Chen; Yuanbin Shu; Weiqi Peng; Chunxiao Lai; Ruiyang Kong; Ruiyang Lan; Lijing Huang; Jinge Xin; Ning Sun; Xueqin Ni; et al. (Research in Veterinary Science, 2023)

Effects of different paddling motion patterns and flexibility on hydrofoil propulsion performance - Linghui Peng; Yu Zhang; Wenchuan Zhao; Ning Wang; Jun Luo (Ocean Engineering, 2023)

Enhancing catalytic hydrolysis activity of ZnNiAl hydrotalcite-like compounds-derived oxides using rare earth metals - Kunlin Li; Yu Tian; Xie Tang; Peng Gao; Xiao Peng; Ping Ning; Chi Wang; Fei Wang; Xin Sun; Kai Li (Journal of Cleaner Production, 2023)

Adsorption of Li+ by imprinted capacitor deionization — A new method for selective recovery of valuable lithium in acidic solutions - Ning Han; Yifei Li; Haisen Peng; Ruize Gao; Qiongqiong He; Zhenyong Miao; Keji Wan (Desalination, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Morph-genetic biomimetic multiscale porous hydrogels for high-efficient solar evaporation from seawater - Lin Chen; Yue Sun; Chao Ma; Ye Sun; Shuyi Peng; Xingyu Cao; Lang Yang; Chunxin Ma; Hongliang Zhao; Hao Wang; Dong Zhang; Qijie Liu; et al. (Chemical Engineering Journal, 2023)

Preparation of Pickering emulsion hydrogels containing indium(III) extractants and their indium(III) recycling properties - Chen Dong; Jing Gao; Yunting Zhao; Weiqin Zhao; Kegong Ning; Peng Wu; Yongjun He (Clean Technologies and Environmental Policy, 2023)

The impact of urban–rural integration on carbon emissions of rural household energy consumption: evidence from China - Lina Peng; Ning Sun; Zhide Jiang; Zhenyu Yan; Jiapeng Xu (Environment, Development and Sustainability, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Coating CoFe2O4 shell on Fe particles to increase the utilization efficiencies of Fe and peroxymonosulfate for low-cost Fenton-like reactions - Yuqing Sun; Chengbo Ma; Di Wu; Xiaomei Liu; Ning Li; Xiaobin Fan; Yang Li; Guoliang Zhang; Fengbao Zhang; Wenchao Peng (Water Research, 2023)

Potential role of fatty acid desaturase 2 in regulating peach aroma formation - Bin Peng; Zixia Gu; Yifeng Zhou; Youzheng Ning; Huanyu Xu; Gang Li; Yuan Ni; Pengpeng Sun; Zhenqiang Xie; Shengpeng Shi; Adeeba Dark; Zhizhong Song (Postharvest Biology and Technology, 2023)

Polyamidoxime-loaded biochar sphere with high water permeability for fast and effective recovery of uranium from seawater - Yue Wang; Meng Cao; Qin Peng; Lushuang Wang; Xuewen Cao; Lijuan Feng; Yihui Yuan; Ning Wang (Journal of Water Process Engineering, 2023)

Exceptional photo-elimination of antibiotic by a novel Z-scheme heterojunction catalyst composed of nanoscale zero valent iron embedded with carbon quantum dots (CQDs)-black TiO2 - Xi Wu; Xiangyu Wang; Iseult Lynch; Zhiling Guo; Peng Zhang; Lisi Wu; Ping Ning; Nanqi Ren (Journal of Hazardous Materials, 2023)

Porphyrin-based hydrogen-bonded organic framework for visible light driven photocatalytic removal of U(VI) from real low-level radioactive wastewater - Peng Wu; Xiaoyu Yin; Yufan Zhao; Feize Li; Yuanyou Yang; Ning Liu; Jiali Liao; Tu Lan (Journal of Hazardous Materials, 2023)

Green light optimized speed advisory achieves fuel savings and CO2 emission reduction by profoundly impacting driving behavior - Xiaoyang Zhao; Zhenyu Jia; Ning Wei; Dongping Guo; Lu Yao; Jiawei Yin; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Single-atom Pd loaded on nitrogen-doped carbon as a bifunctional catalyst for the electrochemical degradation of 2,4-dichlorophenol - Juan Miao; Jingmin Wang; Zhen Lv; Xiaoying Feng; Ning Zhang; Xinquan Zhou; Hang Xu; Xuefeng Wei; Shuge Peng (Journal of Environmental Chemical Engineering, 2023)

Iron nanoparticles decorated TiO2 hollow microspheres for boosting degradation of tetracycline in a photo-Fenton catalytic system - Hongling Dai; Zhaochen Liu; Li Ou; Yue Shen; Zhihui Ning; Fengping Hu; Xiaoming Peng (Journal of Environmental Chemical Engineering, 2023)

Mobile crowdsensing framework for drive-by-based dense spatial-resolution bridge mode shape identification - Zhen Peng; Jun Li; Hong Hao; Ning Yang (Engineering Structures, 2023)

Pd(II), Pt(II) metallosupramolecular complexes as Single-Site Co-Catalyst for photocatalytic H2 evolution - Xunfu Zhou; Lanzhen Peng; Limei Xu; Jin Luo; Xiaomei Ning; Xiaoqin Zhou; Feng Peng; Xiaosong Zhou (Chemical Engineering Journal, 2023)

Phosphate functionalized silicide for efficient removal of uranium contamination from hypersaline effluents at ultralow dosage - Yaping Jian; Yue Ma; Meng Cao; Shilei Zhao; Qin Peng; Hui Wang; Tao Liu; Yihui Yuan; Ning Wang (Chemical Engineering Journal, 2023)

Intensive adsorption of tetracycline by cobalt oxide quantum dots-loaded mineral carbon - Ning Zhao; Qiyi Ma; Baifa Zhang; Yanfu Wei; Dong Liu; Mengyuan Li; Haoyu Li; Peng Yuan (Bioresource Technology, 2023)

Three-Dimensional Numerical Simulation Research on Discharge Characteristics of Storm-Drain Inlet in Low-Lying Areas - Ke Zhang; Jiake Li; Lizhong Ning; Weifeng Xie; Yafang Li; Zakir ullah; Kai Peng (Water Resources Management, 2023)

Impaired Ventrolateral Periaqueductal Gray-Ventral Tegmental area Pathway Contributes to Chronic Pain-Induced Depression-Like Behavior in Mice - Ming Tatt Lee; Wei-Hao Peng; Cheng-Chun Wu; Hung-Wei Kan; Deng-Wu Wang; Yu-Ning Teng; Yu-Cheng Ho (Molecular Neurobiology, 2023)

Identification of Brassica rapa BrEBF1 homologs and their characterization in cold signaling - Wangze Wu; Haobo Yang; Juan Shen; Peng Xing; Xueyan Han; Yun Dong; Guofan Wu; Sheng Zheng; Kun Gao; Ning Yang; Lina Zhang; Yujun Wu (Journal of Plant Physiology, 2023)

H2O2 activation and contaminants removal in heterogeneous Fenton-like systems - Ning Li; Xu He; Jingya Ye; Haoxi Dai; Wenchao Peng; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Shaobin Wang (Journal of Hazardous Materials, 2023)

Exposure to copper nanoparticles or copper sulfate dysregulated the hypothalamic-pituitary-gonadal axis, gonadal histology, and metabolites in Pelteobagrus fulvidraco - Cheng Zhao; Peng Chu; Xiaodong Tang; Jie Yan; Xiaomen Han; Jie Ji; Xianhui Ning; Kai Zhang; Shaowu Yin; Tao Wang (Journal of Hazardous Materials, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Revealing the mechanism underlying the effects of γ-aminobutyric acid-dioscorin interactions on dioscorin structure and emulsifying properties by molecular dynamic simulations - Yun-long Chen; Hao-nan Nie; Hui Dong; Qi Gao; Xue Peng; Ning Wang; Xueling Chen; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Research International, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Natural sediments activating peroxydisulfate for in situ degradation of antibiotics under anoxic conditions: The critical role of surface-adsorbed and structural Fe(II) - Wenjuan Liao; Wei Peng; Peng Liao; Yanqi Xiao; Wenjing Xie; Ao Qian; Yaqi Ning; Na Zhang; Elias Niyuhire; Hao-Jie Cui (Chemical Engineering Journal, 2023)

Uranium(VI) adsorption from carbonate solutions using cetyltrimethylammonium bromide modified purified-bentonite-MOF composite - Shilong Shi; Jun Liu; Junxiang Shu; Peng Wu; Changsong Zhao; Ning Liu; Tu Lan (Applied Clay Science, 2023)

Low-illumination underwater image enhancement based on non-uniform illumination correction and adaptive artifact elimination - Yu Ning; Yong-Ping Jin; You-Duo Peng; Jian Yan (Frontiers in Marine Science, 2023)
High-quality underwater images are used to extract information for a variety of purposes, including habitat characterization, species monitoring, and behavioral analysis. However, due to the limitation of non-uniform illumination environment and equipment, these images often have the problem of local over- or underexposure due to non-uniform illumination. Conventional methods cannot fully correct for this, and the dark area artifacts generated in the process of enhancing a low-light image cannot be readily fixed. Therefore, we describe a low-illumination underwater image enhancement method based on non-uniform illumination correction and adaptive artifact elimination. First, to eliminate the influence of non-uniform illumination on underwater images, an illumination equalization algorithm based on non-linear guided filtering corrects the non-uniform bright and dark regions of underwater images, and the dark channel prior algorithm and contrast-limited adaptive histogram equalization algorithm are introduced to prevent excessive enhancement of images and generation of dark regions. Then, in order to adaptively eliminate the dark area artifacts generated during the enhancement process, an adaptive multi-scale Retinex color fidelity algorithm with color restore is proposed to improve the color of the image and adaptively eliminate the dark area artifacts of the image. Then, the gray world white balance algorithm is used to adjust the color distortion caused by the attenuation of light. Finally, a multi-scale Retinex model parameter estimation algorithm is proposed to obtain the illumination component and reflection component of the image, and then, the enhanced image is obtained according to the Retinex model. The results show that the proposed method is superior to other algorithms regarding contrast, color restoration, and comprehensive effect, and improves low-illumination image enhancement technology.

Microbial carbon use efficiency in different ecosystems: A meta‐analysis based on a biogeochemical equilibrium model - Peng He; Yuntao Zhang; Qirong Shen; Ning Ling; Zhibiao Nan (Global Change Biology, 2023)
Soil microbial carbon use efficiency (CUE) is a crucial parameter that can be used to evaluate the partitioning of soil carbon (C) between microbial growth and respiration. However, general patterns of microbial CUE among terrestrial ecosystems (e.g., farmland, grassland, and forest) remain controversial. To address this knowledge gap, data from 41 study sites ( n = 197 soil samples) including 58 farmlands, 95 forests, and 44 grasslands were collected and analyzed to estimate microbial CUEs using a biogeochemical equilibrium model. We also evaluated the metabolic limitations of microbial growth using an enzyme vector model and the drivers of CUE across different ecosystems. The CUEs obtained from soils of farmland, forest, and grassland ecosystems were significantly different with means of 0.39, 0.33, and 0.42, respectively, illustrating that grassland soils exhibited higher microbial C sequestration potentials ( p C:P ) and the exoenzymatic ratio of C:nitrogen (N) acquisition activities (EEA C:N ) imparted strong negative effects on soil microbial CUE in grassland and forest ecosystems, respectively. But in farmland soils, EEA C:P exhibited greater positive effects, showing that resource constraints could regulate microbial resource allocation with discriminating patterns across terrestrial ecosystems. Furthermore, mean annual temperature (MAT) rather than mean annual precipitation (MAP) was a critical climate factor affecting CUE, and soil pH as a major factor remained positive to drive the changes in microbial CUE within ecosystems. This research illustrates a conceptual framework of microbial CUEs in terrestrial ecosystems and provides the theoretical evidence to improve soil microbial C sequestration capacity in response to global change.

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Prolonged fluoride exposure induces spatial-memory deficit and hippocampal dysfunction by inhibiting small heat shock protein 22 in mice - Jinge Xin; Bin Zhu; Hesong Wang; Yong Zhang; Ning Sun; Xi Cao; Liqin Zheng; Yanxi Zhou; Jing Fang; Bo Jing; Kangcheng Pan; Yan Zeng; et al. (Journal of Hazardous Materials, 2023)

Rapid reduction of aqueous Cr(VI) by oxalic acid on N-doped lignin charcoal: A significant contribution of structural defects and electronic shuttle effect - Mingxin Li; Hongling Dai; Peng Zhan; Chaoqun Tan; Zhihui Ning; Fengping Hu; Xing Xu; Xiaoming Peng (Journal of Cleaner Production, 2023)

Energy saving and emission reduction effects from the application of green light optimized speed advisory on plug-in hybrid vehicle - Zhenyu Jia; Ning Wei; Jiawei Yin; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

The emerging role of N6-methyladenine RNA methylation in metal ion metabolism and metal-induced carcinogenesis - Yaxu Liang; Huan Wang; Bencheng Wu; Ning Peng; Dongming Yu; Xin Wu; Xiang Zhong (Environmental Pollution, 2023)

Synthesis of cellulose nanofibrils modified with carbon dots-graft-polyacrylamide/ZIF-8 composite hydrogel for simultaneous adsorption and detection of tetracycline - Xuefeng Zhang; Junwen Peng; Huijian Huang; Xinmiao Qi; Ning Zhang; Yuanlan Wang; Jianzheng Qiao; Xin Guo; Yiqiang Wu (Chemical Engineering Journal, 2023)

Sustainable production of flocculant-containing bacterial cellulose composite for removal of PET nano-plastics - Hong Lu; Su Sun; Jidan Sun; Xiongyi Peng; Ning Li; Muhammad Wajid Ullah; Yanbo Zhang; Li Chen; Jiangang Zhou (Chemical Engineering Journal, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Complete genome sequence of a novel chrysovirus infecting Aspergillus terreus - Zunqiu Wu; Xun Tian; Xiang Liu; Jianhong Zhou; Wenfeng Yu; Xiaolan Qi; Jian Peng; Tom Hsiang; Qinrong Wang; Ning Wu; Yinhui Jiang (Archives of Virology, 2023)

RNA-binding protein complex AMG-1/SLRP-1 mediates germline development and spermatogenesis by maintaining mitochondrial homeostasis in Caenorhabditis elegans - Peng Wang; Qiushi Wang; Lianwan Chen; Zheng Cao; Hailian Zhao; Ruibao Su; Ning Wang; Xiaojing Ma; Jin Shan; Xinyan Chen; Qi Zhang; Baochen Du; et al. (Science Bulletin, 2023)

Ultrasonic-assisted self-assembly of a neodymium vanadate and hydroxylated multi-walled carbon nanotubes composite for electrochemical detection of p-nitrophenol - Ya You; Shuang-Ning Li; Jiao Zou; Ya-Nan Xin; Sui Peng; Bo Liu; Xin-Yu Jiang; Jin-Gang Yu (Process Safety and Environmental Protection, 2023)

Surveillance practice and automatic data algorithm of sniffing telemetry for SO2 emissions from ship exhaust in Tianjin Port - Zhaoyu Qi; Shitao Peng; Jianbo Hu; Mengtao Deng; Hongxin Zhao; Guoxin Zhu; Xiang Yu; Ning Su (Journal of Cleaner Production, 2023)

Regulation of inflammatory macrophages by oral mineralized metal-organic framework nanoparticles for the synergistic treatment of ulcerative colitis and liver injury - Chenghu Wu; Ning Lu; Lina Peng; Minghao Lin; Yongheng Bai; Mingqin Lu; Junjie Deng; Jilong Wang (Chemical Engineering Journal, 2023)

Robust optimization for designing air quality monitoring network in coal ports under uncertainty - Bochi Liu; Yun Peng; Wenyuan Wang; Ning Mao (Atmospheric Environment, 2023)

Underwater Color-Cast Image Enhancement by Noise Suppression and Block Effect Elimination - Yu Ning; Yong-Ping Jin; You-Duo Peng; Jian Yan (Journal of Marine Science and Engineering, 2023)
Efficient underwater visual environment perception is the key to realizing the autonomous operation of underwater robots. Because of the complex and diverse underwater environment, the underwater images not only have different degrees of color cast but also produce a lot of noise. Due to the existence of noise in the underwater image and the blocking effect in the process of enhancing the image, the enhanced underwater image is still rough. Therefore, an underwater color-cast image enhancement method based on noise suppression and block effect elimination is proposed in this paper. Firstly, an automatic white balance algorithm for brightness and color balance is designed to correct the color deviation of underwater images and effectively restore the brightness and color of underwater images. Secondly, aiming at the problem of a large amount of noise in underwater images, a noise suppression algorithm for heat conduction matrix in the wavelet domain is proposed, which suppresses image noise and improves the contrast and edge detail information of underwater images. Thirdly, for the block effect existing in the process of enhancing the underwater color-cast image, a block effect elimination algorithm based on compressed domain boundary average is proposed, which eliminates the block effect in the enhancement process and balances the bright area and dark area in the image. Lastly, multi-scale image fusion is performed on the images after color correction, noise suppression, and block effect elimination, and finally, the underwater enhanced image with rich features is obtained. The results show that the proposed method is superior to other algorithms in color correction, contrast, and visibility. It also shows that the proposed method corrects the underwater color-cast image to a certain extent and effectively suppresses the noise and block effect of the underwater image, which provides theoretical support for underwater visual environment perception technology.

ceRNA network mediated by lncRNA-miRNA-mRNA of Pelteobagrus fulvidraco plays a dual function of immunity and lipid metabolism in response to Aeromonas veronii infection - Ye Peng; Bing Han; Kai Zhang; Peng Tang; Yiran Zhang; Jie Ji; Shaowu Yin; Xianhui Ning (Aquaculture, 2023)

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liangfeng Liu; Jianqing Tian; Hongjun Wang; Dan Xue; Xinya Huang; Ning Wu; Meng Wang; Xingliang Xu; Changhui Peng; Yanfen Wang; Huai Chen (Soil Biology and Biochemistry, 2023)

Natural core-based laboratory analysis and comparisons of the mechanical and hydraulic characteristics of the soil skeleton of hydrate reservoirs in the South China Sea - Zhichao Liu; Guocai Gong; Yanjiang Yu; Haoxian Shi; Zhiguo Zeng; Tao Zuo; Zhun Zhang; Li Peng; Dongdong Wang; Fulong Ning (Ocean Engineering, 2023)

Standard environmental evaluation framework reveals environmental benefits of green light optimized speed advisory: A case study on plug-in hybrid electric vehicles - Ning Wei; Zhenyu Jia; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Synthesis of hierarchical porous ceramsites loaded with GIS-P1 zeolite crystals for removal of ammonia nitrogen from aqueous solution - Yuxin Chen; Wensheng Xu; Ning Wang; Shengli An; Jun Peng; Jihua Peng; Xiwen Song (Journal of Environmental Chemical Engineering, 2023)

Poisoning mechanism of different Cd precursors on Fe-Ce/TiO2 catalyst for selective catalytic reduction of NOx with NH3 - Xiaobo Wang; Jiaqi Peng; Yue Wang; Ning Guo; Ting Li; Haijie Li; Dongdong Ren; Keting Gui (Journal of Environmental Chemical Engineering, 2023)

Insights into the enhanced performance of NiCo-LDH modified Pd/NF cathode for electrocatalytic hydrodechlorination - Jingmin Wang; Xuefeng Wei; Peipei Wang; Juan Miao; Ruichang Zhang; Ning Zhang; Xinquan Zhou; Hang Xu; Jun Zhang; Haisheng Li; Shuge Peng (Fuel, 2023)

Identification and functional characterization of caspases in turbot (Scophthalmus maximus) in response to bacterial infection - Tong Cui; Peng Liu; Xuan Chen; Zhe Liu; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Pericarp starch metabolism is associated with caryopsis development and endosperm starch accumulation in common wheat - Jiahui Zhuo; Ke Wang; Ning Wang; Caihong Xing; Da Peng; Xinyu Wang; Ge Qu; Caiyun Kang; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Science, 2023)

Neoarchean SSZ and MOR ultra-/high-pressure ophiolitic mélanges of the Eastern Hebei Complex, North China Craton: Dynamics of an Archean paleo-subduction zone - Wenbin Ning; Timothy Kusky; Lu Wang; Junpeng Wang; Hao Deng; Bo Huang; Jiannan Meng; Ruizhi Wang; Die Hu; Yaying Peng; Zhiyuan Chen; Weikang Zhang (Earth-Science Reviews, 2023)

Blood redistribution preferentially protects vital organs under hypoxic stress in Pelteobagrus vachelli - Jie Li; Yao Li; Xia Liang; Zhiru Yang; Ye Peng; Yiran Zhang; Xianhui Ning; Kai Zhang; Jie Ji; Tao Wang; Guosong Zhang; Shaowu Yin (Aquatic Toxicology, 2023)

Comprehensive analysis of arachidonic acid metabolism-related genes in diagnosis and synovial immune in osteoarthritis: based on bulk and single-cell RNA sequencing data - Bizhi Tu; Run Fang; Zheng Zhu; Guang Chen; Cheng Peng; Rende Ning (Inflammation Research, 2023)

An amphiphilic macrocyclic acylhydrazone dimer: Facile synthesis and dual channel detection and removal of phthalate anion - Zhengning Shu; Shitao Sun; Ning Gu; Zhichao Yang; Yongxin Shang; Yi Yang; Mingyu Xia; Bin Lin; Peng Yang (Analytica Chimica Acta, 2023)

Unravelling ciprofloxacin removal in a nitrifying moving bed biofilm reactor: Biodegradation mechanisms and pathways - Yifeng Xu; Ying Gu; Lai Peng; Ning Wang; Shi Chen; Chuanzhou Liang; Yiwen Liu; Bing-Jie Ni (Chemosphere, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Selective flotation of quartz from feldspar using hydroxypropyl starch as depressant - Ning Sun; Guodong Wang; Peng Ge; Wei Sun; Longhua Xu; Honghu Tang; Li Wang (Minerals Engineering, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

A New Method to Investigate the Size Effect and Anisotropy of Mechanical Properties of Columnar Jointed Rock Mass - Danchen Zhao; Yingjie Xia; Chuanqing Zhang; Ning Liu; Chun’an Tang; Hemant Kumar Singh; Jun Chen; Peng Wang (Rock Mechanics and Rock Engineering, 2023)

Soil amendment with sorbitol and mannitol changes the soil microbial community and its enzymatic activities - Huili Yu; Wei Shao; Guoyi Xu; Ning Xie; Xiaojing Yang; Dengtao Gao; Peng Si (Journal of Soils and Sediments, 2023)

Salinization of coastal saline-alkali soil might enhance H2S release by affecting H2S-related bacterial communities - Yufeng Xin; Honglin Zhang; Yu Wu; Peng Sun; Junqing Xie; Ronghua Zhao; Yujie Zhou; Ning Ding; Xinyi Qu; Qing Huang; Na Liu; Xiaohua Qu (Applied Soil Ecology, 2023)

The effectiveness of eight-years phosphorus reducing inputs on double cropping paddy: Insights into productivity and soil-plant phosphorus trade-off - Ning Su; Guixian Xie; Zhiwei Mao; Qiaorong Li; Tian Chang; Yuping Zhang; Jianwei Peng; Xiangmin Rong; Gongwen Luo (Science of The Total Environment, 2023)

Application of MXene-based materials in Fenton-like systems for organic wastewater treatment: A review - Chuanbin Wang; Jingya Ye; Lan Liang; Xiaoqiang Cui; Lingchao Kong; Ning Li; Zhanjun Cheng; Wenchao Peng; Beibei Yan; Guanyi Chen (Science of The Total Environment, 2023)

Insights into biodegradation of antibiotics during the biofilm-based wastewater treatment processes - Ning Wang; Lai Peng; Ying Gu; Chuanzhou Liang; Robert W.M. Pott; Yifeng Xu (Journal of Cleaner Production, 2023)

Evidence of aircraft activity impact on local air quality: A study in the context of uncommon airport operation - Hao Xu; Kai Xiao; Jun Pan; Qingyan Fu; Xiaodong Wei; Junrui Zhou; Yamei Yu; Xue Hu; Huarui Ren; Jinping Cheng; Shitao Peng; Ningning Hong; et al. (Journal of Environmental Sciences, 2023)

Preparation of floating BiOCl0.6I0.4/ZnO photocatalyst and its inactivation of Microcystis aeruginosa under visible light - Hong Liu; Liuliu Yang; Houwang Chen; Meng Chen; Peng Zhang; Ning Ding (Journal of Environmental Sciences, 2023)

Genome-wide identification and functional characterization of inhibitor of nuclear factor-κB (IκB) kinase (IKK) in turbot (Scophthalmus maximus) - Zhe Liu; Peng Liu; Tong Cui; Xuan Chen; Beibei Wang; Chengbin Gao; Zhongyi Wang; Chao Li; Ning Yang (Fish & Shellfish Immunology, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Contribution of surface plasmonic resonance to enhanced photocatalytic antibacterial performance of graphene-based two-dimensional heterojunction - Zhengao Wang; Guangyu Liu; Wei Chen; Lu Zhang; Zheng Qi; Guanghui Bai; Youzhun Fan; Chengli Liu; Cairong Xiao; Wei Li; Yunbing Chang; Guoyan Liang; et al. (Chemical Engineering Journal, 2023)

The mitigation effect of free ammonia and free nitrous acid on nitrous oxide production from the full-nitrification and partial-nitritation systems - Lai Peng; Huiling Qiu; Shengjun Li; Yifeng Xu; Chuanzhou Liang; Ning Wang; Yiwen Liu; Bing-Jie Ni (Bioresource Technology, 2023)

Research on the Purification Performance of a Floating Island System Treating the Effluent of WWTP Under Different Seasons - Zhao-xu Peng; Ning-qi Niu; Ting-mei Li; Lu-ji Yu; Li-kun Gu; Ming-hui Liu (Water, Air, & Soil Pollution, 2023)

A novel identified circular RNA, circSnap47, promotes heart failure progression via regulation of miR-223-3p/MAPK axis - Yunkai Wang; Hongqiang Wang; Luping Zhang; Jinhua Zhang; Ning Liu; Peng Zhao (Molecular and Cellular Biochemistry, 2023)

Organic matter pore characteristics of over-mature marine black shale: a comparison of organic fractions with different densities - Shitan Ning; Peng Xia; Niuniu Zou; Yi Zhong; Yin Yu; Yuliang Mou; Ke Wang (Frontiers of Earth Science, 2023)

Multi-year trends and interannual variation in ecosystem resource use efficiencies in a young mixedwood plantation in northern China - Chuan Jin; Tianshan Zha; Charles P.-A. Bourque; Peng Liu; Xin Jia; Feng Zhang; Haiqun Yu; Yun Tian; Xinhao Li; Xiaoyu Kang; Xiaonan Guo; Ning Wang (Agricultural and Forest Meteorology, 2023)

Excellent operating temperature window and H2O/SO2 resistances of Fe-Ce catalyst modified by different sulfation strategies for NH3-SCR reaction - Xiaobo Wang; Ning Guo; Jiaqi Peng; Yue Wang; Haijie Li; Dongdong Ren; Keting Gui (Environmental Science and Pollution Research, 2023)

Real-time and accurate detection of citrus in complex scenes based on HPL-YOLOv4 - Lijia Xu; Yihan Wang; Xiaoshi Shi; Zuoliang Tang; Xinyuan Chen; Yuchao Wang; Zhiyong Zou; Peng Huang; Bi Liu; Ning Yang; Zhiwei Lu; Yong He; et al. (Computers and Electronics in Agriculture, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Reactive oxygen species signaling is involved in melatonin-induced reduction of chlorothalonil residue in tomato leaves - Xiaohua Peng; Nannan Wang; Shuangsheng Sun; Lijiahong Geng; Ning Guo; Airong Liu; Shuangchen Chen; Golam Jalal Ahammed (Journal of Hazardous Materials, 2023)

Strategies to improve photocatalytic activity of nanoscale zero valent iron decorated MoS2: Construction of novel S-scheme nanoflower heterojunction with advanced visible-light degradation of tetracycline - Xi Wu; Xiangyu Wang; Iseult Lynch; Zhiling Guo; Peng Zhang; Lisi Wu; Youxue Deng; Yu Xie; Ping Ning; Nanqi Ren (Journal of Cleaner Production, 2023)

Role of interfacial electron transfer reactions on sulfamethoxazole degradation by reduced nontronite activating H2O2 - Hao-Jie Cui; Yaqi Ning; Cong Wu; Wei Peng; Dong Cheng; Lichu Yin; Weijun Zhou; Wenjuan Liao (Journal of Environmental Sciences, 2023)

A review on lignin waste valorization by catalytic pyrolysis: Catalyst, reaction system, and industrial symbiosis mode - Shaoqing Wang; Zhen Wan; Yu Han; Yan Jiao; Zhihe Li; Peng Fu; Ning Li; Andong Zhang; Weiming Yi (Journal of Environmental Chemical Engineering, 2023)

Quantitative determination of d-psicose based on flexible copper film materials and electrochemical scanning methods - Jingyu Zhang; Chengxiang Yong; Xiangchen Li; Runhao Zhu; Yongzhi Lai; Rui Peng; Ruizhi Zhao; Tianxi Yu; Jingyuan Ning; Siyi Xiong; Guohua Hui; Peng Wu (Food Chemistry, 2023)

A two-dimensional semiconductive Cu-S metal-organic framework for broadband microwave absorption - Peng Miao; Ning Qu; Weixing Chen; Tianyi Wang; Weifeng Zhao; Jie Kong (Chemical Engineering Journal, 2023)

The application of a multi-channel sensor network to decompose the local and background sources and quantify their contributions - Xiaoliang Qin; Peng Wei; Meisam Ahmadi Ghadikolaei; Nirmal Kumar Gali; Ya Wang; Zhi Ning (Building and Environment, 2023)

Terpenoids from the roots of Chloranthus henryi Hemsl. var. hupehensis (Pamp.) K. F. Wu and their chemotaxonomic significance - Shuai Liu; Zi-Mo Zhang; Hui Yang; Yun-He Zou; Ning Wang; Peng-Yu Zhuang; Xiao-Xia Wang; Hang Liu (Biochemical Systematics and Ecology, 2023)

Roadside NO2/NOx and primary NO2 from individual vehicles - Peter Brimblecombe; Mengyuan Chu; Chun-Ho Liu; Yunfei Fu; Peng Wei; Zhi Ning (Atmospheric Environment, 2023)

Chronic restraint stress–induced depression-like behavior is mediated by upregulation of melanopsin expression in C57BL/6 mice retina - Yingmei Fu; Shanshan Liu; Yigang Dong; Yixia Gan; Xiaoyun Guo; Hongmei Liu; Qingqing Xu; Ruixue Yuan; Ailing Ning; Wu Hong; Yanmin Peng; Shunying Yu (Psychopharmacology, 2023)

Mitophagy-promoting miR-138-5p promoter demethylation inhibits pyroptosis in sepsis-associated acute lung injury - Fen Liu; Ying Yang; Wei Peng; Ning Zhao; Jiaquan Chen; Zeyao Xu; Yamei Cui; Kejian Qian (Inflammation Research, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Crop types and irrigation regimes as drivers of plastisphere bacterial communities in plastic-mulching croplands of subtropical China - Gongwen Luo; Qirui Zhu; Tuo Jin; Jianwei Peng; Ning Zuo; Huiru Zhang; Mengjiao Geng; Ying Huang; Yongliang Han; Chang Tian; Yong Yang; Jiangchi Fei (Applied Soil Ecology, 2023)

Estimate of the degradation potentials of cellulose, xylan, and chitin across global prokaryotic communities - Dan‐dan Li; Zheng Zhang; Jia‐ning Wang; Peng Zhang; Ya Liu; Yue‐zhong Li (Environmental Microbiology, 2023)
Complex polysaccharides (e.g. cellulose, xylan, and chitin), the most abundant renewable biomass resources available on Earth, are mainly degraded by microorganisms in nature. However, little is known about the global distribution of the enzymes and microorganisms responsible for the degradation of cellulose, xylan, and chitin in natural environments. Through large‐scale alignments between the sequences released by the Earth Microbiome Project and sequenced prokaryotic genomes, we determined that almost all prokaryotic communities have the functional potentials to degrade cellulose, xylan, and chitin. The median abundances of genes encoding putative cellulases, xylanases, and chitinases in global prokaryotic communities are 0.51 (0.17–1.01), 0.24 (0.05–0.57), and 0.33 (0.11–0.71) genes/cell, respectively, and the composition and abundance of these enzyme systems are environmentally varied. The taxonomic sources of the three enzymes are highly diverse within prokaryotic communities, and the main factor influencing the diversity is the community's alpha diversity index rather than gene abundance. Moreover, there are obvious differences in taxonomic sources among different communities, and most genera with degradation potentials are narrowly distributed. In conclusion, our analysis preliminarily depicts a panorama of cellulose‐, xylan‐, and chitin‐degrading enzymatic systems across global prokaryotic communities.

Seasonal variations of heavy metals in seawater and integrated poly-cultured scallop Chlamys farreri in Ailian Bay, northern China - Yanfang Zhao; Jifa Wu; Xuming Kang; Jixing Peng; Haiyan Ding; Jinsong Ning; Xiaofeng Sheng; Zhijun Tan (Marine Pollution Bulletin, 2023)

A robust and 3D-printed solar evaporator based on naturally occurring molecules - Xueqian Zhang; Yu Yan; Ning Li; Peng Yang; Yiyan Yang; Gaigai Duan; Xu Wang; Yuanting Xu; Yiwen Li (Science Bulletin, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Wheat leaf disease identification based on deep learning algorithms - Laixiang Xu; Bingxu Cao; Fengjie Zhao; Shiyuan Ning; Peng Xu; Wenbo Zhang; Xiangguan Hou (Physiological and Molecular Plant Pathology, 2023)

Modeling wave processes in a reef-lagoon-channel system based on a Boussinesq model - Yu Yao; Erman Peng; Weijie Liu; Xiuqi Han; Yicheng Liu; Yue Ning (Ocean Engineering, 2023)

Dissolved organic matter evolution can reflect the maturity of compost: Insight into common composting technology and material composition - Xiaoliang Kong; Gongwen Luo; Binghua Yan; Ning Su; Peng Zeng; Jialu Kang; Yuping Zhang; Guixian Xie (Journal of Environmental Management, 2023)

Electrocatalytic hydrogenation of phenol by active sites on Pt-decorated shrimp shell biochar catalysts: Performance and internal mechanism - Xukai Lu; Jun Wang; Wenchao Peng; Ning Li; Lan Liang; Zhanjun Cheng; Beibei Yan; Gaixiu Yang; Guanyi Chen (Fuel, 2023)

Industrial park electric power load pattern recognition: An ensemble clustering-based framework - Kaile Zhou; Ning Peng; Dingding Hu; Zhen Shao (Energy and Buildings, 2023)

Effects of a novel hybrid polymer material on the hydro-mechanical behavior of subgrade silts considering freeze-thaw cycles - Xiao-ning Zhang; Xin-zhuang Cui; Lu-qiang Ding; Ji-yuan Luan; Yi-lin Wang; Peng Jiang; Jian-wen Hao (Cold Regions Science and Technology, 2023)

C1-based biomanufacturing: Advances, challenges and perspectives - Xueqin Lv; Wenwen Yu; Chenyang Zhang; Peng Ning; Jianghua Li; Yanfeng Liu; Guocheng Du; Long Liu (Bioresource Technology, 2023)

Responses of seven wetlands carbon sources and sinks to permafrost degradation in Northeast China - Lidong Han; Changcheng Mu; Ning Jiang; Zhongqi Shen; Yihui Chang; Li Hao; Wenhong Peng (Journal of Soils and Sediments, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Fabrication of a core-shell porphyrin-based magnetic covalent organic framework for effective extraction of PCPs in a wide polarity range - Tao Ning; Siyuan Di; Zihan Li; Haokun Zhang; Zhangdi Peng; Hucheng Yang; Pin Chen; Yue Bao; Yixin Zhai; Shukui Zhu (Analytica Chimica Acta, 2023)

Development of the dried blood spot preparation protocol for comprehensive evaluation of the hematocrit effect - Chih-Ning Cheng; Yu-Fong Peng; Ju-Yu Chen; Guan-Yuan Chen; Te-I Weng; Ching-Hua Kuo (Analytica Chimica Acta, 2023)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Correlation and causal impact on air quality of inter zones in Beijing based on big data - Caixiao Zhang; Zhen Peng; Ruilian Qiu; Ning Zhao (Environment, Development and Sustainability, 2022)

Three pairs of sesquiterpene enantiomers from Chloranthus multistachys pei - Wei-ming Huang; Fang-you Chen; Yu-ting Bian; Tian-jiao Ning; Zhi-chao Chen; Peng-cheng Shuang; Yong-ming Luo (Natural Product Research, 2022)

Zinc in cereal grains: Concentration, distribution, speciation, bioavailability, and barriers to transport from roots to grains in wheat - Zhao Aiqing; Liansheng Zhang; Peng Ning; Qin Chen; Bini Wang; Fuxin Zhang; Xingbin Yang; Youlin Zhang (Critical Reviews in Food Science and Nutrition, 2022)

Root traits and soil nutrient and carbon availability drive soil microbial diversity and composition in a northern temperate forest - Bitao Liu; Fei Han; Peng Ning; Hongbo Li; Zed Rengel (Plant and Soil, 2022)

Genome-Wide Association and Expression Analysis Revealed the Candidate Variants and Molecular Underpinnings of Cold-Stress Response in Large Yellow Croaker - Ning Suo; Yidi Wu; Zhixiong Zhou; Qian He; Huaqiang Bai; Huanling Lin; Qiaozhen Ke; Peng Xu (Marine Biotechnology, 2022)

Dominant modes of summer wet bulb temperature in China - Guicai Ning; Ming Luo; Shigong Wang; Zhen Liu; Peng Wang; Yuanjian Yang (Climate Dynamics, 2022)

Anthocyanin composition and nutritional properties of a blue-grained wheat-Triticum boeoticum substitution line - Xin Liu; Minghu Zhang; Dinghao Wang; Ting Peng; Xiaojuan Liu; Ming Hao; Lin Huang; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Cereal Research Communications, 2022)

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Differential root response of maize inbred seedlings to root growth restriction and phosphorus availability - Yu Zhang; Peng Ning (Biologia, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Understanding the Sources of Heavy Metal Pollution in Ambient Air of Neighboring a Solid Waste Landfill Site - Umangi H. Mehta; Daya S. Kaul; Dane Westerdahl; Zhi Ning; Kai Zhang; Li Sun; Peng Wei; Hardik H. Gajjar; Jai D. Jeyaraman; Mansi V. Patel; Rutu R. Joshi (Aerosol Science and Engineering, 2022)

Determination of fluoroquinolones in chicken muscle by molecularly imprinted graphitic carbon nitride-based solid-phase extraction and ultra-performance liquid chromatography - Su Han Wang; Ning Ma; Xiao Huan Zang; Shuai Hua Zhang; Jian Ping Wang; Ning Peng Wu (Food Additives & Contaminants: Part A, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

Study on the degradation mechanism of 2-amino-4-acetaminoanisole from wastewater by nano-Fe3O4-catalyzed Fenton system - Hong Liu; Peng Zhang; Houwang Chen; Ning Ding; Jing Ni (Environmental Science and Pollution Research, 2022)

Possible role of the CYC2c gene in the cornflower-like ray floret phenotype of Gaillardia cultivars - Peng Sun; Ying Bao; Yingjie Zhu; Ning Huang; Xiangrong Wang; Zhenyang Wu (Journal of Plant Research, 2022)

Crucial roles of a novel exoskeletal‐derived lectin in innate immunity of the oriental river prawn, Macrobrachium nipponense - Juan Du; Kaidi Yue; Yanxin Peng; Qianji Ning (Journal of Fish Diseases, 2022)
As important pattern recognition receptors (PRRs), C‐type lectins play crucial roles in the crustacean innate immune system. In this study, a novel C‐type lectin, designated as Mn Lec1, was obtained from the exoskeleton of the oriental river prawn Macrobrachium nipponense for the first time. The full‐length cDNA of Mn Lec1 was 1329 bp with an open reading frame of 774 bp. The predicted Mn Lec1 protein contains a single carbohydrate‐recognition domain with an EPN/LND motif and one Ca 2+ binding site‐2. Mn Lec1 transcripts were widely detected in the tested tissues of M. nipponense and significantly up‐regulated after Aeromonas hydrophila challenge. The recombinant Mn Lec1 protein was found to have a wide spectrum of binding activities towards various microorganisms, agglutinate two kinds of Gram‐negative bacteria ( Escherichia coli and A. hydrophila ) in a Ca 2+ ‐independent manner. What's more, the survivability of prawns was significantly down‐regulated after RNAi of Mn Lec1 when infected with A. hydrophila . Collectively, these findings suggest that Mn Lec1 from the exoskeleton might function as a PRR and play a crucial role in immune defense against invading pathogens in M. nipponense .

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

Correction to: Construction of nitrogen vacant g-C3N4 nanosheet supported Ag3PO4 nanoparticle Z-scheme photocatalyst for improved visible-light photocatalytic activity - Xiuxiu Zhang; Guiyun Yi; Peng Li; Xiaomeng Zheng; Xuhang Shen; Kunlei Ning; Lunjian Chen; Chuanxiang Zhang; Yulong Zhang; Qi Sun (Environmental Science and Pollution Research, 2022)

Construction of nitrogen vacant g-C3N4 nanosheet supported Ag3PO4 nanoparticle Z-scheme photocatalyst for improved visible-light photocatalytic activity - Xiuxiu Zhang; Guiyun Yi; Peng Li; Xiaomeng Zheng; Xuhang Shen; Kunlei Ning; Lunjian Chen; Chuanxiang Zhang; Yulong Zhang; Qi Sun (Environmental Science and Pollution Research, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Laboratory test and numerical simulations for 3D printed irregular columnar jointed rock masses under biaxial compression - Danchen Zhao; Yingjie Xia; Chuanqing Zhang; Hui Zhou; Chun’an Tang; Ning Liu; Jun Chen; Peng Wang; Chenglong Wang (Bulletin of Engineering Geology and the Environment, 2022)

Correction to: Physalin A induces G2/M phase cell cycle arrest in human non-small cell lung cancer cells: involvement of the p38 MAPK/ROS pathway - Ning Kang; Jun-feng Jian; Shi-jie Cao; Qiang Zhang; Yi-wei Mao; Yi-yuan Huang; Yan-fei Peng; Feng Qiu; Xiu-mei Gao (Molecular and Cellular Biochemistry, 2022)

FNC inhibits non-small cell lung cancer by activating the mitochondrial apoptosis pathway - Xiang Jing; Shuai Niu; Yi Liang; Huiping Chen; Ning Wang; Youmei Peng; Fang Ma; Wanying Yue; Qingduan Wang; Junbiao Chang; Yi Zhang; Yan Zhang (Genes & Genomics, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Ichthyoplankton Species Composition and Assemblages From the Estuary to the Hukou Section of the Changjiang River - Di-an Fang; Xiang-ping Xue; Dong-po Xu; Xiao-hao Wang; Ning-ze Sun; Bai-dong Zhang; Peng Ren (Frontiers in Marine Science, 2021)
Estuary river–lake (ERL) complex is critical for the development of ichthyoplankton, which plays an essential role in the breeding, nursing, and recruitment of freshwater fish species. In this study, different ERL sections were selected to investigate the ichthyoplankton assemblage from the Changjiang River estuary to its Hukou section between May 2018 and August 2020. During the study period, fish larvae of 40, 35, 54, and 46 fish species were sampled in the Rugao (RG), Nanjing (NJ) (nearby estuary), Anqing (AQ), and Hukou (HK) (connected river–lake) sections in the Changjiang River, respectively. Results on ichthyoplankton surveys revealed fluctuating assemblage patterns in the different river sections; larval fish species composition presented ecological habitat-dependent characteristics, which supported the importance of ERL complex for ichthyoplankton development. Furthermore, the density of fish larvae was negatively correlated with water transparency but positively correlated with water temperature, the daily rate of water level increase, and runoff in the limitative range. A generalized additive model analysis indicated that the hydrological factors significantly affecting larval fish abundance are water temperature, transparency, the daily rate of water level increase, and runoff ( p < 0.05). These results also indicated that river estuaries and river–lake connected complexes are essential for ichthyoplankton recruitment and migration. In combination with the historical record, ichthyoplankton assemblage’s patterns in the Changjiang River lower reaches were preliminarily elucidated, although additional works are needed such as assessing effects on their survival and recruitment.

Retraction Note: An auxiliary training system for swimming in coastal areas based on remote sensing images and virtual simulation technology - Peng Hou; Yuwen Ning; Yaowei Song (Arabian Journal of Geosciences, 2021)

Carbon limitation overrides acidification in mediating soil microbial activity to nitrogen enrichment in a temperate grassland - Qiushi Ning; Stephan Hättenschwiler; Xiaotao Lü; Paul Kardol; Yunhai Zhang; Cunzheng Wei; Chengyuan Xu; Jianhui Huang; Ang Li; Junjie Yang; Jing Wang; Yang Peng; et al. (Global Change Biology, 2021)
Higher ecosystem nitrogen (N) inputs resulting from human activities often suppress soil microbial biomass and respiration, thereby altering biogeochemical cycling. Soil acidification and carbon (C) limitation may drive these microbial responses, yet their relative importance remains elusive, which limits our understanding of the longer term effects of increasing N inputs. In a field experiment with continuous N addition at seven different rates from 0 to 50 g N m −2 year −1 over 6 years in a temperate grassland of Inner Mongolia, China, we examined the responses of soil microbial biomass and respiration to changes in soil acidity and C availability by adding lime and/or glucose to soil samples. Soil microbial biomass and respiration did only weakly respond to increasing soil pH, but increased strongly in response to higher C availability with increasing N addition rates. Soil net N immobilization increased in response to glucose addition, and soil microbial biomass increased at higher rates than microbial respiration along the gradient of previous N addition rates, both suggesting increasingly reinforced microbial C limitation with increasing N addition. Our results provide clear evidence for strong N‐induced microbial C limitation, but only little support for soil acidity effects within the initial pH range of 4.73–7.86 covered by our study. Field data support this conclusion by showing reduced plant C allocation belowground in response to N addition, resulting in soil microbial C starvation over the long term. In conclusion, soil microbial biomass and respiration under N addition were strongly dependent on C availability, most likely originating from plant belowground C inputs, and was much less affected by changes in soil pH. Our data help clarify a long‐standing debate about how increasing N input rates affect soil microbial biomass and respiration, and improve the mechanistic understanding of the linkages between ecosystem N enrichment and C cycling.

Correction to: Variations of methane stable isotopic values from an Alpine peatland on the eastern Qinghai-Tibetan Plateau - Qian Guo; Haijun Peng; Bing Hong; Hu Yao; Yongxuan Zhu; Hanwei Ding; Ning An; Yetang Hong (Acta Geochimica, 2021)

Identification of a recessive gene YrZ15-1370 conferring adult plant resistance to stripe rust in wheat-Triticum boeoticum introgression line - Minghu Zhang; Xin Liu; Ting Peng; Dinghao Wang; Dongyu Liang; Hongyu Li; Ming Hao; Shunzong Ning; Zhongwei Yuan; Bo Jiang; Xuejiao Chen; Xue Chen; et al. (Theoretical and Applied Genetics, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Surface Ligand Valency and Immunoliposome Binding: when More Is Not Always Better - Huimin Li; Jiaxing Di; Baowei Peng; Yuhong Xu; Ning Zhang (Pharmaceutical Research, 2021)

Geochemical characteristics and its geological application of over-mature Longmaxi shale gas in the northern Guizhou area, China - Yi Zhong; Peng Xia; Shitan Ning; Yong Fu; Qingguang Li; Yin Yu (Arabian Journal of Geosciences, 2021)

A novel transcription factor negatively regulates antioxidant response, cell wall integrity and virulence in the fungal insect pathogen, Beauveria bassiana - Xin Zhao; Tingying Luo; Shuaishuai Huang; Ning Peng; Ying Yin; Zhibing Luo; Yongjun Zhang (Environmental Microbiology, 2021)
Summary Genomic data have identified a class of fungal specific transcription factors (FsTFs) that are thought to regulate unique aspects of fungal gene expression, although the functions of many of these proteins remain unknown. Here, a novel FsTF (BbStf1), which features a leucine zipper dimerization domain and a fungal transcription factor regulatory middle homology region, was characterized in Beauveria bassiana , a filamentous insect fungal pathogen. Transcriptional activation and nuclear localization were experimentally confirmed for BbStf1. Disruption of Bbstf1 resulted in increased tolerance to oxidative stress and cell wall perturbation, accompanied by increased peroxidase (POD) and superoxide dismutase (SOD) activities and ratio of reduced/oxidized glutathione (GSH/GSSG), and by thickened cell wall and altered composition. Gene expression profile analysis revealed that transcription patterns of antioxidant enzyme and cell wall integrity‐involved genes were altered in the ∆ Bbstf1 , including some BbStf1‐targeted genes clarified with evidence. The ∆ Bbstf1 strain displayed greater virulence to Galleria mellonella in the bioassays through both topical infection and intrahaemocoel injection due to more rapid proliferation in the haemocoel as compared to the wild‐type strain. Altogether, BbStf1 acts as a negative regulator of antioxidant response, cell wall integrity and virulence in B. bassiana .

Size-Dependent Absorption through Stratum Corneum by Drug-Loaded Liposomes - Junye Liu; Anjie Zheng; Baowei Peng; Yuhong Xu; Ning Zhang (Pharmaceutical Research, 2021)

Variations of methane stable isotopic values from an Alpine peatland on the eastern Qinghai-Tibetan Plateau - Qian Guo; Haijun Peng; Bing Hong; Hu Yao; Yongxuan Zhu; Hanwei Ding; Ning An; Yetang Hong (Acta Geochimica, 2021)

Development of a molecularly imprinted microspheres-based microplate fluorescence method for detection of amantadine and rimantadine in chicken - Teng Zhang; Lei Zhang; Ju Xiang Liu; Jian Ping Wang; Ning Peng Wu (Food Additives & Contaminants: Part A, 2021)

Actirhodobacter atriluteus gen. nov., sp. nov., isolated from the surface water of the Yellow Sea - Hua-Peng Xue; Dao-Feng Zhang; Lin Xu; Xiang-Ning Wang; Ai-Hua Zhang; Jian-Ke Huang; Chuang Liu (Antonie van Leeuwenhoek, 2021)

Inversion of 3D velocity and anisotropy of near surfaces based on an azimuth-dependent dispersion curve inversion method - Ning-Bo Jiang; Chun-Tao Liang; Wen Peng (Applied Geophysics, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

ZnO nanorods/Fe3O4-graphene oxide/metal-organic framework nanocomposite: recyclable and robust photocatalyst for degradation of pharmaceutical pollutants - Li Chen; Jun Peng; Fangqi Wang; Donghao Liu; Wenrong Ma; Jinmeng Zhang; Wenqing Hu; Ning Li; Pierre Dramou; Hua He (Environmental Science and Pollution Research, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

RETRACTED ARTICLE: An auxiliary training system for swimming in coastal areas based on remote sensing images and virtual simulation technology - Peng Hou; Yuwen Ning; Yaowei Song (Arabian Journal of Geosciences, 2021)

Upregulation of miR-144-3p protects myocardial function from ischemia–reperfusion injury through inhibition of TMEM16A Ca2+-activated chloride channel - Guoxun Yang; Xiao Tang; Ling Tan; Danpeng Nong; Peng Yang; Haien Ning (Human Cell, 2021)

Regulation of Cued Fear Expression via Corticotropin-Releasing-Factor Neurons in the Ventral Anteromedial Thalamic Nucleus - Yin Lv; Peng Chen; Qing-Hong Shan; Xin-Ya Qin; Xiu-Hong Qi; Jiang-Ning Zhou (Neuroscience Bulletin, 2021)

Theory and full-scale simulation testing of the mechanical properties of anchors under a variable lateral pressure coefficient - Tuo Wang; Jucai Chang; Zhiqiang Yin; Peng Gong; Wenbao Shi; Ning Li (Arabian Journal of Geosciences, 2021)

Potential Effect of Bioturbation by Burrowing Crabs on Sediment Parameters in Coastal Salt Marshes - Tian Xie; Peng Dou; Shanze Li; Baoshan Cui; Junhong Bai; Qing Wang; Zhonghua Ning (Wetlands, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Identification of Core Genes and Pathways in Medulloblastoma by Integrated Bioinformatics Analysis - Yuduo Guo; Peng Huang; Weihai Ning; Hongwei Zhang; Chunjiang Yu (Journal of Molecular Neuroscience, 2020)

A novel system to rapidly detect protein–protein interactions (PPIs) based on fluorescence co-localization - Nan Hu; Zhan-Qi Dong; Ting-Ting Chen; Ning Zheng; Qin Wu; Peng Chen; Cheng Lu; Min-Hui Pan (Biotechnology Letters, 2020)

Erratum to: Low dose of hydroxychloroquine reduces fatality of critically ill patients with COVID-19 - Bo Yu; Chenze Li; Peng Chen; Ning Zhou; Luyun Wang; Jia Li; Hualiang Jiang; Dao-Wen Wang (Science China Life Sciences, 2020)

Low dose of hydroxychloroquine reduces fatality of critically ill patients with COVID-19 - Bo Yu; Chenze Li; Peng Chen; Ning Zhou; Luyun Wang; Jia Li; Hualiang Jiang; Dao-Wen Wang (Science China Life Sciences, 2020)

Stabilization of soil aggregate and organic matter under the application of three organic resources and biochar-based compound fertilizer - Kun Chen; Jing Peng; Jun Li; Qian Yang; Xiumei Zhan; Ning Liu; Xiaori Han (Journal of Soils and Sediments, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

Causes of slowing‐down seasonal CO 2 amplitude at Mauna Loa - Kai Wang; Yilong Wang; Xuhui Wang; Yue He; Xiangyi Li; Ralph F. Keeling; Philippe Ciais; Martin Heimann; Shushi Peng; Frédéric Chevallier; Pierre Friedlingstein; Stephen Sitch; et al. (Global Change Biology, 2020)
Changing amplitude of the seasonal cycle of atmospheric CO 2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO 2 record, shows an increasing SCA before the 1980s ( p 2 fertilization. This challenges the view that CO 2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO 2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs.

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Spatial Distribution and Source of Inorganic Elements in PM2.5 During a Typical Winter Haze Episode in Guilin, China - Tengfa Long; Bin Peng; Zhihui Yang; Chongjian Tang; Ziwei Ye; Ning Zhao; Chunqiang Chen (Archives of Environmental Contamination and Toxicology, 2020)

Phytochemical constituents of the pericarps of Illicium difengpi and their anti-inflammatory activity - De-Sheng Ning; Yu-Xia Fu; Li-Yan Peng; Hui Tang; Lian-Chun Li; Xing-De Wu; Yu-Song Huang; Zheng-Hong Pan (Natural Product Research, 2020)

Phenotype changes of cyanobacterial and microbial distribution characteristics of surface sediments in different periods of cyanobacterial blooms in Taihu Lake - Weizhen Zhang; Peng Gu; Wenjie Zhu; Ning Wang; Mengqi Jiang; Jian He; Zheng Zheng (Aquatic Ecology, 2020)

A new coumarin from Murraya alata activates TRPV1 channel - Hai-Ning Lyu; Ning-Ning Wei; Peng-Fei Tu; KeWei Wang; Yong Jiang (Natural Product Research, 2020)

A multiple reverse transcription PCR assay for simultaneous detection of four main viruses in kiwifruit - Qiding Peng; Long Qiu; Ting Yang; Jiachen Ning; Qianyi Xu; Jiahong Dong; Dehui Xi (European Journal of Plant Pathology, 2020)

Distribution and risk assessment of phthalates in water and sediment of the Pearl River Delta - Zhang Weizhen; Zheng Xiaowei; Gu Peng; Wang Ning; Lai Zini; He Jian; Zheng Zheng (Environmental Science and Pollution Research, 2020)

Spatial Distribution and Formation Mechanism of Water-soluble Inorganic Ions in PM2.5 During a Typical Winter Haze Episode in Guilin, China - Tengfa Long; Bin Peng; Zhihui Yang; Cynthia Sabrine Ishimwe; Chongjian Tang; Ning Zhao; Hong Lin; Kai Zhong; Shan Zhong (Archives of Environmental Contamination and Toxicology, 2020)

Enhanced adsorption of hydrophobic organic contaminants by high surface area porous graphene - Lixuan Ma; Kai Li; Chi Wang; Bo Liu; Hongbo Peng; Yi Mei; Ping Ning (Environmental Science and Pollution Research, 2020)

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Genomic characterization of a novel astrovirus identified in Amur tigers from a zoo in China - Hui-Hui Zhang; Qi-Guan Qiu; Shu-Jing Liu; Wen-Qin Hu; Jie-Yu Li; Tian-Ning Liu; You-Song Peng; Xing-Yi Ge; Chao-Ting Xiao (Archives of Virology, 2019)

Optimizing the wavefield storage strategy in reflection-acoustic logging reverse-time migration - Yu-Sheng Li; Ning Li; Ye Yuan; Hong-Liang Wu; Zhou Feng; Peng Liu (Applied Geophysics, 2019)

Suitable Reference Genes/miRNAs for qRT-PCR Normalization of Expression Analysis in Sugarcane Under Sorghum mosaic virus Infection - Hui Ling; Ning Huang; Liping Xu; Qiong Peng; Feng Liu; Yuting Yang; Youxiong Que (Sugar Tech, 2019)

Cosleeping and sleep problems in children: a systematic review and meta-analysis - Xiaojing Peng; Gangxuan Yuan; Ning Ma (Sleep and Biological Rhythms, 2019)

Warming effects on soil respiration in moss-dominated crusts in the Tengger Desert, northern China - Chao Guan; Xinrong Li; Ning Chen; Peng Zhang; Changming Zhao (Plant and Soil, 2019)

Allocating assistance after a catastrophe based on the dynamic assessment of indirect economic losses - Zhengtao Zhang; Ning Li; Hong Xu; Jieling Feng; Xi Chen; Chao Gao; Peng Zhang (Natural Hazards, 2019)

The effects of temperature on human mortality in a Chinese city: burden of disease calculation, attributable risk exploration, and vulnerability identification - Xin Xu; Zuosen Chen; Xiyuan Huo; Chunping Wang; Ning Li; Xianfeng Meng; Qiang Wang; Qiyong Liu; Peng Bi; Jing Li (International Journal of Biometeorology, 2019)

Ligustroflavone reduces necroptosis in rat brain after ischemic stroke through targeting RIPK1/RIPK3/MLKL pathway - Yi-Yue Zhang; Wei-Ning Liu; Yue-Qi Li; Xiao-Jie Zhang; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Quantifying the carbon source of pedogenic calcite veins in weathered limestone: implications for the terrestrial carbon cycle - Lin Zou; Lin Dong; Meng Ning; Kangjun Huang; Yongbo Peng; Shujian Qin; Honglin Yuan; Bing Shen (Acta Geochimica, 2019)

Dietary intake assessment of caramel colours and their processing by-products 4-methylimidazole and 2-acetyl-4-tetrahydroxy-butylimidazole for the Chinese population - Jiang Liang; Pei Cao; Xiaodan Wang; Peng Gao; Haibin Xu; Ning Ma (Food Additives & Contaminants: Part A, 2019)

Paternal effects on fatty acid composition of tree peony seed oil - Qing Hao; Li-Ping Peng; Zhen Li; Si-Qi Men; Ning-Ning Tong; Qing-Yan Shu; Zheng-An Liu (Euphytica, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Hydrogen Sulfide Inhibits Formaldehyde-Induced Senescence in HT-22 Cells via Upregulation of Leptin Signaling - Wei-Wen Zhu; Min Ning; Yi-Zhu Peng; Yi-Yun Tang; Xuan Kang; Ke-Bin Zhan; Wei Zou; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2019)

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)

Phosphorus recovery from freeze-microwave pretreated sludge supernatant by phosphate sedimentation - Xiao Chang; Wei Zeng; Ning Li; Shuaishuai Li; Yongzhen Peng (Environmental Science and Pollution Research, 2019)

FMST: an Automatic Neuron Tracing Method Based on Fast Marching and Minimum Spanning Tree - Jian Yang; Ming Hao; Xiaoyang Liu; Zhijiang Wan; Ning Zhong; Hanchuan Peng (Neuroinformatics, 2019)

Candida glabrata-Induced Refractory Infectious Arthritis: A Case Report and Literature Review - Shu Chen; Yi Chen; Yi-qin Zhou; Ning Liu; Rong Zhou; Jin-hui Peng; Qi-rong Qian (Mycopathologia, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Influence of rock fractures on the amplitude of dipole-source reflected shear wave - Hao Wang; Ning Li; Cai-Zhi Wang; Hong-Liang Wu; Peng Liu; Yu-Sheng Li; Ying-Ming Liu; Ye Yuan (Applied Geophysics, 2019)

Chemical constituents from Alisma plantago - aquatica subsp . orientale (Sam.) Sam and their anti-inflammatory and antioxidant activities - Xin-Yu Zhao; Gang Wang; Yan Wang; Xiang-Ge Tian; Jian-Chao Zhao; Xiao-Kui Huo; Cheng-Peng Sun; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Xun Wang (Natural Product Research, 2018)

Transcriptional Insights into the Sugarcane-Sorghum mosaic virus Interaction - Hui Ling; Ning Huang; Qibing Wu; Yachun Su; Qiong Peng; Waqar Ahmed; Shiwu Gao; Weihua Su; Youxiong Que; Liping Xu (Tropical Plant Biology, 2018)

Histamine Excites Rat GABAergic Ventral Pallidum Neurons via Co-activation of H1 and H2 Receptors - Miao-Jin Ji; Xiao-Yang Zhang; Xiao-Chun Peng; Yang-Xun Zhang; Zi Chen; Lei Yu; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2018)

Fluid evolution and ore genesis of the Dalingshang deposit, Dahutang W-Cu ore field, northern Jiangxi Province, South China - Ning-Jun Peng; Shao-Yong Jiang; Suo-Fei Xiong; Dao-Hui Pi (Mineralium Deposita, 2018)

The relationship between extreme temperature and emergency incidences: a time series analysis in Shenzhen, China - Yinsheng Guo; Yue Ma; Jiajia Ji; Ning Liu; Guohong Zhou; Daokui Fang; Guangwen Huang; Tao Lan; Chaoqiong Peng; Shuyuan Yu (Environmental Science and Pollution Research, 2018)

The relationship between drought activity and vegetation cover in Northwest China from 1982 to 2013 - Yelin Jiang; Ranghui Wang; Qing Peng; Xiaoquan Wu; Husen Ning; Cheng Li (Natural Hazards, 2018)

Optimization of preparation of monolithic carbon foam from rice husk char for benzene leakage emergency - Xiao Peng; Fengnan Guo; Xuan Zhang; Ning Shi; Yan Wu (Environmental Science and Pollution Research, 2018)

Novel alternatively spliced isoforms of MEF2A and their mRNA expression patterns in pigs - Xiao Hong Guo; Qi Zhang; Meng Li; Peng Fei Gao; Guo Qing Cao; Zhi Min Cheng; Ning Fang Zhang; Bao Yu Le; Jian Feng Liu; Xiao Jun Liu; Bu Gao Li (Journal of Genetics, 2018)

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Risk prediction in infective endocarditis by modified MELD-XI score - Peng-cheng He; Xue-biao Wei; Si-ni Luo; Xiao-lan Chen; Zu-hui Ke; Dan-qing Yu; Ji-yan Chen; Yuan-hui Liu; Ning Tan (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Antibacterial and anti-biofilm activity of the lipid extract from Mantidis ootheca on Pseudomonas aeruginosa - Wen-dong Wang; Nan-nan Zhang; Warren Chanda; Min Liu; Syed Riaz ud Din; Yun-peng Diao; Lei Liu; Jing Cao; Xiao-li Wang; Xing-yun Li; An-hong Ning; Min Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2018)

Holocene peatland development and carbon stock of Zoige peatlands, Tibetan Plateau: a modeling approach - Xinwei Liu; Huai Chen; Qiuan Zhu; Jianghua Wu; Steve Frolking; Dan Zhu; Mei Wang; Ning Wu; Changhui Peng; Yixin He (Journal of Soils and Sediments, 2018)

Permineralized osmundaceous and gleicheniaceous ferns from the Jurassic of Inner Mongolia, NE China - Ning Tian; Yong-Dong Wang; Wu Zhang; Shao-Lin Zheng; Zhi-Peng Zhu; Zhong-Jian Liu (Palaeobiodiversity and Palaeoenvironments, 2018)

Hsp90 regulation affects the treatment of glucocorticoid for pancreatitis-induced lung injury - Yan Zhao; Ren-Ping Xiong; Xing Chen; Ping Li; Ya-Lei Ning; Nan Yang; Yan Peng; Yu-Lin Jiang; Yuan-Guo Zhou (Molecular and Cellular Biochemistry, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Treatment of PAH-contaminated soil using cement-activated persulfate - Fujun Ma; Qian Zhang; Bin Wu; Changsheng Peng; Ning Li; Fasheng Li; Qingbao Gu (Environmental Science and Pollution Research, 2018)

Alterations in soil fungal community composition and network assemblage structure by different long-term fertilization regimes are correlated to the soil ionome - Chao Xue; C. Ryan Penton; Chen Zhu; Huan Chen; Yinghua Duan; Chang Peng; Shiwei Guo; Ning Ling; Qirong Shen (Biology and Fertility of Soils, 2018)

Mevastatin promotes neuronal survival against Aβ-induced neurotoxicity through AMPK activation - Edy Kornelius; Hsin-Hua Li; Chiung-Huei Peng; Hui-Wen Hsiao; Yi-Sun Yang; Chien-Ning Huang; Chih-Li Lin (Metabolic Brain Disease, 2017)

Development and trait evaluation of chromosome single-segment substitution lines of O. meridionalis in the background of O. sativa - Ning He; Rouxian Wu; Xiaoping Pan; Liping Peng; Kang Sun; Tuo Zou; Haitao Zhu; Ruizhen Zeng; Ziqiang Liu; Guifu Liu; Shaokui Wang; Guiquan Zhang; et al. (Euphytica, 2017)

Diallyl trisulfide inhibits proliferation, invasion and angiogenesis of glioma cells by inactivating Wnt/β-catenin signaling - Qingxia Tao; Cuiying Wu; Ruxiang Xu; Lijun Niu; Jiazhen Qin; Ning Liu; Peng Zhang; Chong Wang (Cell and Tissue Research, 2017)

Mechanism of Lycium barbarum polysaccharides on primary cultured rat hippocampal neurons - Peng Zhao; Ning-Tian Ma; Ren-Yuan Chang; Yu-Xiang Li; Yin-Ju Hao; Wen-Li Yang; Jie Zheng; Yang Niu; Tao Sun; Jian-Qiang Yu (Cell and Tissue Research, 2017)

Orexin Directly Enhances the Excitability of Globus Pallidus Internus Neurons in Rat by Co-activating OX1 and OX2 Receptors - He-Ren Gao; Qian-Xing Zhuang; Yong-Xiao Zhang; Zhang-Peng Chen; Bin Li; Xiao-Yang Zhang; Yi-Ting Zhong; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2017)

A new phenol glycoside from Physalis angulata - Cheng-Peng Sun; Xiu-Fang Nie; Ning Kang; Feng Zhao; Li-Xia Chen; Feng Qiu (Natural Product Research, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Carbon isotopic composition and genetic types of natural gas in the Sichuan Basin, China - Jin-ning Peng; Dong-yan Wang; Guang-xiang Liu; Min Zhang; Feng-li Li (Acta Geochimica, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Sugar Industry and Improved Sugarcane Farming Technologies in China - Yang-Rui Li; Xiu-Peng Song; Jian-Ming Wu; Chang-Ning Li; Qiang Liang; Xi-Hui Liu; Wei-Zan Wang; Hong-Wei Tan; Li-Tao Yang (Sugar Tech, 2016)

Aging of solidified/stabilized electrolytic manganese solid waste with accelerated carbonation and aging inhibition - Bing Du; Changbo Zhou; Zhigang Dan; Zhiyuan Zhao; Xianjia Peng; Jianguo Liu; Ning Duan (Environmental Science and Pollution Research, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

The Rab1 in host cells modulates Brucella intracellular survival and binds to Brucella DnaK protein - Ning Liu; Changjiang Sun; Guimei Cui; Pan Wei; Li Yang; Wanchun Sun; Shuangxi Wang; Lin Wang; Qisheng Peng (Archives of Microbiology, 2016)

A Novel PhLRR Gene Promoter is Sufficient for Engineering Male Sterility in Petunia - Yuanzheng Yue; Di Yang; Jian Sun; Hao Peng; Chaoqun Yin; Rui Guo; Guogui Ning; Huirong Hu (Plant Molecular Biology Reporter, 2016)

Impact of genetic polymorphisms related to clopidogrel or acetylsalicylic acid pharmacology on clinical outcome in Chinese patients with symptomatic extracranial or intracranial stenosis - Zhigang Zhao; Xingang Li; Shusen Sun; Shenghui Mei; Ning Ma; Zhongrong Miao; Ming Zhao; Shiqi Peng (European Journal of Clinical Pharmacology, 2016)

3D modeling of geological anomalies based on segmentation of multiattribute fusion - Zhi-Ning Liu; Cheng-Yun Song; Zhi-Yong Li; Han-Peng Cai; Xing-Miao Yao; Guang-Min Hu (Applied Geophysics, 2016)

Holocene high lake-levels and pan-lake period on Badain Jaran Desert - NaiAng Wang; Kai Ning; ZhuoLun Li; YiXin Wang; Peng Jia; Ling Ma (Science China Earth Sciences, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Physalin A induces G2/M phase cell cycle arrest in human non-small cell lung cancer cells: involvement of the p38 MAPK/ROS pathway - Ning Kang; Jun-feng Jian; Shi-jie Cao; Qiang Zhang; Yi-wei Mao; Yi-yuan Huang; Yan-fei Peng; Feng Qiu; Xiu-mei Gao (Molecular and Cellular Biochemistry, 2016)

The angiogenic variation of skeletal site-specific human BMSCs from same alveolar cleft patients: a comparative study - Yifei Du; Fei Jiang; Yi Liang; Yuli Wang; Weina Zhou; Yongchu Pan; Mingfei Xue; Yan Peng; Huan Yuan; Ning Chen; Hongbing Jiang (Journal of Molecular Histology, 2016)

Pre-stack-texture-based reservoir characteristics and seismic facies analysis - Cheng-Yun Song; Zhi-Ning Liu; Han-Peng Cai; Feng Qian; Guang-Min Hu (Applied Geophysics, 2016)

Assembly and immunogenicity of baculovirus-derived infectious bronchitis virus–like particles carrying membrane, envelope and the recombinant spike proteins - Peng-wei Xu; Xuan Wu; Hong-ning Wang; Bing-cun Ma; Meng-die Ding; Xin Yang (Biotechnology Letters, 2016)

Development of an ELISA based on a multi-fragment antigen of infectious bronchitis virus for antibodies detection - Meng-die Ding; Xin Yang; Hong-ning Wang; An-yun Zhang; Zhi-kun Zhang; Wen-qiao Fan; Hai-peng Cao (Biotechnology Letters, 2015)

Retraction Note to: The role of TGFβ1 stimulating ROCK I signal pathway to reorganize actin in a rat experimental model of developmental dysplasia of the hip - Xinhong Pei; Yueqiang Mo; Bo Ning; Zhe Yuan; Luying Peng; Ruixue Ma (Molecular and Cellular Biochemistry, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Selective Production of Levoglucosenone from Catalytic Fast Pyrolysis of Biomass Mechanically Mixed with Solid Phosphoric Acid Catalysts - Zhi-bo Zhang; Qiang Lu; Xiao-ning Ye; Ti-peng Wang; Xian-hua Wang; Chang-qing Dong (BioEnergy Research, 2015)

Pcdh11x Negatively Regulates Dendritic Branching - Cuiying Wu; Lijun Niu; Zhongjie Yan; Chong Wang; Ning Liu; Yiwu Dai; Peng Zhang; Ruxiang Xu (Journal of Molecular Neuroscience, 2015)

First insights into the microbial diversity in the omasum and reticulum of bovine using Illumina sequencing - Shuai Peng; Jigang Yin; Xiaolei Liu; Boyin Jia; Zhiguang Chang; Huijun Lu; Ning Jiang; Qijun Chen (Journal of Applied Genetics, 2015)

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

Detection and attribution of vegetation greening trend in China over the last 30 years - Shilong Piao; Guodong Yin; Jianguang Tan; Lei Cheng; Mengtian Huang; Yue Li; Ronggao Liu; Jiafu Mao; Ranga B. Myneni; Shushi Peng; Ben Poulter; Xiaoying Shi; et al. (Global Change Biology, 2015)
The reliable detection and attribution of changes in vegetation growth is a prerequisite for the development of strategies for the sustainable management of ecosystems. This is an extraordinary challenge. To our knowledge, this study is the first to comprehensively detect and attribute a greening trend in China over the last three decades. We use three different satellite‐derived Leaf Area Index ( LAI ) datasets for detection as well as five different process‐based ecosystem models for attribution. Rising atmospheric CO 2 concentration and nitrogen deposition are identified as the most likely causes of the greening trend in China, explaining 85% and 41% of the average growing‐season LAI trend ( LAI GS ) estimated by satellite datasets (average trend of 0.0070 yr −1 , ranging from 0.0035 yr −1 to 0.0127 yr −1 ), respectively. The contribution of nitrogen deposition is more clearly seen in southern China than in the north of the country. Models disagree about the contribution of climate change alone to the trend in LAI GS at the country scale (one model shows a significant increasing trend, whereas two others show significant decreasing trends). However, the models generally agree on the negative impacts of climate change in north China and Inner Mongolia and the positive impact in the Qinghai–Xizang plateau. Provincial forest area change tends to be significantly correlated with the trend of LAI GS ( P P = 0.07) correlated with the residual of LAI GS trend, calculated as the trend observed by satellite minus that estimated by models through considering the effects of climate change, rising CO 2 concentration and nitrogen deposition, across different provinces. This result highlights the important role of China's afforestation program in explaining the spatial patterns of trend in vegetation growth.

A new daphnane diterpenoid from Excoecaria venenata with inhibitory effect on human leukaemia HL-60 cells - De-Sheng Ning; Li-Yan Peng; Shi-Hong Lv; Dian-Peng Li; Zheng-Hong Pan (Natural Product Research, 2015)

Glial fibrillary acidic protein promoters direct adenovirus early 1A gene and human telomerase reverse transcriptase promoters direct sodium iodide symporter expression for malignant glioma radioiodine therapy - Wei Li; Jian Tan; Peng Wang; Ning Li; Chengxia Li (Molecular and Cellular Biochemistry, 2015)

Adjusting migration schedules at stopping sites: time strategy of a long-distance migratory shorebird during northward migration - He-Bo Peng; Ning Hua; Chi-Yeung Choi; David S. Melville; Yan Gao; Qianyan Zhou; Ying Chen; Wenjie Xue; Qiang Ma; Wei Wu; Chendong Tang; Zhijun Ma (Journal of Ornithology, 2015)

Overexpression of MicroRNA-122 Re-sensitizes 5-FU-Resistant Colon Cancer Cells to 5-FU Through the Inhibition of PKM2 In Vitro and In Vivo - Jinxia He; Ganfeng Xie; Jingtao Tong; Yonghai Peng; Haihui Huang; Jianjun Li; Ning Wang; Houjie Liang (Cell Biochemistry and Biophysics, 2014)

Hsa-miR-1246, hsa-miR-320a and hsa-miR-196b-5p inhibitors can reduce the cytotoxicity of Ebola virus glycoprotein in vitro - MiaoMiao Sheng; Ying Zhong; Yang Chen; JianChao Du; XiangWu Ju; Chen Zhao; GuiGen Zhang; LiFang Zhang; KangTai Liu; Ning Yang; Peng Xie; DangSheng Li; et al. (Science China Life Sciences, 2014)

Protocadherin 11 X Regulates Differentiation and Proliferation of Neural Stem Cell In Vitro and In Vivo - Peng Zhang; Cuiying Wu; Ning Liu; Lijun Niu; Zhongjie Yan; Yanyan Feng; Ruxiang Xu (Journal of Molecular Neuroscience, 2014)

Establishment and optimization of a regionally applicable maize gene-flow model - Ning Hu; Jichao Hu; Xiaodong Jiang; Zongzhi Lu; Yufa Peng; Wanlong Chen; Kemin Yao; Ming Zhang; Shirong Jia; Xinwu Pei; Weihong Luo (Transgenic Research, 2014)

Different types of nitrogen deposition show variable effects on the soil carbon cycle process of temperate forests - Yuhan Du; Peng Guo; Jianqiu Liu; Chunyu Wang; Ning Yang; Zhenxia Jiao (Global Change Biology, 2014)
Nitrogen (N) deposition significantly affects the soil carbon (C) cycle process of forests. However, the influence of different types of N on it still remained unclear. In this work, ammonium nitrate was selected as an inorganic N ( IN ) source, while urea and glycine were chosen as organic N ( ON ) sources. Different ratios of IN to ON (1 : 4, 2 : 3, 3 : 2, 4 : 1, and 5 : 0) were mixed with equal total amounts and then used to fertilize temperate forest soils for 2 years. Results showed that IN deposition inhibited soil C cycle processes, such as soil respiration, soil organic C decomposition, and enzymatic activities, and induced the accumulation of recalcitrant organic C. By contrast, ON deposition promoted these processes. Addition of ON also resulted in accelerated transformation of recalcitrant compounds into labile compounds and increased CO 2 efflux. Meanwhile, greater ON deposition may convert C sequestration in forest soils into C source. These results indicated the importance of the IN to ON ratio in controlling the soil C cycle, which can consequently change the ecological effect of N deposition.

Response of the bacterial diversity and soil enzyme activity in particle-size fractions of Mollisol after different fertilization in a long-term experiment - Ning Ling; Yuming Sun; Jinghua Ma; Junjie Guo; Ping Zhu; Chang Peng; Guanghui Yu; Wei Ran; Shiwei Guo; Qirong Shen (Biology and Fertility of Soils, 2014)

Influence of casein phosphopeptide-amorphous calcium phosphate application, smear layer removal, and storage time on resin-dentin bonding - Jun Lin; Wei-ying Zheng; Peng-ruo-feng Liu; Ning Zhang; Hui-ping Lin; Yi-jing Fan; Xin-hua Gu; Oliver Vollrath; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2014)

Rapid Fluorescent Detection of Escherichia coli K88 Based on DNA Aptamer Library as Direct and Specific Reporter Combined With Immuno-Magnetic Separation - Zhihui Peng; Min Ling; Yi Ning; Le Deng (Journal of Fluorescence, 2014)

RETRACTED ARTICLE: The role of TGFβ1 stimulating ROCK I signal pathway to reorganize actin in a rat experimental model of developmental dysplasia of the hip - Xinhong Pei; Yueqiang Mo; Bo Ning; Zhe Yuan; Luying Peng; Ruixue Ma (Molecular and Cellular Biochemistry, 2014)

Role of Unfolded Protein Response in Affecting Osteoblast Differentiation Induced by Fluoride - Xi-ning Li; Peng Lv; Zhi Sun; Guang-sheng Li; Hui Xu (Biological Trace Element Research, 2014)

Effects of lipopolysaccharide-induced inflammation on the interstitial cells of Cajal - Jia Wei; Ning Li; Xue Xia; Xuyong Chen; Fei Peng; Gail E. Besner; Jiexiong Feng (Cell and Tissue Research, 2014)

Large-Eddy Simulation of Mesoscale Circulations Forced by Inhomogeneous Urban Heat Island - Ning Zhang; Xueyuan Wang; Zhen Peng (Boundary-Layer Meteorology, 2014)

A new triterpenoid saponin from the root of Croton lachnocarpus Benth. - Zheng-Hong Pan; De-Sheng Ning; Jin-Lei Liu; Bo Pan; Dian-Peng Li (Natural Product Research, 2014)

A Quantitative Method to Control and Adjust the Accuracy of Adaptive Grid Depth Modeling - Zhang Lihua; Jia Shuaidong; Peng Rencan; Dong Jian; Li Ning (Marine Geodesy, 2013)

Heat shock factor OsHsfB2b negatively regulates drought and salt tolerance in rice - Jianhua Xiang; Jing Ran; Jie Zou; Xiaoyun Zhou; Ailing Liu; Xianwen Zhang; Yan Peng; Ning Tang; Guangyu Luo; Xinbo Chen (Plant Cell Reports, 2013)

Discovery of indeno[1,2- $$c$$ c ]quinoline derivatives as dual topoisomerases I/II inhibitors: Part 3 - Chih-Hua Tseng; Cherng-Chyi Tzeng; Chiao-Li Yang; Pei-Jung Lu; Yu-Peng Liu; Hui-Ling Chen; Chien-Yu Chen; Chia-Ning Yang; Yeh-Long Chen (Molecular Diversity, 2013)

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis - Shan Yan; Na Wang; Zhen Chen; Yuanpeng Wang; Ning He; Yajuan Peng; Qingbiao Li; Xu Deng (Functional & Integrative Genomics, 2013)

Viability inhibition effect of gambogic acid combined with cisplatin on osteosarcoma cells via mitochondria-independent apoptotic pathway - Wei Zhao; Chang-Cheng You; Jin-Peng Zhuang; Jia-Ning Zu; Zhi-Yong Chi; Gong-Ping Xu; Jing-Long Yan (Molecular and Cellular Biochemistry, 2013)

The impacts of climate change and human activities on biogeochemical cycles on the Q inghai‐ T ibetan P lateau - Huai Chen; Qiuan Zhu; Changhui Peng; Ning Wu; Yanfen Wang; Xiuqing Fang; Yongheng Gao; Dan Zhu; Gang Yang; Jianqing Tian; Xiaoming Kang; Shilong Piao; et al. (Global Change Biology, 2013)
With a pace of about twice the observed rate of global warming, the temperature on the Qinghai‐Tibetan Plateau (Earth's ‘third pole’) has increased by 0.2 °C per decade over the past 50 years, which results in significant permafrost thawing and glacier retreat. Our review suggested that warming enhanced net primary production and soil respiration, decreased methane ( CH 4 ) emissions from wetlands and increased CH 4 consumption of meadows, but might increase CH 4 emissions from lakes. Warming‐induced permafrost thawing and glaciers melting would also result in substantial emission of old carbon dioxide ( CO 2 ) and CH 4 . Nitrous oxide ( N 2 O ) emission was not stimulated by warming itself, but might be slightly enhanced by wetting. However, there are many uncertainties in such biogeochemical cycles under climate change. Human activities (e.g. grazing, land cover changes) further modified the biogeochemical cycles and amplified such uncertainties on the plateau. If the projected warming and wetting continues, the future biogeochemical cycles will be more complicated. So facing research in this field is an ongoing challenge of integrating field observations with process‐based ecosystem models to predict the impacts of future climate change and human activities at various temporal and spatial scales. To reduce the uncertainties and to improve the precision of the predictions of the impacts of climate change and human activities on biogeochemical cycles, efforts should focus on conducting more field observation studies, integrating data within improved models, and developing new knowledge about coupling among carbon, nitrogen, and phosphorus biogeochemical cycles as well as about the role of microbes in these cycles.

Role of Endoplasmic Reticulum Stress in Aberrant Activation of Fluoride-Treated Osteoblasts - Yu-lai Zhou; Hong-yan Shi; Xi-ning Li; Peng Lv; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2013)

Sequence analysis of the whole genome of a recombinant Marek’s disease virus strain, GX0101, with a reticuloendotheliosis virus LTR insert - Shuai Su; Ning Cui; Aijun Sun; Yanpeng Li; Jiabo Ding; Zimeng Chen; Peng Zhao; Zhizhong Cui (Archives of Virology, 2013)

(−)-Epigallocatechin-3-gallate alleviates spatial memory impairment in APP/PS1 mice by restoring IRS-1 signaling defects in the hippocampus - Ning Jia; Kun Han; Jing-Jing Kong; Xiu-Mei Zhang; Sha Sha; Gui-Ru Ren; Yun-Peng Cao (Molecular and Cellular Biochemistry, 2013)

Complete genome sequence of enterovirus 87 isolated from a child with acute flaccid paralysis in China in 2000 - Zexin Tao; Ning Cui; Aiqiang Xu; Feng Ji; Lizhi Song; Xiaojuan Lin; Ping Xiong; Haiyan Wang; Suting Wang; Peng Chen; Yanyan Song (Virus Genes, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

miR-30a downregulation aggravates pressure overload-induced cardiomyocyte hypertrophy - Xuesong Yin; Chenghai Peng; Wenhu Ning; Chunyan Li; Zhongqiao Ren; Jihong Zhang; Han Gao; Kan Zhao (Molecular and Cellular Biochemistry, 2013)

Molecular cloning, sequence characterization, SNP detection, and tissue expression analysis of duck FMO3 gene - Peng Wang; Jiangxia Zheng; Lujiang Qu; Ling Lian; Guiyun Xu; Ning Yang (Molecular and Cellular Biochemistry, 2013)

Jasmonates modulate the promotion effects induced by SNP on root development of wheat under osmotic stress through lipoxygenase activation - Xianye Wang; Ning Wang; Qi Rui; Peng Zhang; Langlai Xu (Journal of Plant Biochemistry and Biotechnology, 2013)

Source apportionment of polycyclic aromatic hydrocarbons in surface sediments of the Bohai Sea, China - Ning-Jing Hu; Peng Huang; Ji-Hua Liu; Xue-Fa Shi; De-Yi Ma; Ying Liu (Environmental Science and Pollution Research, 2013)

Isolation and genomic characterization of three enterovirus 90 strains in Shandong, China - Zexin Tao; Ning Cui; Aiqiang Xu; Yao Liu; Lizhi Song; Yan Li; Haiyan Wang; Feng Ji; Peng Chen; Yanyan Song (Archives of Virology, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Methane emissions from rice paddies natural wetlands, lakes in China: synthesis new estimate - Huai Chen; Qiu'an Zhu; Changhui Peng; Ning Wu; Yanfen Wang; Xiuqin Fang; Hong Jiang; Wenhua Xiang; Jie Chang; Xiangwen Deng; Guirui Yu (Global Change Biology, 2013)
Sources of methane ( CH 4 ) become highly variable for countries undergoing a heightened period of development due to both human activity and climate change. An urgent need therefore exists to budget key sources of CH 4 , such as wetlands (rice paddies and natural wetlands) and lakes (including reservoirs and ponds), which are sensitive to these changes. For this study, references in relation to CH 4 emissions from rice paddies, natural wetlands, and lakes in C hina were first reviewed and then reestimated based on the review itself. Total emissions from the three CH 4 sources were 11.25 Tg CH 4 yr −1 (ranging from 7.98 to 15.16 Tg CH 4 yr −1 ). Among the emissions, 8.11 Tg CH 4 yr −1 (ranging from 5.20 to 11.36 Tg CH 4 yr −1 ) derived from rice paddies, 2.69 Tg CH 4 yr −1 (ranging from 2.46 to 3.20 Tg CH 4 yr −1 ) from natural wetlands, and 0.46 Tg CH 4 yr −1 (ranging from 0.33 to 0.59 Tg CH 4 yr −1 ) from lakes (including reservoirs and ponds). Plentiful water and warm conditions, as well as its large rice paddy area make rice paddies in southeastern C hina the greatest overall source of CH 4 , accounting for approximately 55% of total paddy emissions. Natural wetland estimates were slightly higher than the other estimates owing to the higher CH 4 emissions recorded within Q inghai‐ T ibetan P lateau peatlands. Total CH 4 emissions from lakes were estimated for the first time by this study, with three quarters from the littoral zone and one quarter from lake surfaces. Rice paddies, natural wetlands, and lakes are not constant sources of CH 4 , but decreasing ones influenced by anthropogenic activity and climate change. A new progress‐based model used in conjunction with more observations through model‐data fusion approach could help obtain better estimates and insights with regard to CH 4 emissions deriving from wetlands and lakes in C hina.

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

Fraction characteristics of rare earth elements in the surface sediment of Bohai Bay, North China - Yayan Xu; Jinming Song; Liqin Duan; Xuegang Li; Huamao Yuan; Ning Li; Peng Zhang; Ying Zhang; Sisi Xu; Mo Zhang; Xiaodan Wu; Xuebo Yin (Environmental Monitoring and Assessment, 2012)

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Spatiotemporal Variations in Nitrous Oxide Emissions from an Open Fen on the Qinghai–Tibetan Plateau: a 3-Year Study - Huai Chen; Yanfen Wang; Ning Wu; Dan Zhu; Wei Li; Yongheng Gao; Qiu’an Zhu; Gang Yang; Changhui Peng (Water, Air, & Soil Pollution, 2012)

The return periods and risk assessment of severe dust storms in Inner Mongolia with consideration of the main contributing factors - Xueqin Liu; Ning Li; Wei Xie; Jidong Wu; Peng Zhang; Zhonghui Ji (Environmental Monitoring and Assessment, 2012)

Different effects of omega-3 fatty acids on the cell cycle in C2C12 myoblast proliferation - Yunqian Peng; Yu Zheng; Yunsheng Zhang; Jie Zhao; Fei Chang; Tianyu Lu; Ran Zhang; Qiuyan Li; Xiaoxiang Hu; Ning Li (Molecular and Cellular Biochemistry, 2012)

Transition of human diets and agricultural economy in Shenmingpu Site, Henan, from the Warring States to Han Dynasties - LiangLiang Hou; Ning Wang; Peng Lü; YaoWu Hu; GuoDing Song; ChangSui Wang (Science China Earth Sciences, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

Insulin-Like Growth Factor Binding Protein 7 Modulates Estrogen-Induced Trophoblast Proliferation and Invasion in HTR-8 and JEG-3 Cells - Zhen-Kun Liu; Hai-Yan Liu; Wen-Ning Fang; Ying Yang; Hong-Mei Wang; Jing-Pian Peng (Cell Biochemistry and Biophysics, 2012)

Glypican-3, a novel prognostic marker of hepatocellular cancer, is related with postoperative metastasis and recurrence in hepatocellular cancer patients - Su Ning; Chen Bin; Huang Na; Shen Peng; Ding Yi; Ye Xiang-hua; Zeng Fang-yin; Zheng Da-yong; Luo Rong-cheng (Molecular Biology Reports, 2012)

Selecting the optimum location of the corner using gravity gradient method - Peng-Fei Sun; Yan-Gang Wu; Chun-Cheng Yang; Zhao-Hong Han; Mei-Ning Fan (Applied Geophysics, 2011)

Nitrous oxide fluxes from the littoral zone of a lake on the Qinghai-Tibetan Plateau - Huai Chen; Meng Wang; Ning Wu; Yanfen Wang; Dan Zhu; Yongheng Gao; Changhui Peng (Environmental Monitoring and Assessment, 2011)

Molecular Cloning and Expression Analysis of Porcine Ghrelin O-Acyltransferase - Tonghui Lin; Qingyong Meng; Dandan Sui; Dezhi Peng; Yang Li; Xiaofang Liu; Longfei Xie; Ning Li (Biochemical Genetics, 2011)

Complexity and characteristic frequency studies in ECG signals of mice based on multiple scale factors - XiaoDong Yang; AiJun He; Peng Liu; TongFeng Sun; XinBao Ning (Science China Life Sciences, 2011)

Genetic Linkage Mapping and Analysis of Muscle Fiber-Related QTLs in Common Carp (Cyprinus carpio L.) - Yan Zhang; Peng Xu; Cuiyun Lu; Youyi Kuang; Xiaofeng Zhang; Dingchen Cao; Chao Li; Yumei Chang; Ning Hou; Hengde Li; Shu Wang; Xiaowen Sun (Marine Biotechnology, 2011)

Standing crop and primary production of benthic microalgae on the tidal flats in Yueqing Bay - Qiang Hao; Yuming Cai; Xiuren Ning; Chenggang Liu; Xin Peng; Xuexi Tang (Journal of Ocean University of China, 2011)

Methane Fluxes from Alpine Wetlands of Zoige Plateau in Relation to Water Regime and Vegetation under Two Scales - Huai Chen; Ning Wu; Yanfen Wang; Yongheng Gao; Changhui Peng (Water, Air, & Soil Pollution, 2011)

Predominance of Precipitation and Temperature Controls on Ecosystem CO2 Exchange in Zoige Alpine Wetlands of Southwest China - Yan Bin Hao; Xiao Yong Cui; Yan Fen Wang; Xu Rong Mei; Xiao Ming Kang; Ning Wu; Peng Luo; Dan Zhu (Wetlands, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Efficacy of a novel endotoxin adsorber polyvinylidene fluoride fiber immobilized with L-serine ligand on septic pigs - Jian-ping Gao; Man Huang; Ning Li; Peng-fei Wang; Huan-lin Chen; Qiu-ping Xu (Journal of Zhejiang University-SCIENCE B, 2011)

Investigation of the Interaction Between the Ser447Term Polymorphism of Lipoprotein Lipase and the Stroke-Related Risk Factors in Ischemic Stroke - Yumei Yang; Danhua Du; Peng Gao; Xuan Zhang; Ning Wu; Feng Wang; Zhenqi Wang; Lin Ye; Jiang Wu; Ian L. Megson; Jun Wei (Translational Stroke Research, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Impacts of long-term inorganic and organic fertilization on lignin in a Mollisol - Ning Liu; Hongbo He; Hongtu Xie; Zhen Bai; Xudong Zhang; Chang Peng; Ping Zhu; Jun Ren; Lichun Wang (Journal of Soils and Sediments, 2010)

Cytotoxic Activity and DNA-binding Properties of Xanthone Derivatives - Rui Shen; Peng Wang; Ning Tang (Journal of Fluorescence, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Synthesis, Crystal Structure, DNA-binding Properties and Cytotoxic Activity of the Copper (II) Complex Involving Xanthone - Rui Shen; Peng Wang; Ning Tang (Journal of Fluorescence, 2009)

Sedentarization of Tibetan Nomads - Tao Lu; Ning Wu; Peng Luo (Conservation Biology, 2009)

Tumor-inhibitory and liver-protective effects of Phellinus igniarius extracellular polysaccharides - Wei Dong; Li Ning; Wei-dong Lu; Cui-cui Li; Rui-peng Chen; Xiao-ning Jia; Lin Wang; Li-zhong Guo (World Journal of Microbiology and Biotechnology, 2009)

Analysis of dynamics and driving factors of wetland landscape in Zoige, Eastern Qinghai-Tibetan Plateau - Pengfei Qiu; Ning Wu; Peng Luo; Zuyuan Wang; Maihe Li (Journal of Mountain Science, 2009)

Effect of snow-cover duration on plant species diversity of alpine meadows on the eastern Qinghai-Tibetan Plateau - Wennian Chen; Yan Wu; Ning Wu; Peng Luo (Journal of Mountain Science, 2008)

Isolation and identification of a potential biocontrol agent Bacillus subtilis QM3 from Qinghai yak dung in China - Qing-Ping Hu; Jian-Guo Xu; Peng Song; Jin-Ning Song; Wu-Ling Chen (World Journal of Microbiology and Biotechnology, 2008)

Apoptosis induced by ardipusilloside III through BAD dephosphorylation and cleavage in human glioblastoma U251MG cells - Hong Lin; Xiang Zhang; Guang Cheng; Hai-Feng Tang; Wei Zhang; Hai-Ning Zhen; Jin-Xiang Cheng; Bo-Lin Liu; Wei-Dong Cao; Wen-Peng Dong; Peng Wang (Apoptosis, 2008)

Purification and characterization of trypsin-like enzymes from North Pacific krill (Euphausia pacifica) - Zhiqiang Wu; Guoliang Jiang; Peng Xiang; Dong Yang; Ning Wang (Biotechnology Letters, 2007)

Differential effects of ceramide species on exocytosis in rat PC12 cells - Ning Tang; Wei-Yi Ong; En-Ming Zhang; Peng Chen; Jin-Fei Yeo (Experimental Brain Research, 2007)

Improvement of the multiple-stress tolerance of an ethanologenic Saccharomyces cerevisiae strain by freeze-thaw treatment - Pingying Wei; Zilong Li; Yuping Lin; Peng He; Ning Jiang (Biotechnology Letters, 2007)

Involvement of PDCD5 in the regulation of apoptosis in fibroblast-like synoviocytes of rheumatoid arthritis - Ning Wang; Hou-Shan Lu; Zhen-Peng Guan; Tie-Zheng Sun; Ying-Yu Chen; Guo-Rui Ruan; Zhan-Kun Chen; Jun Jiang; Chu-Jie Bai (Apoptosis, 2007)

Identification and functional characterization of a leucine-rich repeat receptor-like kinase gene that is involved in regulation of soybean leaf senescence - Xiao-Ping Li; Rui Gan; Peng-Li Li; Yuan-Yuan Ma; Li-Wen Zhang; Ren Zhang; Yong Wang; Ning Ning Wang (Plant Molecular Biology, 2006)

Differential expression of genes encoding 1-aminocyclopropane-1-carboxylate synthase in Arabidopsis during hypoxia - Hsiao-Ping Peng; Ter-Yun Lin; Ning-Ning Wang; Ming-Che Shih (Plant Molecular Biology, 2005)

(R)-Oxynitrilase-catalysed synthesis of chiral silicon-containing aliphatic (R)-ketone-cyanohydrins - Ning Li; Min-Hua Zong; Chen Liu; Hua-Song Peng; Hua-Chang Wu (Biotechnology Letters, 2003)